Analytical solution for a circular shield tunnel with ground-lining interaction considering gravity and non-uniform deformation - Jinyang Fu; Bo Wang; Haoyu Wang; Xinghua Fang; Junsheng Yang; Jiarui Yin; Xiangyu Chen (European Journal of Environmental and Civil Engineering, 2026)

UV-C treatment modulates storage performance and aroma metabolism of postharvest litchi fruit - Liyu Fu; Jinghui Yang; Yawen Li; Sijie Li; Xuequn Pang; Zhaoqi Zhang; Fang Fang (Postharvest Biology and Technology, 2026)

Higher mitochondrial DNA methylation is associated with increased risk of stroke: a nested case-control study - Xueru Fu; Yuewan Fang; Yujie Zhao; Bin Yang; Yaqin Su; Li Yang; Weifeng Huo; Liuding Wen; Yuying Wu; Yang Zhao; Fulan Hu; Ming Zhang; et al. (Human Genetics, 2026)

Integration of clinical and cellular lipidomics identifies a serum metabolite signature predictive of oxaliplatin resistance in colorectal cancer - Xue-fei Wu; Li-ye Xie; Fu-wei Lian; Hao-tang Wei; Shu-fang Ning; Bang-li Hu (Functional & Integrative Genomics, 2026)

Impacts of different ozone treatments on the growth and soil bacterial community of Pinellia ternata - Yucheng Qiu; Xi Feng; Xiangrui Fu; Xiaoying Shang; Yunsheng Zhao; Donglai Ma; Huiyong Fang; Xian Gu (Brazilian Journal of Microbiology, 2026)

Diverse bioactive metabolites from Callicarpa longifolia var. floccosa: terpenoids, polyketide, and callilongiflocin A as a potent anti-inflammatory diterpenoid targeting IL-17/TNF-α/MAPK signaling with anti-psoriatic activity - Ting Liu; Xiao-Lu Wu; Lian-Chun Li; Lan-Fang Tan; De-Sheng Ning; Yu-Xia Fu; Zheng-Hong Pan (Phytochemistry, 2026)

Integrating human perceptions into ecological restoration: Analyzing the mismatches and barriers between ecological components, ecosystem services, and human perceptions in riparian green spaces - Ce Wen; Fan Yang; Xing Zhang; Hongda Fang; Yuanpeng Fu; Xuxi Zhou; Changzhou Yan (Ecological Engineering, 2026)

Fabrication of microwave-absorbing MFe2O4@sepiolite (M = Mn, Mn0.5Ni0.5, Ni) nanorods with enhanced catalytic performance for degradation and assessment of intermediate toxicity - Ruolin Ni; Lei Jiang; Jinhui Lin; Dan Wu; Keming Zhang; Lu Fu; Zhaohong Zhang; Fang Ma; Yongcai Zhang (Applied Clay Science, 2026)

A chiral metal-organic cage Al-CMOC for high-resolution gas chromatographic separation - Xiao-Fang Shu; An-Xu Ma; Fu Li; Chang-Xiu Ma; Jin Liu; Xu-Xu Jin; Sheng-Ming Xie; Bang-Jin Wang; Jia-Ni Yang; Jun-Hui Zhang; Li-Ming Yuan (Analytica Chimica Acta, 2026)

miR-325–3p targets GSDMD in macrophages to attenuate lung injury induced by Streptococcus equi subsp. zooepidemicus - Yajuan Li; Li Jiang; Qiuguo Fang; Xiali Yu; Jingyu Yu; Shun Li; Yunfei Huang; Feixiang Huang; Jiedan Liao; Qiang Fu (Veterinary Immunology and Immunopathology, 2026)

Differential immobilization mechanisms of calcium silicate-based materials toward Pb(Ⅱ) and Cd(Ⅱ): From adsorption characteristics to long-term leaching stability - Wenjun Fu; Jiangjie Fang; Yongdian Yue; Xinzhuang Fu; Chuanxi Peng; Di Chen; Youchuan Chen; Tong Yue (Journal of Environmental Chemical Engineering, 2026)

Metal-polyphenol network-coated probiotic microcapsules: Enhancing Limosilactobacillus fermentum storage stability and yogurt characteristics - Yi-han Cai; Fang Huang; Si-ying Yan; Xiao-jin Lin; Shu-ling Huang; Shao-fu Feng; Jie-ying Chen; Yan-yan Huang; Xin-An Zeng; Xiang-ze Jia (International Dairy Journal, 2026)

Numerical study on the design and performance of cathode flow channels in solid oxide fuel cells based on bionic airfoil structures - Lirong Fu; Xuan Fang; Jinyi Liu; Mingwei Li (Fuel, 2026)

Study on the water-holding mechanism of chicken feet adding with lactic acid bacteria fermentation broth and L-arginine - Shiqi Fu; Lingxu Guo; Fang Yang; Pei Gao; Qixing Jiang; Wenshui Xia; Hong Chen (Food Research International, 2026)

The vigor of recalcitrant seeds regulates the aril aroma release via phytohormones jasmonic acid and salicylic acid in litchi fruits - Liyu Fu; Yawen Li; Ruihao Zhong; Sijie Li; Jinghui Yang; Haoshuang Sun; Xuequn Pang; Xuemei Huang; Zhaoqi Zhang; Fang Fang (Food Chemistry, 2026)

Decoding the partitioning behavior of poly- and perfluoroalkyl substances: Insights from human liver and blood biomonitoring with machine learning - Linping Cao; Yishu Zheng; Wenfei Yu; Jiaqi Shao; Yu Fu; Yating Liu; Weichen Zhang; Jiamian Fang; Yuanchen Chen; Hangbiao Jin (Environmental Pollution, 2026)

Nanoscale interfacial scaffold enables perovskite/silicon tandems with 34% efficiency and an open-circuit voltage over 2.01 V - Huimin Zhang; Qingshui Zheng; Hongbo Mo; Fu Zhang; Zhijie Rao; Linyu Ning; Yue Yin; Dongsheng Yang; Zheng Fang; Lei Ding; Yongcai He; Xixiang Xu; et al. (Science Bulletin, 2026)

Rhizophagus intraradices differentially promotes growth and phosphorus uptake in Camellia oleifera under low versus adequate phosphorus supply - Wan-Lin Fu; Ying-Ning Zou; Shi-Qi Pu; Fang-Ling Wang; Zhi-Yan Xiao; Jun-Yong Cheng; Mei-Hua Yang; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

LsS6K acts as a negative regulator of thiamethoxam tolerance in Laodelphax striatellus - Shu Fang; Yuyang Shi; Mi Zhou; Huijun Zhang; Hong Fu; Qun Zheng; Kun Qian; Jianjun Wang (Pesticide Biochemistry and Physiology, 2026)

An interpretable generative learning-based tri-objective optimization framework for tidal turbine hydrofoil design - Longyan Wang; Yu Fang; Xuanjie Zhu; Tianshun Xia; Jian Xu; Jianping Yuan; Yanxia Fu (Ocean Engineering, 2026)

Upstream costs of the energy transition: differentiated mechanisms of economic–environmental synergy in lithium development systems - Jianan Wang; Wei Fang; Haizhong An; Jinyu Fang; Yujia Fu (Journal of Environmental Management, 2026)

Dual-color ultrabright AIEgens nanoparticles-based lateral flow immunoassay for simultaneous quantitative detection of serum amyloid A protein and C-reactive protein - Lun Bian; Yuhang Yang; Yu Fu; Kuangrou Jia; Xiangzhou Liu; Xueqing Xu; Yingsong Wu; Fang Hu; Guanfeng Lin (Analytica Chimica Acta, 2026)

Transcription factor LbUBC positively regulates salt gland development and salt tolerance by directly binding to the LbTTG1 promoter and repressing its transcription - Shuyue Fu; Yuqing Tan; Jianfei Ma; Baoshan Wang; Fang Yuan (Plant Cell Reports, 2026)

Multi-omics analysis of untargeted metabolomics and gut microbiota study on the mechanism of Astragalus-Safflower to coordinate the regulation of energy metabolism pathways and gut microbiota remodeling to improve ischemic stroke - Junmin Fu; Fuyu Liu; Yun Han; Yonggang Feng; Kaixin Shan; Mimi Wang; Xiang Meng; Haibo Zhang; Mingsan Miao; Suxiang Feng; Xiaoyan Fang (Metabolic Brain Disease, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Multi-driver landslide disasters: distribution, formation, and mitigation - Shufeng Tian; Ningsheng Chen; Haitao Ding; Xiangyu Shao; Mengjie Jiao; Yongjian Li; Jiming Jin; Muhib Ullah Khan; Mingyang Wu; Xiaohu Chen; Bishal Gurung; Yongzhi Wang; et al. (Science Bulletin, 2026)

Novel insights into salinity-mediated aggregation behaviors of anammox granular sludge: Structural alterations, functional properties and metabolic responses of extracellular glycoproteins - Guangjie Huang; Yixuan Shen; Haonan Wang; Gaozhong Fan; Fang Fang; Huimin Fu; Shuai Wang (Journal of Water Process Engineering, 2026)

Chronic intermittent hypobaric hypoxia ameliorates iron metabolism disorder through ferritinophagy in collagen-induced arthritis mice - XueRui Fu; Fang Cui; RuoTong Wang; Shuang Liu; YunLu Zhao; AiJing Liu; BingYan Guo; Chen Jia; ManNa Zhang; Di Hao; Min Shi (Journal of Trace Elements in Medicine and Biology, 2026)

Geostatistical prior constrained Bayesian full-waveform inversion based on wasserstein-2 distance likelihood function - Wenze Cheng; Hanming Chen; Lingqian Wang; Yuxin Fu; Chi Fang; Hui Zhou (Journal of Applied Geophysics, 2026)

A KED-based framework for enhanced subcanopy topography retrieval leveraging TanDEM-X InSAR and spaceborne LiDAR data - Tao Zhang; Jianjun Zhu; Zhiwei Liu; Haiqiang Fu; Changcheng Wang; Zenghui Fan; Yumin Fang; Yang Liu (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

A specific strategy for accelerating strength-development rate of self-generated proppants: the gel effect related autoacceleration - Xianyan Ren; Zhenyong Li; Yating Chen; Xiaoji Fu; Yirui Zhang; Dan Fang; Xirui Chen; Cheng Bian (Fuel, 2026)

Insights into the molecular basis of umami in premium green teas via integrated metabolomics, peptidomics, and in silico molecular docking - Jiaqi Yang; Shitao Fang; Qi Zhou; Yizhi Wang; Kangni Yan; Peng Qunhua; Lin Zhi; Wu Yan; Fu Jianyu; Mu Dan; Lv Haipeng; Shi Jiang (Food Chemistry, 2026)

Green-synthesized ε-polylysine/zein nanocomplexes as safe antimicrobials: Applications and metabolomic mechanisms in grape preservation - Chunli Fang; Ruiqi Zhu; Jia Wei; Nan Wei; Ting Feng; Jun Ma; Zhinan Fu; Bin Wu; Xuhong Guo (Food Chemistry, 2026)

The heterojunction regulated by Au nanoparticles efficient removal of NO through the synergistic effects of SPR and the electron bridge - Youzhou He; Zhiqiang Guo; Yue Li; Xingyan Liu; Kaili Wu; Yuyu Fang; Rong Peng; Min Fu; Bowen Lei (Environmental Research, 2026)

A robust constrained-weight physics-informed neural network for forward and inverse analyses of mechanics - Kailin Ding; Yong Fu; Dan Fang (Computer Physics Communications, 2026)

CRISPR-Cas12a-coupled split-promoter activator bridge enables reusable one-reporter-multiple-target cell-free nucleic acid diagnostics - Fengling Fang; Mingming Zhao; Weiquan You; Xiangjun Tang; Shanjian Chen; Yao Yin; Qishui Ou; Yueguo Li; Ya Fu (Chemical Engineering Journal, 2026)

Hyperspectral phenotyping and GWAS identify novel QTLs for soybean photosynthetic rate - Li Wang; Ning Fu; Jinyu Zhang; Ao Shen; Yuanmeng Yu; Yanhong Wang; Xiaoli Guan; Dan Zhang; Fang Huang; Xiaoyong Yang; Deyue Yu; Zhongwen Huang; et al. (Theoretical and Applied Genetics, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Urinary DNA Methylation Profiling Improves Discrimination of Prostate Cancer Across PSA-Defined Risk Strata - Wei Zhu; Yi Qian; Xiaokai Zhao; Zhenxuan Fang; Zeyu Luo; Wenhua Xie; Yifang Cao; Wei Chen; Huiyu Fu; Jiayu Peng; Lijun Zhang; Jieyi Li; et al. (Biochemical Genetics, 2026)

CircGABRB2_006 Drives Malignant Progression and EMT in Papillary Thyroid Carcinoma via the miR-296-5p/FGFR1 Axis - Chuan Wan; Yanjun Guo; Han Guo; Jingjing Zhu; Fangchao Liu; Yunyuan Zhang; Bingfei Cheng; Juanjuan Li; Ying Xin; Bingzi Dong; Weiwei Fu; Dongmei Meng; et al. (Biochemical Genetics, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Activating valence oscillations in reconstructed high-entropy selenide for self-stabilized seawater oxidation through localized lattice oxygen redox - Hai Li; Xiaoliang Zhang; Yangyang Liu; Taiping Fang; Xue Zou; Gui Wang; Shun Wan; Hongliang Dong; Zihao Lu; Yufan Wu; Jinhui Fu; Luobin Cao; et al. (Science Bulletin, 2026)

Molecular mechanisms underlying the maintenance of protein homeostasis in pearl gentian grouper under acute high-temperature stress - Qiu-Ting Yang; Ren-Xie Wu; Yan-Shan Liang; Ben-Ben Miao; Su-Fang Niu; Feng-Ling Lei; Fan-Li Long; Zhen-Bang Liang; Yu-Xin Shen; Yu Fu (Journal of Thermal Biology, 2026)

Field-scale isotope tracing reveals combined organic fertilizer–antibiotic effects in amplifying antimicrobial resistance in the soil–lettuce continuum - Qingyuan Dou; Yuhao Fu; Leilei Xiang; Aoife Canavan; Jean Damascene Harindintwali; Rehan Ahmad; Mariko Fujisawa; Martin Elsner; Gerd Dercon; Xin Jiang; Fang Wang (Journal of Hazardous Materials, 2026)

Biochar-assisted copper removal and metabolic responses of Hydrocotyle vulgaris in a hydroponic system: Insights from untargeted metabolomics and computational modeling - Ziyi Lian; Xiaofan Fu; Haoran Yin; Yuxin Li; Lei Zhao; Jing Shang; Tian Gao; Bo Zhang; Chengbin Xu; Runjie Zhang; Fang Ma; Jieting Wu (Journal of Environmental Management, 2026)

Zwitterionic engineering of chitosan enables highly soluble, antibacterial films for sustainable fruit preservation - Dahai Liu; Xiaoxiao Wang; Jing Xu; Fang Yang; Riwang Li; Qiang Fu; Jie Li; Jieyan Wang; Xiu Wang; Haotian Lan; Ziyin Liu; Yafei Su; et al. (Food Research International, 2026)

Enhanced mechanical, thermal, and rheological properties of nanocellulose-reinforced multifunctional sanxan gum hydrogels - Yue Wang; Baoping Wang; Ping Cheng; Xue Zhang; Jun Han; Fang Tian; Lina Fu; Zhiping Fan (Food and Bioproducts Processing, 2026)

Outpacing self-trapping: Schottky junction–mediated hot-electron extraction for enhanced photocatalysis - Siyi Zhang; Shiwen Du; Shilong Suo; Zhenfei Fu; Ziyue Zhang; Ni Hu; Zhenhua Zhang; Zhihong Lu; Pengfei Fang (Chemical Engineering Journal, 2026)

The role of oxygen vacancies and metallic Ru in regulating oxide pathway mechanism for acidic water electrolysis - Dinghua Zhou; Yutian Ding; Tao Song; Jiayi Wu; Zengyu Su; Zhiyong Fang; Muhammad Bilal Hussain; Peili Zhang; Xian-Zhu Fu; Shao-Qing Liu; Shuwen Wu; Jing-Li Luo (Chemical Engineering Journal, 2026)

Mitochondria-targeted nanoparticles for heart failure therapy: Rational design and therapeutic mechanisms - Qiuyue Song; Kang Fang; Xinhai Cui; Wenli Xie; Jie Zhao; Xianjun Fu; Kuo Xu (Chemical Engineering Journal, 2026)

Ferroptosis mediated by aggregation of Triosephosphate isomerase 1 links cadmium exposure to pulmonary fibrosis - Yishan Yin; Xuehan Jiang; Jiayi Li; Hongxue Yang; Yi Fang; Bo Li; Hongyu Fu; Jingzeng Cai; Ziwei Zhang (Chemico-Biological Interactions, 2026)

A secreted alpha-amylase effectively induces reproductive cyst formation both within and across Colpoda species, key soil-dwelling protists - Zixin Cheng; Zhongqiao Song; Kejia Fu; Yuan Wang; Kai Chen; Jing Zhang; Che Hu; Xiaocui Chai; Shuai Luo; Fang Zhou; Yuan Xiao; Zhenfei Xing; et al. (Science China Life Sciences, 2026)

Two-Stage Automatic-Transfer Geological Mapping Method Based on Multisource Data Fusion - Yadong Xu; Congyong Tao; Yushuai Yu; Xiaoning Guo; Mengzhi Lv; Shihui Zhang; Wenqian Fang; Wenxiao Zhou; Yunhai Zhu; Lihua Fu (Mathematical Geosciences, 2026)

Effects of dietary Portulaca oleracea L. aqueous extract on growth performance, intestinal health and intestinal microflora of common carp (Cyprinus carpio) - Jing-Tong Huang; Cong-Fu Liu; Yu-Shi Cai; Li-Fang Li; Hai-Tao Zhao; Yan-Ping Yang; Rui-Fang Wang (Animal Feed Science and Technology, 2026)

Relapsing Seronegative Immune-Mediated Cerebellar Ataxia with Evolving Intrathecal Immune Activation and Rituximab Consolidation in a Toddler: A Case Report - Panhui Yu; Fang Chen; Weixiu Wang; Jingjie Li; Liyao Ma; Pengjiu Fu; Yifan Zhao; Le Wang (The Cerebellum, 2026)

Deep Learning Framework for Early Warning of Shear Failure in Jointed Rock Masses - Zhigang Yao; Yong Fang; Luo Hu; Jianfeng Wang; Kaicheng Ying; Yapeng Fu; Jian Cui (Rock Mechanics and Rock Engineering, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Longitudinal multi-omics unveils rice-fish co-culture promotes common carp health and growth via microbiome remodeling - Chang Fang; Shi-jun Chen; Ke-ni Chen; Nian-nian Zhang; Bing Fu; Shu-ping Zhang; Si-yuan Xiong; Jia-en Zhang; Hui-rong Yang (Aquaculture, 2026)

Chronic arsenic exposure promotes cell migration via KEAP1-mediated F-actin cytoskeletal rearrangement - Xin Fang; Junyi Wang; Xianhang Yin; Maojia Fu; Yuxin Hu; Huihui Wang; Jingbo Pi; Yuanyuan Xu (Toxicology and Applied Pharmacology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Thermally regulated adsorption–desorption processes at the plastic–liquid interface drive microplastics release from sealed plastic bags - Yiting Lian; Dunzhu Li; Shuiyi He; Yushu Chen; Yuhui Fu; Baofeng Zhang; Chengran Fang; Hai Xiang; Huajun Feng (Journal of Environmental Chemical Engineering, 2026)

Mask-CDKD: A source-free and label-free cross-domain knowledge distillation framework from SAM for satellite onboard VHR land-cover mapping - Daoyu Shu; Zhan Zhang; Xiao Huang; Ru Wang; Nan Jia; Xinzhe Fu; Bingnan Yang; Fang Wan; Jianzhong Lu; Jianya Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Garnet’s impact on the petrogenesis of Himalayan leucogranites - Dong-Yong Li; Fang-Zhen Teng; Yilin Xiao; Zhi-Chao Liu; Hai-Ou Gu; Wang-Ye Li; Xiao-Chi Liu; Fu-Yuan Wu (Geochimica et Cosmochimica Acta, 2026)

Insights into high-entropy alloys (FeCoNiCuZr) with ligands for selective hydrogenation of quinoline - Hongquan Fu; Yunqiao Mo; Yue Tang; Bin Wang; Hejun Gao; Fang Liao; Juan Zhang; Yunwen Liao (Chemical Engineering Journal, 2026)

Molybdenum isotopes in metamorphic and magmatic rocks may record substantial fluid activity in continental subduction zones - Wei Fang; Li-Qun Dai; Ren-Xu Chen; Zi-Fu Zhao (Chemical Geology, 2026)

Engineering Pb/PbO heterojunction with oxygen vacancies for room-temperature electrosynthesis of γ-valerolactone - Shasha Fang; Ran Hao; Wenjiong Li; Yixin Luo; Fu Li; Qingxin Guan; Jia Wang; Wei Li; Daniel C.W. Tsang (Bioresource Technology, 2026)

GABAergic Inhibition from the Nucleus Tractus Solitarius to Ventrolateral Medulla Phox2b Neurons Modulates Central Respiratory Chemoreflex and Ventilatory Homeostasis - Liuqi Shao; Yake Ji; Hongxiao Yu; Zixuan Cheng; Fanrao Kong; Xiaoyi Wang; Bingwen Zhang; Yinchang Wang; Yimeng Song; Fang Yuan; Congrui Fu; Sheng Wang (Neuroscience Bulletin, 2026)

The Impact of Digestate Nitrogen Application Rate and DOC/TN Ratio on Soil Nitrogen and its Leaching in Pepper Cultivation - Fang Liu; Jianbo Jiang; Li Yang; Tengbing He; Tianling Fu; Tao Zhang; Qingxia Zhao; Xiangying Li; Jianbo Cheng (Journal of Soil Science and Plant Nutrition, 2026)

Daphnetin prevents acute graft-versus-host disease by suppressing donor T cell expansion and function - Zhi-Feng Wei; Yan-Fang Chen; Fei Song; Yu Fu; Yun-Wei Zhang; Tian-Xue Qin; Su-Jun Gao; Long Su (Inflammopharmacology, 2026)

Genetic diversity of Haemaphysalis longicornis populations in China and their symbiotic association with Coxiella R1 strain - Weiqing Zheng; Junhua Tian; Hongxia Liu; Haijun Hu; Hongna Chen; Lihua Ma; Yinuo Yan; Jintong Fu; Jinzhi Huang; Yongwei Wen; Siyu Fang; Qianfeng Xia (Experimental and Applied Acarology, 2026)

LSTA-Swin: a long- and short-term aggregated spatio-temporal neural network for enhanced ENSO forecasting - Wei Fang; Xiao-Zhi Zhang; Yijing Li; Zhang-Jie Fu; Hai-Yan Fu (Climate Dynamics, 2026)

Contrasting responses of bacterial-mediated soil organic phosphorus transformations to varying rates of nitrogen addition in a Cunninghamia lanceolata plantation - Xiang Zhang; Qiong Zhao; Li-Man Wei; Lin-Hui Wu; Xiang-Min Fang; Yong-Hong Ma; Fu-Sheng Chen (Applied Soil Ecology, 2026)

Nighttime Atmospheric Pressure Measurement at 80–110 km Altitude over Xi’an by GBAVTII - Cun-Xia Li; Yang-He Liu; Yan Fang; Ning-Ju Hui; Yan-Long Wang; Yi-Shan Zhang; Di-Di Fu; Yuan-He Tang (Applied Geophysics, 2026)

Microsphazaphilones H–Y: new azaphilone pigments with HIV latency reversal activity from the marine-derived fungus Microsphaeropsis arundinis P1B - Qing-Ren Lu; Xian-Yuan Yang; Lei Li; Lei-Ming Wu; Lu-Xiang Wan; Yi-Fan Fu; Xian-An Chen; Xin-Xiang Xu; Tao Yuan; Xin Chen; Abrar Ahmed; Nirmal Malik; et al. (Marine Life Science & Technology, 2026)

Cuproptosis: a novel mechanism and 3PM-oriented therapeutic strategy for cancer - Ding Yang; Wei-Ting Hu; Miao Li; Fang-Qing Shen; Hao-Yu Wang; Jin-Ying Ye; Fu-Lu Ren; Yun Wang (EPMA Journal, 2026)

Neuromuscular control mechanism during posture-cognition dual task in mild cognitive impairment: a concurrent fNIRS-sEMG-COP study - Ruochen Fu; Jinjin Ma; Yao Zu; Yingying Fang; Yan Li; Arnold Y. L. Wong; Xue Cheng; Yan Leng; Jiajia Yang; Chuhuai Wang; Qiuhua Yu (GeroScience, 2026)

HGS+ enlarged vesicular compartments serve as the sites for coronavirus assembly at later infection stage - Xubing Long; Buyun Tian; Rongrong Chen; Rong Bai; Jinping Yang; Yushuang Fang; Xinyue Fu; Yanhong Xue; Wei Ji; Tao Xu; Zonghong Li (Science Bulletin, 2026)

Rhizosphere reprogramming by integrated bio‑organic fertilizer and seed coating mitigates atrazine phytotoxicity in soybeans - Xin Wen; Yuhao Fu; Leilei Xiang; Maoyuan Liao; Jean Damascene Harindintwali; Yu Wang; Chao He; Zhengyuan Gao; Jiandong Jiang; Xin Jiang; Fang Wang (Journal of Hazardous Materials, 2026)

Dual function of sulfur in Cd-As co-contaminated soils: Enhancing phytoremediation with mustard and ensuring rice safety under drought-flood rotation systems - Fei Miao; Xin Zhang; Qingling Fu; Hongqing Hu; Md․ Shoffikul Islam; Zaibin Yuan; Xiang Wang; Lin Yang; Linchuan Fang; Jun Zhu (Journal of Environmental Sciences, 2026)

An AI-driven multilayer strategy and curated dataset for mining antioxidant peptides from yak bone collagen hydrolysates - Yali Wang; Jiaqing Yang; Baishan Fang; Kangxu Wang; Yousi Fu (Food Research International, 2026)

Leaf functional traits and wood density of evergreen and deciduous tree species in a tropical karst forest - Yu-Meng Gao; Shi-Jian Yang; Jiao-Lin Zhang; Yan-Juan Jiang; Shu-Bin Zhang; Amy Ny Aina Aritsara; Guo-Hao Hu; Pei-Li Fu; Ze-Xin Fan; Kun-Fang Cao (Flora, 2026)

In situ H2O2 generation-activation via dual active sites in an electro-Fenton system for actual textile dye wastewater treatment - Yaxiong Zeng; Xiaotian Yang; Xueni Huang; Yulin Wang; Fang Cheng; Donggen Chen; Jie Yu; Luchao Wu; Fang Tao; Hailu Fu (Chemical Engineering Journal, 2026)

Ultrasound-activated in situ nano-vaccines (SATNAV) for precise CRPC sono-immunotherapy via multi-reprograming the immunosuppressive microenvironment - Xinzhi Xu; Jing Fu; Yujie Wan; Jiaqi Gong; Ruixia Hong; Jia Tang; Qizhi Wang; Ying Li; Kaifeng Huang; Yizhe Zhong; Hang Zhou; Jichun Yang; et al. (Chemical Engineering Journal, 2026)

The proteomic blueprint of human aging: a 50-year, 13-tissue atlas - Matthew X. Fang; Tian-Min Fu (Science China Life Sciences, 2026)

Open spatial relation extraction about geological objects with dependency graph network - Deping Chu; Lele Fu; Bo Wan; Fang Fang; Shunping Zhou (Earth Science Informatics, 2026)

Nitrogen inhibitors enhance ecosystem multifunctionality through microbial networks in alpine grasslands of the Tibetan Plateau - Fang-Kun Yang; Peng-Yang Wang; Ze-Yang Liu; Fu-Ying Niu; Cheng-Yi Xie; Yi-Ming Gao; Yan-Mei Ma; Yu-Xing Wang; Jia-Cheng Guo; Wen-Ying Wang (Applied Soil Ecology, 2026)

The Protective Role of Selenium Against Thyroid Injury in Pigs: Involvement of PINK1/Parkin-Mediated Mitophagy and Apoptosis Regulation - Xuehan Jiang; Yishan Yin; Yi Fang; Hongxue Yang; Hongyu Fu; Bo Li; Xiaoxiao Chen; Bendong Shi; Jingzeng Cai; Ziwei Zhang (Biological Trace Element Research, 2026)

Circular economy of Castanea henryi : high-value utilization and processing technologies advances - Zhi-hui Deng; Bin Yuan; Yuan-yuan Lu; Xiao-ming Tian; De-fang Niu; Feng Zou; Xiao-ming Fan; De-yi Yuan; Fu-liang Hu (Critical Reviews in Food Science and Nutrition, 2026)

Biocontrol efficacy and antagonistic mechanisms of Bacillus velezensis L271 against Garlic Fusarium Rot caused by Fusarium solani - Shidong He; Dongliang Fang; Jinqi Wang; Liangshuai Fu; Junjie Liu; Yanbin Sun; Jinbiao Ma; Miao Zhou; Taotao Wang; Zheng Gao; Shuxin Zhang; Xiang Li (Postharvest Biology and Technology, 2026)

Efficient probabilistic damage analysis of pile group foundations in long-span bridges subjected to ship impact - Wei Wang; Zhichen Fang; Shuai Wang; Jiahui Fu; Nailiang Xiang; Rongxin Zhou (Ocean Engineering, 2026)

The enhancing effect of interfacial polymerization on the corrosion resistance and the preparation of PVDF hollow fiber membranes - Min Fang; Wenshuai Fu; Zhenyu Li; Feng Liu; Shusu Shen; Renbi Bai; Xiaoji Zhou (Journal of Water Process Engineering, 2026)

Potential role of AHL-mediated quorum sensing in filamentous bulking induced by Sphaerotilus natans in the activated sludge process with low dissolved oxygen - Yi Fu; Wei-Xin Liu; Shao-Yang Liu; You-Peng Chen; Song-Ya Li; Fang Fang; Jin-Song Guo; Peng Yan (Journal of Environmental Chemical Engineering, 2026)

Development of a high-sensitivity dopamine sensor using copper tungstate nanoparticle-decorated carbon nanofibers on a glassy carbon electrode for analysis in various biological samples - Kiruthika Mariappan; Jing-Han Teng; Fu-Yi Chang; Shen Ming Chen; Jenn Fang Su; Ching-Lung Chen (Journal of Environmental Chemical Engineering, 2026)

Prebiotic efficacy of green banana flour against antibiotic-associated diarrhea in juvenile mice - Zhengke Fu; Xiaoxia Wang; Yang Liu; Daying Xia; Yilin Song; Fan Xv; Maoshen Chen; Fang Zhong; Fei Liu (Food Bioscience, 2026)

Corrigendum to “Bacillus coagulans controls grass carp overwintering syndrome through the intestinal microbiota-metabolite-immunity network” [Fish Shellfish Immunol. 169 (2026) 111084] - Yangyang Zhang; Zehui Su; Hucheng Jiang; Yanhua Zhao; Fu Gao; Kai Cai; Shuguang Fang; Kun Hu (Fish & Shellfish Immunology, 2026)

Oriented hetero-phase engineering modulates spontaneous polarization and band alignment - Yumin Wang; Zhenfei Fu; Zewei Zheng; Cheng Gao; Suiting Ning; Yun Tang; Wei Zeng; Pengfei Fang; Yi Xiong (Chemical Engineering Journal, 2026)

Multi-omics dissection of procyanidin C1-driven microbiota-linked EPA-enriched phosphatidylcholine signaling in multi-tissue insulin resistance - Zhihao Liu; Qihao Li; Fu Zhao; Dapeng Zhang; Xinyue Li; Daozheng Fang; Haimeng Li; Qixiang Shang; Fengyan Chen; Zhiyuan Zhen; Yong Zhu; Chang-An Geng; et al. (Chemical Engineering Journal, 2026)

ACT001 alleviates sepsis-induced acute lung injury by downregulating PANoptosis via the JAK2/STAT3 pathway - Nana Zhang; Hewei Zhang; Jialu Ping; Na Shen; Tao Fang; Qiang Fu (Inflammation Research, 2026)

From SPP to RTK: promoting the satellite navigation potential of acoustically excited antenna - Shangyang Wang; Yifan Fu; Rui Hu; Du Li; Bing Xu; Ruofan Liu; Yinuo Song; Junru Li; Bin Fang; Wenkui Lin; Zhongming Zeng; Xiangwei Zhu (GPS Solutions, 2026)

Metabolic Engineering of Selenocysteine Biosynthesis and Insertion Pathway in Lactococcus Lactis - Jing-Jing Peng; Yao Qin; Shi-Yang Yue; Ping Shi; Ling-Yu Wang; Chen-Xing Liu; Yu-Hui Fang; Xiao-Dong Pei; Fu-Tian Yu; Xin-Bi Huang; Xiao-Ling Liu; Cheng-Hua Wang (Biological Trace Element Research, 2026)

Developing a nitrogen management strategy for winter wheat to enhance economic profit and energy savings using satellite-based management zone mapping at the county scale - Jie Jiang; Zhaopeng Fu; Jiayi Zhang; Jinpeng Yang; Wanping Fang; Qiang Cao; Yongchao Tian; Yan Zhu; Weixing Cao; Xiaojun Liu (Computers and Electronics in Agriculture, 2026)

Electroporation-mediated exogenous gene delivery methodology into germ cells of the scallop, Chlamys farreri - Xiaolin Guo; Fang Liu; Yue Chen; Shukun Dai; Qing Wang; Siyu Lin; Yifan Fu; Zhifeng Zhang; Zhenkui Qin (Aquaculture, 2026)

Unraveling the distribution and stability of deep soil organic carbon after long-term conservation tillage practices - Jianye Li; Yong Zhu; Na Li; Yunying Fang; Xiaolin Dou; Yuanyuan Lu; Xingyi Zhang; Bojie Fu; Chunlong Liu; Shuguang Liu; Xinqiang Liang (Soil and Tillage Research, 2026)

Acid-triggered degradation of a silicon-based nanopesticide activates SA-dependent conifer defense against Dioryctria sylvestrella - Zheng Wang; Antong Ma; Jiaxing Fang; Xiaoqi Xu; Wei Gan; Jiayue Liu; Fu Liu; Sufang Zhang; Defu Chi; Dafeng Chen; Yapei Wang; Xiangbo Kong (Pesticide Biochemistry and Physiology, 2026)

The plant ontology of cell types - Hongyu Chen; Pu Liang; Xiaolin Lu; Shuai Jiang; Jingjing Jin; Jiaqi Cai; Yaqian Lu; Dihuai Zheng; Jie Yao; Qinjie Chu; Huixia Shou; Chengxin Fu; et al. (Molecular Plant, 2026)

Synthesis of acrylic hydrogel-granulated manganese-based ion-sieve and its adsorption performance in Baqiancuo salt-lake brine - Dawei Fang; Shilong Suo; Lijuan Liu; Donglu Fu; Zongren Song (Journal of Water Process Engineering, 2026)

The role of the nasal microbiome in linking ozone pollution to allergic rhinitis in children - Hao Tang; Shuang Du; Yongqiang Tan; Wen Su; Zhiping Niu; Jin Sun; WenPu Shao; Xinyi Fang; Zhiwei Tang; Dongjun Zhang; Zhuoru Chen; Zhenhua Zhang; et al. (Journal of Hazardous Materials, 2026)

Mechanisms of chronic infection: The multificated strategy of Cryptococcus - Sijie Qian; Danfeng Fang; Hongxin Fu; Wei Wu; Weibo Du (Fungal Biology Reviews, 2026)

Lentinan mitigates age-related sarcopenia through the promotion of mitochondrial biogenesis - Yuchuan He; Jiangbo Zhang; Xiangdong Sun; Yuchen Fang; Anni Fu; Xue Han; Juanjuan Zhang (Food Research International, 2026)

Competition release dominates growth recovery of four subtropical broadleaved tree species following an extreme snow event - Tong-Liang Xu; Rao-Qiong Yang; Zaw Zaw; Shankar Panthi; Xin-Hua Peng; Ju-Mei Zhang; Pei-Li Fu; Ke-Yan Fang; Ze-Xin Fan (Forest Ecology and Management, 2026)

Multi-omics chemical and biochemical profiling reveals ellagic acid enhances insulin sensitivity via gut microbiota–tryptophan–indole signaling mechanism - Zhihao Liu; Fu Zhao; Qihao Li; Qixiang Shang; Daozheng Fang; Xinyue Li; Haimeng Li; Quanrun He; Dapeng Zhang; Juanjuan Cheng; Yong Zhu; Zhongxia Li; et al. (Food Chemistry, 2026)

Dual MOFs-Derived CdS/In2S3 heterojunction photocatalyst for fast and efficient reduction of Cr(VI) - Hong Wu; Zhuoqi Liu; Tianrong Xiong; Xingyan Liu; Ying Chen; Min Fu; Yue Deng; Yongcheng Feng; Yuyu Fang; Bowen Lei; Youzhou He (Environmental Research, 2026)

Association between environmental noise exposure during pregnancy and the risk of preterm birth: evidence from a multi-dimensional analysis - Guangjun Zheng; Yanyan Fu; Haofeng Zhang; Fudong He; Zhenger Fang; Biying Zhou; Xiu Qin; Lei Sun; Hua Xiao; Xi Fu; Guang Hao (Environmental Research, 2026)

MOF-derived AgCl/ZnO heterojunction photocatalysts: Enhanced degradation of tetracycline via promoted charge carrier separation - Kailai Zhang; Ao Feng; Chuwen Ou; Qinwu Wu; Zhen Meng; Hang Chen; Shurui Xu; Xiaobo Fu; Wenbo Liao; Baizeng Fang; Guoyu Zhong (Environmental Research, 2026)

Prolonged low pH reprograms carbon and nitrogen metabolism and micronutrient use in Symbiodinium kawagutii and reveals indicators for reef water quality management - Fu-Fang Wen; Qing-Ling Ma; Hao-Ran Guo; Yan Huang; Da-Wei Li; Wei-Dong Yang; Hong-Ye Li; Li-Gong Zou (Environmental Research, 2026)

Breaking the vicious cycle in urethral repair: A Janus hydrogel scaffold with integrated active regulation and passive protection - Yangwang Jin; Fei Qin; Wenzhuo Fang; Meng Liu; Qiang Fu; Ming Yang; Jianguo Ma; Ranxing Yang (Chemical Engineering Journal, 2026)

Rationally designed AIEgens for amplified fluorescence in ultrasensitive gastrin-17 immunodiagnostics - Yu Fu; Jingxi Zhang; Chongquan Zhao; Kun Wen; Lun Bian; Fang Hu (Chemical Engineering Journal, 2026)

One-step therapy strategy: Multifunctional chitosan-based hydrogel enriched with platelet-rich plasma for enhanced healing of infected wounds - Han Zhang; Hang Wu; Xianchun Fu; Lun Liu; Yuan Fang; Yongtao Zhang; Tianrui Wang; Yingze Zhang; Liang Liu (Carbohydrate Polymers, 2026)

Phytochemical signaling mediates host specificity and species interactions in the Eurasian spruce bark beetle - Jiaxing Fang; Xia Shi; Huicong Du; Sufang Zhang; Fu Liu; Jiayue Liu; Dafeng Chen; Xiangbo Kong (Journal of Pest Science, 2026)

Carbon emission prediction based on spatial–temporal pattern recognition and novel integrated vine copula - A. Xu; S. Fang; J. Chen; Z. Fu; Z. Chen (International Journal of Environmental Science and Technology, 2026)

Subduction-accretion of sub-ridge mantle in the south Tibetan mélange zone - Zhen Zhang; Tong Liu; Chuan-Zhou Liu; Chang Zhang; Riccardo Tribuzio; Dong-Fang Song; Fu-Yuan Wu (Contributions to Mineralogy and Petrology, 2026)

Two new compounds from Atractylodes japonica Koidz. ex Kitam - Mei Yi; Jing Wang; Jie Sun; Yan Liu; Zhen-Xing Fang; Lei Fu; Yuan-Yuan Zhou (Natural Product Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

UCO provides greater carbon reduction potential than plant oils across diverse biodiesel production technologies - Yang Li; Fang Wang; Xiao Fu; Ye Wu (Journal of Cleaner Production, 2026)

Precise ligand defect nanoarchitectonics in integrity-preserving 2D Zn-TCPP for efficient photocatalytic H2 evolution - Xingyan Liu; Jianjun Pu; Haibo Zhou; Hongwen Zhang; Yafeng Qian; Min Fu; Yuyu Fang; Youzhou He; Siping Wei (Journal of Environmental Chemical Engineering, 2026)

Pyrolysis behaviors of lump sub-bituminous coal. Part 2: Effect of particle size - Zong-Pin Fu; Le-Le Qiu; Yi-Bin Huang; Yun-Peng Zhao; Jian Zhou; Jing Liang; Jian Xiao; Fang-Jing Liu (Fuel, 2026)

Structural characterization and prebiotic activity of oligosaccharides derived from sesame meal produced by different oil extraction methods - Hui-Fang Duan; Xiao-Rong Chen; Ran Zhang; Yuan-Qing Luo; Chang-Yong Lu; Ke-Qing Liu; Rui-Fu Cui; Run-Yang Zhang; Hua-Min Liu (Food Research International, 2026)

Bacillus coagulans controls grass carp overwintering syndrome through the intestinal microbiota-metabolite-immunity network - Yangyang Zhang; Zehui Su; Hucheng Jiang; Yanhua Zhao; Fu Gao; Kai Cai; Shuguang Fang; Kun Hu (Fish & Shellfish Immunology, 2026)

Interfacial proton transfer in MOF-functionalized aerogel enabling for selective heavy metal adsorption - Jun-Heng Fu; Baihang Cai; Yeshuang Zhong; Xinru Gong; Shuangfeng Fang; Fei Wang; Yufeng Yan; Rui Dai; Puyuan Liu; Jianye Gao; Ruihan Wang; Ying Cao; et al. (Desalination, 2026)

Mechanisms of montmorillonite-mediated high-temperature catalysis of organic matter under variable hydration states and implications for petroleum geology - Xiaoyang Zhao; Guanghui Yuan; Yingchang Cao; Fang Hao; Keyu Liu; Zihao Jin; Xiaohan Fu; Fulin Shao (Science China Earth Sciences, 2026)

Estimation of regional heterogeneity and synergistic drivers of ecological boundary transgression in the Yangtze River Economic Belt - Jianan Wang; Wei Fang; Haizhong An; Yujia Fu (Environmental Monitoring and Assessment, 2026)

Persteroid, a new steroid from the marine-derived fungus Penicillium sp. ZYX-Z-143 - Lu-Ting Dai; Li Yang; Zi-Peng Wang; Jiao-Cen Guo; Qing-Yun Ma; Qing-Yi Xie; Hao-Fu Dai; Zhi-Fang Yu; You-Xing Zhao (Natural Product Research, 2026)

Decoding the gut-microbiota-muscle nexus: Multi-omics integration reveals mTOR driven flesh modulation in rice-fish co-cultured common carp (Cyprinus carpio) - Yinglin He; Bing Fu; Chang Fang; Niannian Zhang; Mengping Zheng; Yuting Yang; Shuping Zhang; Shijun Chen; Huirong Yang (Aquaculture, 2026)

Spatial-temporal effects on cargo throughput at Chinese ports: Insights from a multiscale geographically weighted regression approach - Xialan Fang; Jian Fu; Yihua Liu; Jun Ye (Ocean & Coastal Management, 2026)

Paleoclimatic fluctuations as drivers of karst plant diversification in southern China - Ke Tan; Long-Fei Fu; Ming-Xun Ren; Xiao-Juan Li; Zi-Bing Xin; Ren-Fen Wang; Pramote Triboun; Truong Van Do; Fang Wen; Yi-Gang Wei (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The CsWRKY3–CsHB7 transcriptional cascade promotes temperature-responsive peel pigmentation via CsCCD4b-mediated β-citraurin biosynthesis in citrus - Ranran Wei; Ang Fu; Yu Fang; Quan Sun; Zhijing Mo; Pengtao Yue; Ying Liang; Zongzhou Xie; Lijun Chai; Junli Ye; Xiuxin Deng (Molecular Plant, 2026)

Mechanistic role of chloride in enhancing carbamazepine degradation by dithionite-activated sodium hypochlorite - Wei Song; Hongze Fang; Zhitao Zhang; Caixia Fu; Xing Du; Bingzhi Liu; Bin Li; Ruigang Wang; Chunyan Huang; Zhihong Wang; Zhiwei Zhao (Journal of Hazardous Materials, 2026)

Field evidence of seed coating with the degrading bacterium mitigating atrazine risks to soybeans in black soils - Xin Wen; Leilei Xiang; Yuhao Fu; Yu Wang; Jean Damascene Harindintwali; Chao He; Zhengyuan Gao; Maoyuan Liao; Jiandong Jiang; Xin Jiang; Fang Wang (Journal of Hazardous Materials, 2026)

Quercetin alleviates Deoxynivalenol-induced myocardial fibrosis in chicken by regulating MCU-mediated mitochondrial calcium overload - Hong-yu Fu; Yi Fang; Jia Chen; Hongxue Yang; Xuehan Jiang; Yishan Yin; Bo Li; Xiaoxiao Chen; Jingzeng Cai; Ziwei Zhang (Journal of Hazardous Materials, 2026)

Automatic detection of equatorial plasma bubbles using deep neural networks - Ting Zhang; Yifu Luo; Bin Zhang; Fang Jiang; Tianfang Wang; Si Xiao; Xuesong Bai; Liping Fu (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

A synergistic catalyst of Fe/ZSM-5 for robust aromatics production via methane dehydroaromatization - Xiaohui Wang; Zhilong Cheng; Bingrong Liu; Huiyi Liu; Xin Fang; Ruiqi Chai; Lishuang Ma; Yuchao Lyu; Jianye Fu; Xinmei Liu (Fuel, 2026)

Dual functionality of phosphates in a micellar casein concentrate: reconstitution enhancement while tailoring acid-induced gel structural properties - Yi-Fang Gao; Si-Yi Han; Hong-Fu Zhao; Ying-Hua Zhang (Food Research International, 2026)

Self-assembled nanoparticles from sugarcane polyphenol compounds for enhanced antioxidant activity and in vivo absorption - Zhang Tong; Fang Jia-Qin; Fu Xiong; Wang Ping-Ping; Wang Chun; Fu Yu-Xuan; Chen Chun (Food Research International, 2026)

Comparative evaluation of oxidant performance and ecological responses in PAH-contaminated soils under stoichiometric control - Zhiliang Zhao; Yu Liu; Chao He; Leilei Xiang; Yuhao Fu; Jean Damascene Harindintwali; Yongrong Bian; Xin Jiang; Fang Wang; Ravi Naidu (Chemical Engineering Journal, 2026)

Monomeric thiomolybdate ions decorated-MOFs for enhanced Hg(II) removal from water: Performance and mechanism - Chunyu Lv; Kaixing Fu; Xia Liu; Yijing Xia; Zhuoya Fang; Junfeng Zhang; Jinming Luo (Chemical Engineering Journal, 2026)

Microscopic probing into plasmodesmata (PD) and PD-derived intercellular gateways (PdIGs): Beyond morphology - Ming-fang Lv; Wei-na Shang; Yuan-xing Dai; Jun-ying Li; Yi Li; Shuai Fu; Jian Hong; Li Xie; Heng-Mu Zhang (Protoplasma, 2026)

How do moss-dominated biocrusts drive carbon sequestration under lithological constraints in karst soils? - Fang Wang; Yuanfeng Yang; Ze Li; Zhe Lin; Zhiyong Fu; Hongsong Chen; Yusong Deng (Plant and Soil, 2026)

Potential Role of Mitochondria-Associated Endoplasmic Reticulum Membranes (MAMs) Abnormalities in Epileptogenesis: Multimodal Mechanisms and Therapeutic Targets - Ruting Fu; Jiahao Liu; Liya Fang; Jin Guo (Molecular Neurobiology, 2026)

Biochar mitigates the suppressive effects of nitrogen deposition on soil methane uptake in a subtropical forest - Jiashu Zhou; Caixian Tang; Tony Vancov; Shenglei Fu; Yunying Fang; Tida Ge; Yanfei Dong; Yu Luo; Bing Yu; Yanjiang Cai; Jason C. White; Yongfu Li (Agriculture, Ecosystems & Environment, 2026)

A Study on the Pore Evolution Characteristics and Main Control Factors of the Gulong Shale Reservoirs - Junhui Li; Yangxin Su; Xiuli Fu; Daming Niu; Pingchang Sun; Shi Fang; Kunning Cui; Yue Bai; QingXia Xu (Island Arc, 2026)
Gulong shale oil in the first member of the Qingshankou Formation, Songliao Basin, has considerable exploration potential, yet the evolution of its reservoir remains poorly constrained. Clarifying this evolution is essential for evaluating reservoir properties and identifying prospective intervals. In this study, Gulong shale core samples from the first member of the Qingshankou Formation were collected from multiple wells across a maturity range from immature to highly mature. Pore evolution was investigated using N 2 adsorption, high‐pressure mercury intrusion (MICP), and argon ion beam milling scanning electron microscopy. Results reveal that porosity evolves non‐monotonically, decreasing from the immature to mature stages, increasing at the highly mature stage, and then slightly declining at the highest maturity. Concomitant with this evolution is a shift in the main control factors, with inorganic pores governing reservoir characteristics at immature–mature stages and organic pores becoming the primary control at high maturity. Overall, thermal maturation, diagenesis, and hydrocarbon generation and expulsion processes jointly govern reservoir quality, suggesting that, under favorable preservation and pressure conditions, highly mature shale may hold exploration potential.

A wheat posture monitoring and analysis system based on keypoint detection - Bing Han; Zhuangzhuang Sun; Shouyang Liu; Yuqi Cao; Jianbo He; Yifan Zhu; Hongwen Zhang; Zhengxin Fang; Xiuqing Fu (Computers and Electronics in Agriculture, 2025)

Plantation forest stand age affects the characteristics and the chlorine reactivity of soil-derived dissolved organic matter - Xin-Yi Jiao; Su-Ping Liu; Shuang Peng; Zi-Hao Wu; Fu-Qiang Fan; Le Fang; Yan-Chao Jin; Peng Liu; Cai-Shan Wang; Ding Pan; Xue-Rong Wang; Ying-Zhi Ding; et al. (Water Research, 2025)

Significant enhancement of photoproduced reactive intermediates in liquid-like region in frozen surface water for micropollutant degradation - Yu Zeng; Mingyang Zhang; Shuyao Zhou; Qinglong Fu; Fei Peng; Jinsong Liu; Yujun Wang; Dongmei Zhou; Guodong Fang (Water Research, 2025)

Large-scale analysis of SARS-CoV-2 genomic data from sewage using eVarEPS reveals that amino acid mutations detected in sewage provide an early warning on population prevalence - Ziquan Lv; Chang Shu; Yulin Fu; Yinghui Li; Shisong Fang; Xiangjie Yao; Qinglan Sun; Kesheng Peng; Jian Lu; Guomei Fan; Dongmei Liu; Jinzhen Tang; et al. (Water Research, 2025)

Recombinant GnRH6-kisspeptin-CRM197 vaccine inhibits reproductive function in male rats and dogs - Yanyun Zhu; Mengxian Li; Xiangyang Jiang; Dongyuan Fu; Zhihao Pan; Zhuoya Wu; Kejian Han; Ya Liu; Yunsheng Li; Tong Yu; Kaiyuan Ji; Mengling Peng; et al. (The Veterinary Journal, 2025)

Multi-sensor multi-dimensional data fusion method for submarine cable anchor damage event identification - Chunying Xu; Xinjie Wu; Jingqi Fang; Jianrong Chen; Keyan Xiao; Jiawang Chen; Chuliang Wei; Hailun Fu (Ocean Engineering, 2025)

Integrating lewis acid/base pairs and hydroxyfunctional groups as dual adsorption sites into porous biochar fiber for enhanced iodine capture - Hongquan Fu; Xiao Wang; Liping Li; Zhenyang Li; Jinming Chang; Fang Liao; Hejun Gao; Juan Zhang; Yunwen Liao (Journal of Water Process Engineering, 2025)

Impact of citric acid on cadmium immobilization in soil amended with biochar - Gang Wu; Md. Shoffikul Islam; Qingling Fu; Yonghong Liu; Jun Zhu; Linchuan Fang; Hongqing Hu (Journal of Environmental Sciences, 2025)

Presence of a queen (Apis mellifera) reduces the sensitivity of worker bees to environmental risks - De Fang Niu; Qiu Lan Zheng; Bin Yuan; Xiao Ling Su; Cui Ping Zhang; Yuan Yuan Lu; Ping Liu; Fu Liang Hu; Huo Qing Zheng (Journal of Asia-Pacific Entomology, 2025)

Covalent engineering of pectin-whey protein isolate conjugates enhances mucoadhesion and bioaccessibility of curcumin microparticles: Strategic impacts of crosslinking modalities - Haifeng Wang; Ting Fang; Ying Chen; Jiang Mou; Teng Li; Yuying Fu; Yun Zhai (Food Chemistry, 2025)

Bioactive pterostilbene encapsulated in zein via an in-situ co-precipitation strategy for efficient antimicrobial and fruit preservative - Chunli Fang; Zhinan Fu; Nan Wei; Jia Wei; Shuying Li; Ting Feng; Zicheng Tan; Junyou Wang; Bin Wu; Xuhong Guo (Food Hydrocolloids, 2025)

Multigraph fusion neural network for predicting available cadmium levels in farmland soils - Ren-Jie Zhang; Shu-Fang Pan; Huai-Zeng Xing; Tian-Hao Dong; Sai-Hua Liu; Tao Xue; Fa-Xiang Tian; Hong-Yu Fu; Yun-He Xie; Xiong-Hui Ji (Environmental Pollution, 2025)

Hyperspectral modeling of colored dissolved organic matter (CDOM): Insights from machine learning and band ratio models - Jinyue Chen; Chongyang Wang; Shuisen Chen; Shilong Ren; Lei Fang; Yanxia Li; Wenjun Sun; Zhenyu Gao; Zehui Wang; Rao Fu; Guoqiang Wang; Qiao Wang (Estuarine, Coastal and Shelf Science, 2025)

Ohmic contact interface engineering of fullerene-derived long-range ordered porous carbon-based anodes for durable sodium-ion capacitors - Jundong Shao; Mingming Gao; Ying Huang; Songlin Liu; Junke Li; Xiaosong Xiong; Antonio Gaetano Ricciardulli; Sheng Yang; Yubin Fu; Faxing Wang; Chun Fang; Panpan Zhang; et al. (Chemical Engineering Journal, 2025)

Nucleoside-modified mRNA-engineered myogenic-induced stem cell sheet propels urethral sphincter rejuvenation and reverses stress urinary incontinence - Meng Liu; Yuhui Wang; Ranxing Yang; Kaile Zhang; Ming Yang; Wenzhuo Fang; Yangwang Jin; Wei Fu; Ying Wang; Qiang Fu (Chemical Engineering Journal, 2025)

Strain-engineered selenium vacancies in MoSe2 cocatalysts to redirect photocarrier trapping for efficient hydrogen evolution - Siyi Zhang; Ni Hu; Zhenfei Fu; Shilong Suo; Qing Han; Ziwu Han; Ziyue Zhang; Ruiling Zhang; Bing Jin; Zhenhua Zhang; Zhihong Lu; Pengfei Fang (Chemical Engineering Journal, 2025)

DNA-assembled architectures for multi-enzyme cascades in high-performance biosensing - Yu Fu; Miao Zhang; Jiaying An; Qingxiang Zhang; Yujie Yu; Han Zhang; Yuxin Si; Di Zhang; Yuxin Fang (Chemical Engineering Journal, 2025)

Synergistic sulfite-ferrate activation for tetrachloroethylene degradation: Mechanistic insights and applicability for in-situ and ex-situ remediation - Yu Liu; Leilei Xiang; Zhiliang Zhao; Fang Wang; Ziquan Wang; Yuhao Fu; Yu Wang; Jean Damascene Harindintwali; Zhiyong Ma; Yongrong Bian; Xin Jiang; Ravi Naidu (Chemical Engineering Journal, 2025)

Cryogenic pre-activation induces structural optimization and performance boost for Li-rich Mn-based cathodes - Rui-Chi Li; Lan-Fang Que; Jun-Sen Jiang; Fu-Da Yu; Ji-Huai Wu; Xuan Wang; Can-Zhong Lu; Yi-Ming Xie (Chemical Engineering Journal, 2025)

Unveiling the dynamics of multi-scale carbon emissions in urban agglomerations: A hierarchical causal framework for China's strategic economic corridor - Jianan Wang; Wei Fang; Haizhong An; Yujia Fu (Atmospheric Pollution Research, 2025)

Assessing the potential of seedling-carried iron plaques on root to reduce As accumulation in rice: insights from the biotic/abiotic role of 'new' iron plaques formation - Xin Zhang; Hongqing Hu; Fei Miao; Mengxi Feng; Linchuan Fang; Jun Zhu; Qingling Fu (Plant and Soil, 2025)

Characterisation of cytochrome c oxidase-coding genes from mung bean and their response to cadmium stress based on genome-wide identification and transcriptome analysis - Yan Leng; Zhuan-Bin Niu; Shao-Hua Liu; Fu-Jun Qiao; Gui-Fang Liu; Bin Cheng; Shi-Weng Li (Molecular Biology Reports, 2025)

Impact of long-term use of multiple herbicides on soil microbial communities and nutrient cycling across different agricultural land-use types - Xin Wen; Yuhao Fu; Leilei Xiang; Chao He; Jean Damascene Harindintwali; Yu Wang; Siqi Wei; Yongrong Bian; Xin Jiang; Fang Wang (Agriculture, Ecosystems & Environment, 2025)

Dexmedetomidine alleviates ferroptosis caused by traumatic brain injury via the NRF2/HO-1/GPX4 pathway - Jin-Jing Hao; Xue-lian Fang; Yi-Yang Chen; Zi-jun Meng; Fu-xing Dong; Xiao-fang Yang; Zheng Chu; Jin-xia Kuai; Haijun Bao (Metabolic Brain Disease, 2025)

Improving urban butterfly diversity and abundance through strategic consideration of patch resources and butterfly ecological preference - Wenqiang Fang; Weicong Fu; Zihao Chen; Peilin Huang; Shaolin Peng; Ting Zhou (Urban Forestry & Urban Greening, 2025)

Analytical study of non-linear seepage field in underwater tunnels with different computational models and boundary conditions - Xiang Liu; Bangmeng Fu; Dongchi Wang; Annan Jiang; Qian Fang; Jianye Li (Transportation Geotechnics, 2025)

Differential diagenetic controls on petrophysical heterogeneity of lacustrine beach-bar tight sandstones: Insights from the Boxing Sag, eastern China - Cunfei Ma; Haowen Song; Yuqi Wu; Xiaopeng Cao; Haicheng Liu; Huafeng Zhang; Yong Fu; Wei Wang; Chao Huang; Xianxu Fang (Marine and Petroleum Geology, 2025)

Exogenous DBT and overexpression of deoR improved the waste tire rubber desulfurization ability of a newly isolated Escherichia sp. strain - Yao Lu; Fang-Qi Gao; Yu-Yan Wang; Ying-Wen Fu; Zhuo-Miao Li; Juan Xie; Gao-Qiang Liu; Yong-Nan Liu (Journal of Hazardous Materials, 2025)

Quality characteristics and digestive behavior of seed oils from two Huajiao (Zanthoxylum bungeanum and Zanthoxylum schinifolium) - Xiaowei Peng; Dunhe Zhang; Bofei Fu; Cuilan Fang; Aijun Li; Yalan Li; Jianquan Kan (Food Research International, 2025)

Strengthening and repair of non-uniformly corroded RC columns by ECC or CFRP jacketing: Bond performance evaluation - Deming Fang; Jin Huang; Chuanqing Fu; Zhengyu Zhu; Rusheng Qian; Xingjian Liu; Rui He (Engineering Structures, 2025)

Inhibitory effects of biological soil crusts on splash erosion across two contrasting lithologies in karst regions of Southwest China - Shiqin Zhang; Jingqin Shi; Lanhui Yang; Jingben Xu; Yongshi Tan; Yuanfeng Yang; Fang Wang; Zhiyong Fu; Hongsong Chen; Yusong Deng (CATENA, 2025)

Nearly 100% selective hydrolysis of pyrolytic sugar over sustainable carbon catalysts enables highly efficient production of bioethanol - Hong-li Ma; Ming-fu Li; Ying-chuan Zhang; Qing-hua Huang; Li-qun Jiang; Zhen Fang (Bioresource Technology, 2025)

The response of plant-derived lignin phenols accumulation to nutrient addition depends on soil depth in a subtropical plantation - Jin He; Dong Bu; Yuan-Huang Zeng; Shui-Bo Han; Wen-Qing Li; Fu-Sheng Chen; Ying-Ying Zong; Yu-Xin Huang; Yang Zhang; Xiang-Min Fang (Plant and Soil, 2025)

Unraveling histones: plant protectors under environmental stress unlocking the key to resilience - Jieting Wu; Jing Shang; Lei Zhao; Xiaofan Fu; Jin Lv; Sidi Lv; Chengbin Xv; Wenquan Jin; Junsheng Lv; Fang Ma; Haijuan Guo (Plant and Soil, 2025)

Fluorescent Probe for Recognizing Fe3+ in Aqueous Solutions and its Applications - Shengling Li; Xiangpeng Kong; Qi Wang; Jinghua Fang; Chenwei Fu; Xinxin Zhang; Jiahui Jia; Yikai Chen (Journal of Fluorescence, 2025)

Inhibition of the NLR pathway alleviates MAPK1 mutation-driven proliferation and differentiation deficits and enhanced apoptosis in P19 cells - Tingying Lei; Lei Liu; Fei Guo; Ru Li; Li Zhen; Fang Fu; Min Pan; Jin Han; Hang Zhou; Chunling Ma; Ruibin Huang; Xinyi Zhao; et al. (Tissue and Cell, 2025)

Human umbilical cord mesenchymal stem cell-derived exosomes repair raloxifene-induced damage in endometrial stromal cells via autophagy activation - Shiling Chen; Xiuying Lin; Lei Liu; Jianhua Fu; Xiaodan Lu; Chunxue Niu; Qilai Wang; HaiFeng Wei; Mengxue Wu; Munan Sun; Lixin Cao; Xuguang Mi; et al. (Reproductive Toxicology, 2025)

Land use carbon emission projections in shared socioeconomic and representative concentration pathways: Relationship with urbanization in Chinese megacities - Yu Yao; Linlin Lu; Zongtang Fu; Fang Chen; Ran Wang; Qingting Li (Land Use Policy, 2025)

Ferrate meets carbon nanotubes: Unraveling the catalytic pathways for enhanced oxidation efficiency of polycyclic aromatic hydrocarbons - Zhiliang Zhao; Leilei Xiang; Yu Liu; Jichan Qian; Yuhao Fu; Jean Damascene Harindintwali; Yongrong Bian; Cheng Fang; Xin Jiang; Fang Wang; Ravi Naidu (Journal of Hazardous Materials, 2025)

A novel approach for using cobalt and manganese components in high-cobalt slag to develop MnCo2O4 electrodes for asymmetric supercapacitors - Yukun Huang; Zeying Wang; Rifan Chen; Chenyi Cao; Yangyang Fan; Biao Fu; Weijun Peng; Yijun Cao; Yong-Zheng Fang (Journal of Environmental Chemical Engineering, 2025)

Oil-based micro-sized extraction system designed from O/W Pickering emulsion template for highly efficient nanoplastics removal in the gastrointestinal tract - Xiao Fu; Chi Zhang; Xiao Tong Lu; Fang Xiao Guo; Xu Zhang; Huixia Zhou; Xin-Ai Guo; Xiaoyu Wang; Ching Yuan Hu; Shuai Zhang; Yong Hong Meng (Food Hydrocolloids, 2025)

Engineered IGF-1-expressing adipose-derived stem cell sheet fragments promote urethral sphincter tissue regeneration - Ying Wang; Guo Gao; Meng Liu; Ming Yang; Yuhui Wang; Wenzhuo Fang; Yangwang Jin; Wei Fu; Qiang Fu (Chemical Engineering Journal, 2025)

Rare earth high-entropy layered materials as long-life and high-rate cathodes for sodium-ion batteries - Qiuwen Zhang; Xiaoguang Fu; Shengfeng Zhang; Jun Chen; Bifen Gao; Fang Fu (Chemical Engineering Journal, 2025)

Efficient catalytic decomposition of N2O over neodymium-modified Co3O4 catalysts - Dongxin Yao; Shuang Cao; Piaopiao Wei; Peng Zhang; Fang Cheng; Yaxiong Zeng; Hailu Fu; Zhongbiao Wu (Chemical Engineering Journal, 2025)

Configuration-locked near-planar D-A-D polymers for ultrahigh stability electrochromic supercapacitors - Haichang Fu; Hongtao Fang; Junze Jin; Yicai Lu; Weijun Li; Qidi Huang; Yanxian Jin; Zhangxin Chen; Dan Chen; Kai Huang (Chemical Engineering Journal, 2025)

Genetic burden and multidimensional predictors in prenatal diagnosis of fetal congenital diaphragmatic hernia - Ruibin Huang; Fang Fu; Shanshan Mei; Liyuan Liu; Wei Zhong; Jin Han; Qiuxia Yu; Hang Zhou; Chunling Ma; Li Zhen; Min Pan; Qiong Deng; et al. (Human Genetics, 2025)

Both biotic and abiotic soil N₂O productions are lower under organic N than inorganic N deposition in a Moso bamboo forest - Wenting Jiang; Yan Wang; Yongxin Lin; Hiroko Akiyama; Yunying Fang; Tony Vancov; Shenglei Fu; Hojeong Kang; Xinli Chen; Zhengqin Xiong; Zhijie Li; Shuijin Hu; et al. (Biology and Fertility of Soils, 2025)

What Controls the Distribution of Ore Veins in Quartz Vein-Type Tungsten Deposits: Constrains from Fan-Shaped Mineralization in SE China - Gui-Cong Fang; Deng-Hong Wang; Fu-Qiang Yang; Zhan-Xu Ni; Chang-Shuai Huang; Ping Wang; Meng Feng; Zuo-Hai Feng (Journal of Earth Science, 2025)

Research on shipping carbon governance considering rent-seeking behavior: an evolutionary game analysis based on prospect theory - Qing Chen; Fang Chen; Bojun Gu; Peng Tian; Yufang Fu (Frontiers in Marine Science, 2025)
Accurate carbon emission data serve as the foundation for the effective functioning of carbon markets. However, strategic collusion driven by perceived utility values among market participants can systematically erode governance efficacy. In response to the vulnerability of shipping carbon governance systems caused by rent-seeking behavior, this study develops a tripartite evolutionary game model involving shipping companies, carbon verification agencies, and governments based on prospect theory. Using system dynamics modeling and numerical simulation, we validate the equilibrium constraints and analyze the impact of basic parameters and perceived value coefficient. The results indicate that shipping carbon governance evolves dynamically in stages across its lifecycle, driven by the formation of self-sustaining in shipping companies. Moreover, stakeholder decisions predominantly determined by cost-benefit structures, wherein ESGs’ green premiums effectively drive low-carbon transition, while the anticipated rent-seeking gains incentivize such collusion. Additionally, perceived coefficients exert differentiated moderating effects. Shipping companies’ transition decisions show negative correlations with the risk attitude and loss aversion coefficients, whereas carbon verification agencies and governments demonstrate overall positive correlations with these coefficients. Consequently, we propose a systematic governance framework to provide decision support for solving the rent-seeking dilemma and promoting a carbon governance in shipping industry.

Genome-wide association and genomic selection studies on feed efficiency with fishmeal-free feed in large yellow croaker (Larimichthys crocea) - Gongsi Wang; Yingbo Yuan; Xiaotong Li; Ranxin Fu; Xingcheng Zhu; Zhenye Zhao; Yuhan Jin; Sen Zhang; Peng Ren; Lining Zhang; Qinghui Ai; Ming Fang; et al. (Aquaculture, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

Anti-inflammatory abietane-type diterpenoids from the roots of Salvia przewalskii - Yan-Fang Chen; Yu-Qing Lu; Wan-Yun Gao; Bo-Yi Fan; Fu-Cai Ren; Chuan-Pu Shen (Phytochemistry, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Comparative analysis of microplastic and microbial communities in varied aquatic environments: Disparities in occurrence, interconnections, and ecological implications - Lingfang Fu; Yongxin Guo; Jialiang Tang; Mengdi Yang; Lu Huang; Jieer Xiao; Zhongya Fan; Zhongyang Wang; Jiangyu Zhi; Zhiwei Huang; Huaiyang Fang; Ping Li (Journal of Hazardous Materials, 2025)

Characteristics and life cycle carbon emission reduction potential of waste recycling after implementing new waste classification policy in China: From case study to national perspective - Hao Fu; Le Chen; Wei Fang; Wenfang Gao; Kun Hu; Panyue Zhang; Guangming Zhang (Journal of Environmental Sciences, 2025)

Erosion mechanism of subsea tunnel considering non-linear seepage and linearly varying permeability coefficient with time - Xiang Liu; Bangmeng Fu; Kuichen Li; Annan Jiang; Qian Fang; Jianye Li (Geomechanics for Energy and the Environment, 2025)

Study on intrinsic reaction kinetics of coal char gasification based on general surface activation function model - Jiye Tao; Zezheng Shi; Yang Liu; Yongxiao Jia; Zhi Wang; Xinyu Wang; Yumin Chen; Bo Yu; Shisen Xu; Dongliang Xu; Qingyan Fang; Peifang Fu; et al. (Fuel, 2025)

Dynamic changes in metabolites during the manufacture of three distinct flavor types of Tieguanyin - Lin Zeng; Yan-Qing Fu; Jin-Long Liu; Yuan-Chao Li; Shui-lian Gao; Ying Gao; Fang Wang; Yong-Quan Xu (Food Chemistry, 2025)

A novel salient object detection network for burned area segmentation in high-resolution remote sensing images - Yuxiang Fu; Wei Fang (Environmental Modelling & Software, 2025)

Constitutive model of biotreated sand based on thermodynamic theory - Fang Liang; Yang Xiao; Zhichao Zhang; Guiyong Fu; Hao Cui (Computers and Geotechnics, 2025)

Femtosecond laser patterning with in situ sintering of porous transport layers simultaneously enhance both electron and gas-liquid transport in proton exchange membrane water electrolysis - Jian Huang; Zhen Shen; Jun Li; Fang Chen; Barbara Mecheri; Alessandra D' Epifanio; Enrico Traversa; Liang Zhang; Qian Fu; Dingding Ye; Xun Zhu; Qiang Liao (Chemical Engineering Journal, 2025)

Lanthanum-based hydrogels for simultaneous removal of trace phosphorus and algae - Yan Zhang; Qian Xie; Cheng Fu; Zhen Qiu; Zechao Zhuang; Ting Wang; Yunying Fang; Yongfu Li; Yanjiang Cai; Huajun Feng; Bing Yu (Chemical Engineering Journal, 2025)

Analgesic Effects of Acupressure on Jing-jiaji Acupoints in a Rat Model of Cervical Spondylotic Radiculopathy - Shang-Hong Jiang; Song Yang; Ling Meng; Ling-Yao Xie; Jia-Ni Yang; Si-Qi Li; Ke-Ying Liao; Zhi-Fang Qiu; Yao-Yao Xiao; Man-Di Fu; Zhi-Li Liu; Xue-Yu Jiang (Molecular Neurobiology, 2025)

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

Asymmetric C2-functionalization of indoles via visible-light-promoted three-component reaction - Han-Peng Pan; Xiao-Ying Hu; Jun-Hui Luo; Zhao-Jie Fu; Xin-Yi Yao; Meng-Yan Ran; Fang-Xin Wang; Xiang-Zhi Zhang (Molecular Diversity, 2025)

Hypoxia-preconditioned ADSC exosomes encapsulated in a multifunctional dual-network hydrogel promote the healing and functional regeneration of seawater-immersed wounds - Jie Li; Zishuo Wang; Wenjing Yang; Yongchao Zhou; Tao Fu; Yuhui Zhang; Xuzhou Duan; Dong Liu; Lingtong Kong; Yan Shang; Yuchen Zhang; Xuhui Wang; et al. (Chemical Engineering Journal, 2025)

Molybdenum isotopes record slab inputs to the mantle source of late Triassic Arc Lavas, Northeast China - Zhigang Wang; Hui-Dong Zhang; Li-Qun Dai; Zi-Fu Zhao; Wei Fang (Chemical Geology, 2025)

Nutrient enrichment weakens the positive feedback of soil organic carbon decomposition to short-term warming in subtropical forests - Ming-Hui Meng; Chao Liang; Jin He; Zi-Yi Shi; Fu-Sheng Chen; Fang-Chao Wang; Xue-Li Jiang; Xiang-Min Fang (Plant and Soil, 2025)

Combining network pharmacology and RNA sequencing to reveal the mechanism of emodin for the treatment of human neuroblastoma - Hai-mei Jiang; Shang-yi Huang; Dan Huang; Yan Zhao; Yi Yuan; Hai-fu Huang; Ying Tang; Jin-fang Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Exploring Lumbar Ligamentum Flavum, Disc Height and Foraminal Height Variations Across Different Postures: A Cadaveric Computed Tomography Investigation - Yuan-Fu Liu; Nozomu Inoue; Yu-Hua Dean Fang; Jing-Yao Wang; Alejandro A. Espinoza Orías; Chao-Jui Chang; Cheng-Li Lin (Journal of Medical and Biological Engineering, 2025)

Designing a Power Supply System for an Amphibious Robot Based on Wave Energy Generation - Lishan Ma; Fang Huang; Lingxiao Li; Qiang Fu; Chunjie Wang; Xinpeng Wang (Journal of Marine Science and Engineering, 2025)
As the range of applications for amphibious robots expands, higher demands are being placed on their working time and working range. This paper proposed a power supply system for an amphibious robot based on wave energy generation, which can convert wave energy into electric energy to enhance endurance. First, the no-load induced electromotive force, magnetic line distribution vector diagrams, and magnetic density cloud diagrams of the cylindrical and flat generators were compared by finite element simulation, which determined that the cylindrical structure has better power generation performance. Then, the electromagnetic parameters of the cylindrical generator were analyzed using Ansys Maxwell, and the final dimensions were determined. Finally, the wave motion was simulated using a swing motor, and the effects of different cutting speeds for the actuator before and after rectification, as well as series-parallel capacitance on the power generation performance of the designed generator, were experimentally analyzed. This provides a potential solution to enhance the working time and working range of amphibious robots.

Sparse spike inversion with parity decomposition and stratal dip constraints - Jian-lei Zhang; Zhi-fang Ran; Fu-min Li; Guo-fa Li (Applied Geophysics, 2025)

Petrogenesis and tectonic implication of the Neoproterozoic Shuimo alkaline-carbonatite complex from Northwestern margin of the Yangtze Block (China) - Bin Lin; Lian-Xun Wang; Yu-Fang Zhong; Xiao-Bing Qi; Xue-Wei Fu; Chang-Qian Ma (Precambrian Research, 2025)

Biological fitness of an oligophagous herbivore Chrysomela populi on two different poplars - Yujia Cheng; Ziqi Qu; Sufang Zhang; Fu Liu; Xiangbo Kong; Tingbo Jiang; Jiaxing Fang (Journal of Insect Physiology, 2025)

Association between serum elementomics of 48 elements and female fecundity: evidence from a nested case-control study in China - Tian Tian; Fang Liu; Li Li; Jing Wei; Kailibinuer Kayimu; Yu Fu; Huahua Jiang; Fei Kong; Rui Yang; Yuanyuan Wang; Xiaoyu Long; Jie Qiao (International Journal of Hygiene and Environmental Health, 2025)

Study on the influence mechanism of raw potato flour on the stability of ketchup - Boqing Fu; Jiahui Fang; Zhengbiao Gu; Yan Hong; Li Cheng; Xu Wang (Food Chemistry, 2025)

Binders with cationic semi-interpenetrating networks for sodium-ion batteries under extreme conditions - Chen-Hui Yang; Chi-Hon Leung; Lan-Fang Que; Fu-Da Yu; Can-Zhong Lu; Yi-Ming Xie (Chemical Engineering Journal, 2025)

Multi-scale characteristics and statistically associated factors of ozone pollution in Hangzhou based on machine learning - Yu-ting He; Tao Ding; Ru Yi; Yuan-yuan Wang; Yi Fu; Cheng-kai Tu; Hong-yan Fang; Jin-ye Li; Ming Zhang (Atmospheric Pollution Research, 2025)

Sonoporation-enhanced the antibacterial efficacy of aminoglycosides against Gram-negative persisters - Hongyi Chen; Jingkai Wang; Fang Han; Chen Guo; Xinmiao Fu; Zhiqiang Zhang; Yizhi Song (World Journal of Microbiology and Biotechnology, 2025)

Eutrophication‐induced dinoflagellate succession contributes to marine carbon sequestration through refractory dissolved organic matter accumulation - Fu‐Tao Fang; Zhuo‐Yi Zhu; Yuan‐Bi Yi; Ding He; Hong‐Yan Bao; En‐Ren Zhang; Cheng‐Xu Zhou (Limnology and Oceanography, 2025)
The increasing eutrophication of coastal seas is causing a shift in the most important phytoplankton groups from diatoms to dinoflagellates, but its feedback to marine carbon cycling remains unclear. Here, we investigated the potential of the key coastal phytoplankton, the diatom Skeletonema costatum , and the dinoflagellate Prorocentrum donghaiense , for refractory dissolved organic carbon (DOC) accumulation over dark degradation incubations of 70 d. Our multi‐method approach showed that dinoflagellate detritus, rather than diatom detritus, significantly contributes to refractory DOC. This is evidenced by the fact that the detritus of dinoflagellates compared to that of diatoms (1) has a weaker transmittance in infrared spectrometry, indicating a lower content of labile organic substances (alcohol and amide groups); (2) has a higher release and/or transformation efficiency of particulate organic carbon to DOC (81% vs. 50%); (3) has a lower content of labile fraction, amino acid (8% vs. 17% carbon) and exhibits lower degradability of the DOC formed (23% vs. 30%); (4) has a lower content of labile compounds determined by Fourier transform ion cyclotron resonance mass spectrometry (maximum molecular lability boundary: 21% vs. 31%); and (5) has a higher proportion of refractory carboxylic‐rich alicyclic molecules (57% ± 0.5% vs. 51% ± 0.7%) over incubations. Our results emphasize that eutrophication‐triggered coastal dinoflagellate succession has a significant potential for positive feedback to carbon sequestration through the formation of refractory DOC.

Anthropogenic nitrogen inputs favour increased nitrogen and organic carbon levels in Qinghai–Tibetan Plateau lakes: Evidence from sedimentary records - Ping Zhang; Xiangzhong Li; Fu-Jun Yue; Yuyan Zhang; Yuan Wang; Deyan Wu; Dongkun Liu; Fang Li; Xin Wang; Xuefang Ji (Water Research, 2025)

Insight into homogeneous activation of sodium hypochlorite by dithionite coupled with dissolved oxygen (DO@NaClO/DTN) for carbamazepine degradation - Wei Song; Hongze Fang; Zhaosheng Lei; Ruigang Wang; Caixia Fu; Fei Wang; Yuning Fang; Xing Du; Zhihong Wang; Zhiwei Zhao (Water Research, 2025)

Coxiella R1 symbiont regulates the Asian long-horned tick on its reproduction and development - Weiqing Zheng; Jintong Fu; Jingzhi Huang; Yongwei Wen; Siyu Fang; Xiaoyan Yang; Qianfeng Xia (Veterinary Parasitology, 2025)

Air pollution of PM2.5-bound PAHs in urban Chongqing, China from 2015 to 2022: Concentration, source tracking and health risk - Bofei Fu; Shang Li; Shushu Lan; Xiaowei Peng; Chongjun Ran; Nanyan Li; Hong Li; Lun Xiao; Guohua Zhao; Junrui Chang; Jingxiu Han; Yunyun Wu; et al. (Urban Climate, 2025)

How does built environment influence outdoor jogging activities in high-density cities? New insights using machine learning from 2D/3D perspectives - Qikang Zhong; Congying Fang; Hongpeng Fu (Sustainable Cities and Society, 2025)

Synergistic bimolecular erosion-healing interfacial passivation for wide-bandgap perovskite and tandem solar cells - Shiqiang Fu; Guang Li; Shun Zhou; Jiahao Wang; Dexin Pu; Lishuai Huang; Zhiqiu Yu; Wanping Chen; Guojia Fang; Weijun Ke (Science Bulletin, 2025)

Roles of different valence manganese oxides and hydroxyl radicals in controlling cadmium and arsenic mobilization in paddy soil - Xuewei WANG; Qingling FU; Jun ZHU; Linchuan FANG; Hongqing HU (Pedosphere, 2025)

Highly efficient photocatalytic removal of NO and synchronous inhibition of NO2 via heterojunction formed by ZnAl-LDH and MXene-Ti3C2-derived TiO2@C - Kaili Wu; Yacen Tang; Yirui Qiu; Haibo Zhou; Xingyan Liu; Panyin Wang; Youzhou He; Shimeng Pan; Yuyu Fang; Min Fu; Siping Wei; Fan Dong (Journal of Hazardous Materials, 2025)

Controlled growth of villiform MnO2 over CeO2 nanorods for the efficient catalytic oxidation of formaldehyde - Suhong Lu; Nadi He; Chengyu Xu; Nan Sun; Yuheng Jiang; Hao Fu; Haomeng Wang; Jurong Liu; Yuzhen Fang; Guilong Liu (Journal of Environmental Chemical Engineering, 2025)

How to balance cadmium immobilization and greenhouse gas emissions when using microbial induced-calcite precipitation (MICP): Regulate the N/Ca molar ratio and dosage - Min Liu; Hongqing Hu; Md. Shoffikul Islam; Xiongfei Rao; Jun Zhu; Linchuan Fang; Qingling Fu (Journal of Environmental Chemical Engineering, 2025)

Saliency supervised masked autoencoder pretrained salient location mining network for remote sensing image salient object detection - Yuxiang Fu; Wei Fang; Victor S. Sheng (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Experimental and modeling of water evaporation and condensation during self-heating in biomass storage piles - Xinke Chen; Lun Ma; Qingyan Fang; Fu Zhou; Qilei Ma; Cheng Zhang; Gang Chen; Chungen Yin (Fuel, 2025)

Green construction and digestive properties of Fe (II) and quercetin double-loaded delivery system by wampee polysaccharide and its application - Juan-li Fang; Fu-lan Hu; Ya-qin Wu; Tao Liu; Peng-peng Sun; Yuan-yuan Ren (Food Chemistry, 2025)

Lightweight deep learning model for embedded systems efficiently predicts oil and protein content in rapeseed - Mengshuai Guo; Huifang Ma; Xin Lv; Dan Wang; Li Fu; Ping He; Desheng Mei; Hong Chen; Fang Wei (Food Chemistry, 2025)

Development of aroma attributes and volatile components during liquid-state fermentation of instant dark tea by Aspergillus niger - Haoran Sun; Yaling Cao; Rui Fang; Jia Li; Shanshan Shen; Shengshuo Zhang; Ranqin Fan; Jialin Fu; Feng Zou; Pengxiang Yue; Yu Wang; Xueling Gao (Food Bioscience, 2025)

Occurrence, release and risk assessment of metal elements in polylactic acid food containers from China - Zhouyue Cai; Yuanyuan Zhu; Xuheng Fu; Huimin Zhang; Yamin Fang; Song Yu (Food Packaging and Shelf Life, 2025)

Atomic-level defect engineering enables hollow ternary molybdenum phosphoselenide nanospheres for enhanced sodium-ion storage - Yao Guo; Yangjie Liu; Lihong Xu; Mujtaba Aminu Muhammad; Huiling Fang; Jiaqi Yu; Mengyao Tu; Xiang Hu; Chuan-Fu Sun; Zhenhai Wen (Chemical Engineering Journal, 2025)

Wide-bandgap perovskite solar cells with > 1.34 V Voc for all-perovskite tandems - Yunfei Li; Nannan Sun; Bo Feng; Wen Li; Zhengbo Cui; Wenxiao Zhang; Sheng Fu; Xiaodong Li; Junfeng Fang (Chemical Engineering Journal, 2025)

Deciphering the effective substances of mangrove plant Acanthus ilicifolius Linn. against liver injury - Qing Zhao; Shu-Yue Song; Han Fang; Yao-Yao Zheng; Meng-Qi Zhang; Xia Ren; Ya-Hui Zhang; Xiu-Mei Fu; Xin Li; Chang-Yun Wang (Natural Product Research, 2025)

Selective gold extraction from e-waste leachate via sulfur-redox mechanisms using sulfhydryl-functionalized MOFs - Jialong Qin; Hengzhi Liu; Zhuoya Fang; Junjun Pei; Kai Yin; Kaixing Fu; Jinming Luo (Water Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Neolithic human adaptations to the environmental changes in the Jianghan Plain, middle Yangtze Valley - Yuenan Li; Yansheng Gu; Mingjuan Jiang; Shaofan Fang; Zhongbiao Fu; Shuo Guan; Ruonan Liu; Zongmin Zhu; Hongye Liu (Quaternary Science Reviews, 2025)

Impact of particle-attached microbial denitrification on N2O production in an agricultural-urban watershed - Mengdi Yang; Hanjie Yang; Wencai Wang; Huaiyang Fang; Lu Huang; Dan Li; Lingfang Fu; Shiyuan Ding; Xiao-Dong Li; Cong-Qiang Liu; Gangjian Wei; Dongli Li; et al. (Journal of Environmental Management, 2025)

A critical review of human internal exposure to short-chain chlorinated paraffins and its concerning health risks - Ke Fang; Yi-bin Sun; Run-ming He; Jian-kun Qian; Wen Gu; Yi-fu Lu; Zhao-min Dong; Yi Wan; Chao Wang; Song Tang (Environmental Research, 2025)

Chlorpyrifos-oxon results in autophagic flux dysfunction contributing to neuronal apoptosis via a ROS/AMPK/CHOP activation pathway - Jui-Ming Liu; Kuan-I Lee; Chin-Chuan Su; Kai-Min Fang; Shing-Hwa Liu; Shih-Chang Fu; Chun-Ying Kuo; Kai-Chih Chang; Jun-An Ke; Ya-Wen Chen; Ching-Yao Yang; Chun-Fa Huang (Chemico-Biological Interactions, 2025)

Advances and applications in single-cell and spatial genomics - Jingjing Wang; Fang Ye; Haoxi Chai; Yujia Jiang; Teng Wang; Xia Ran; Qimin Xia; Ziye Xu; Yuting Fu; Guodong Zhang; Hanyu Wu; Guoji Guo; et al. (Science China Life Sciences, 2025)

Growth Onset Rather Than Photosynthesis Strongly Regulates Autumn Senescence Termination Besides Climate Change - Shuping Ji; Shilong Ren; Yann Vitasse; Constantin M. Zohner; Yongshuo H. Fu; Xiaoqiu Chen; Xiaoyang Zhang; Charlotte Grossiord; Huiying Liu; Matthias Peichl; Dailiang Peng; Shuai An; et al. (Global Ecology and Biogeography, 2025)
Aim Plant senescence largely influences the global carbon cycle by regulating the growing season length. However, the driving mechanisms of plant senescence remain unclear, particularly the role of developmental factors. This study aims to investigate how environmental and developmental factors drive autumn senescence and evaluate whether woody and herbaceous plants exhibit divergent responses to these drivers. Location Eurasia. Time Period 1982–2014. Major Taxa Studied Woody and herbaceous species. Methods Using 120,833 long‐term ground phenological observations, we employed partial correlation analysis to investigate the influence of environmental and developmental factors on senescence termination. Experimental records from literature and pasture survey observations from China were separately utilised to further validate the influence of developmental factors on senescence termination. Structural equation modelling was applied to analyse the pathways of growth onset affecting senescence termination. Additionally, multiple linear regression was used to examine the tendency of the sensitivity of senescence termination to plant development rate. Results We find that earlier growth onset primarily leads to earlier senescence termination directly in herbaceous plants, but indirectly in woody plants by accelerating early‐season development. The sensitivity of senescence termination to plant development rate shows a declining trend, particularly in early‐season negative effects on woody plants and late‐season positive effects on herbaceous plants, suggesting diminished impacts of future warming on senescence timing. The impact of growing season photosynthetic activity on senescence termination is not pronounced for both woody and herbaceous plants. Main Conclusions The results demonstrate that growth onset may affect woody and herbaceous senescence termination through different pathways, whereas the carry‐over effects of growing season photosynthetic activity are not widely discovered. This emphasises that the introduction of developmental factors into phenological models needs to be considered carefully according to plant type.

Damage analyses of the main pylon of a suspension bridge under ship impact using fiber beam elements - Wei Wang; Zhichen Fang; Jiahui Fu; Shuai Wang; Rongxin Zhou (Ocean Engineering, 2025)

Machine learning prediction for the removal of As and Cd from co-contaminated water by iron-modified biochar from As-enriched P. vittata - Mengxi Feng; Xin Zhang; Hongqing Hu; Fei Miao; Jun Zhu; Linchuan Fang; Qingling Fu (Journal of Water Process Engineering, 2025)

The cation/H+ exchanger OsCAX2 is involved in cadmium uptake and contributes to differential grain cadmium accumulation between Indica and Japonica rice - Xiang-Qian Liu; Huan Liu; Meng-Jie Fu; Li-Wen Zhang; Si-Fan Yin; Zhong Tang; Fang-Jie Zhao; Xin-Yuan Huang (Journal of Hazardous Materials, 2025)

Optimizing the thiosulfate-mediated zerovalent iron/persulfate activation systems: Trade-off between Fe(III)/Fe(II) cycling and quenching effects in environmental remediation - Maolin Wang; Mi Deng; Gang Zhao; Yanchun Fan; Tianwen Liu; Ying Huang; Lan Peng; Haoyang Fu; Shengqiong Fang (Journal of Environmental Management, 2025)

Solvent extraction of lithium from aqueous solution using all ionic liquid system - Donglu Fu; Zongren Song; Jiankang Liu; Shilong Suo; Jie Wei; Dawei Fang (Journal of Environmental Chemical Engineering, 2025)

Experimental study of a multi-combination passive-ammonia selective catalytic reduction (pSCR) systems using monolithic catalysts - Jiale Fu; Zhiyuan Hu; Liang Fang; Jiayi Shen; Yunhua Zhang; Diming Lou; Piqiang Tan (Journal of Environmental Chemical Engineering, 2025)

Research on the short-process of leaching and semi-extraction method of nickel‑cobalt from mixed hydroxide precipitate (MHP) to prepare battery grade products - Yukun Shen; Hongyu Wang; Liang Zhang; Liyong Zhou; Chunping Fu; Kweon Ho Jin; Mingkang Fang; Jiade Wang (Hydrometallurgy, 2025)

Achieving excellent thermoelectric properties in CaTiO3-based materials via entropy engineering and recrystallization - Bingbing Fang; Jianbo Li; Ying Fu; Jinghan Zhao; Manliu Du; Huijun Kang; Jun Wang (Chemical Engineering Journal, 2025)

Bioaccumulation of Polyhalogenated Carbazoles and Its Related Compounds from Soil to Plant: Impact Factors and Uptake Pathways - Yun Ma; Hailin Shi; Yaqi Fang; Xinyue Jia; Jie Fu; Shanshan Zhou; Jianjie Fu (Water, Air, & Soil Pollution, 2025)

Organic Matter Occurrence and Its Effects on Pore Structure and Methane Adsorption Capacity: A Case Study of the Niutitang Black Shale in Guizhou, China - Peng Xia; Fang Hao; Jinqiang Tian; Yong Fu; Yuliang Mou; Chuan Guo; Zhen Yang; Ke Wang (Journal of Earth Science, 2025)

Study on the policy diffusivity of China’s marine strategic science and technology power building based on LDA modelling - Yufang Fu; Hui Xu; Yi Wang; Fang Chen; Bojun Gu (Frontiers in Marine Science, 2025)
The world's maritime countries are competing for the strength of marine science and technology. Throughout the world, the systematic construction of marine strategic scientific and technological strength has become a decisive factor in marine scientific and technological competition, and it is an inevitable choice for China to cope with marine scientific and technological competition. As far as science and technology policy is concerned, the efficiency of policy supply directly affects the effect of science and technology implementation. Therefore, it is urgent to clarify the mechanism of policy diffusion that influences the development of marine strategic scientific and technological forces. This paper employs a case study approach to examine the diffusion characteristics of China's marine science and technology policies. The analysis is based on the marine science and technology policies issued by the Chinese government at the central, provincial and municipal levels since 2002. The study employs an LDA model and text-mining techniques in the R language to construct a comprehensive understanding of the diffusion process. The study reveals that China's marine science and technology development policies exhibit a top-down diffusion trend. Furthermore, the implementation intensity and responsiveness of lower-level governments to higher-level policies are increasing. The diffusion of policy themes displays clear temporal characteristics, with policies undergoing continual refinement in the context of top-down content diffusion. However, there is less interaction between bottom-up policies. In this regard, we should improve the overall effectiveness of the marine strategic scientific and technological strength policy system, optimize the policy diffusion mechanism of marine strategic scientific and technological strength, and strengthen the construction of a public participation consultation system to strengthen the overall play of China's marine strategic scientific and technological strength.

Evaluation of tomato seed full-time sequence germination vigor based on improved YOLOv8s - Luxu Tian; Zhengxin Fang; Haoyu Jiang; Shouyang Liu; Hongwen Zhang; Xiuqing Fu (Computers and Electronics in Agriculture, 2025)

Enhanced selective removal of PFAS at trace level using quaternized cellulose-functionalized polymer resin: Performance and mechanism - Jinjing Huang; Kaixing Fu; Zhuoya Fang; Jinming Luo (Water Research, 2025)

Optimization-based global liquefied natural gas shipping network management for emission reduction - Hongchu Yu; Weihuang Wu; Xuequan Zhang; Zhixiang Fang; Xiuju Fu; Lei Xu; Jingxian Liu (Ocean Engineering, 2025)

Irradiation and DOM mediate lead release from polyvinyl chloride microplastics in natural surface water - Mingyang Zhang; Yu Zeng; Qinglong Fu; Peixin Cui; Ning Chen; Yujun Wang; Dongmei Zhou; Guodong Fang (Journal of Hazardous Materials, 2025)

Unravelling the complex influence of dissolved organic matter on microbial diversity in a salinized lake - Weiying Feng; Xuezheng Yu; Jiayue Gao; Jin Hur; Fang Yang; Zhuangzhuang Feng; Haiqing Liao; José Manuel Gonçalves; Isabel Maria Duarte; Pingqing Fu (Environmental Research, 2025)

The effect of soil depth on stoichiometry was greater than that of elevation in Abies georgei var. Smithii forest in Southeastern Tibet, China - Si-jie Zhu; Jiang-rong Li; Bo Zhang; Fang-wei Fu; Liang-na Guo (Acta Oecologica, 2025)

Corrigendum to “Intestinal flora analysis and serum metabolomics reveal the effectiveness of Bacillus coagulans BC66 in treating bacterial enteritis in bullfrogs” [Aquaculture Volume 594, 15 January 2025, 741341] - Zehui Su; Fu Gao; Rui Shu; Kai Cai; Shuguang Fang; Xiaoting Lei; Dan Li; Kun Hu (Aquaculture, 2025)

Latest research progress on anti-microbial effects, mechanisms of action, and product developments of dietary flavonoids: A systematic literature review - Jincan Luo; Jinhai Luo; Zhili Sheng; Zhonghao Fang; Yu Fu; Nannan Wang; Bao Yang; Baojun Xu (Trends in Food Science & Technology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

A new diterpenoid alkaloid from the Aconitum scaposum - Cheng-En Fu; Gui-Fang Li; Guo-Qing Sun; Shuai Huang; Lin Chen; Xian-Li Zhou (Phytochemistry Letters, 2025)

Antimicrobial perylenequinones isolated from the endophytic fungus Alternaria alstroemeriae - Yong-Fu Li; Fang Yue; Xu-Ri Wan; Chang Li; Yi Sun; Yue-Hu Pei (Phytochemistry Letters, 2025)

Corrigendum to “Long-term warming and acidification interaction drives plastic acclimation in the diatom Pseudo-nitzschia multiseries” [Mar. Environ. Res. 204 (2025) 106901] - Yanmin Sun; Fan Yang; Ran Duan; Dong Xu; Yanan Zhang; Chengwei Liang; Zhuonan Wang; Xintong Huang; Bingkun Wang; Yapeng Wang; Haoming Sun; Naihao Ye; et al. (Marine Environmental Research, 2025)

Long-term warming and acidification interaction drives plastic acclimation in the diatom Pseudo-nitzschia multiseries - Yanmin Sun; Fan Yang; Ran Duan; Dong Xu; Yanan Zhang; Chengwei Liang; Zhuonan Wang; Xintong Huang; Bingkun Wang; Yapeng Wang; Haoming Sun; Naihao Ye; et al. (Marine Environmental Research, 2025)

Mechanistic impact of Gracilaria bailinae extracts on photosynthesis and metabolism in Phaeodactylum tricornutum - Li-Gong Zou; Fu-Fang Wen; Xiao Zhang; Gang Li; Qing Wang; Hong-Ye Li; Yu-Feng Yang (Marine Environmental Research, 2025)

On using an aerosol thermodynamic model to calculate aerosol acidity of coarse particles - Zhengyang Fang; Shuwei Dong; Chengpeng Huang; Shiguo Jia; Fu Wang; Haoming Liu; He Meng; Lan Luo; Yizhu Chen; Huanhuan Zhang; Rui Li; Yujiao Zhu; et al. (Journal of Environmental Sciences, 2025)

“Nanoregion” effect of ionic liquid mixture system for preparing highly active porous electrocatalytic hydrogen production materials - Donglu Fu; Zongren Song; Xiaoxue Ma; Boyu Liu; Shilong Suo; Shiju Yu; Minghua Jing; Dawei Fang (Fuel, 2025)

A simple and colorimetric method utilizing cell-free toehold switch sensors for the detection of Chlamydia trachomatis, Ureaplasma urealyticum and Neisseria gonorrhoeae - Fengling Fang; Hongyan Guo; Zhaopei Guo; Lin Lin; Lu Lai; Yue Shi; Weiquan You; Shanjian Chen; Can Liu; Mingming Zhao; Shaobin Guo; Qishui Ou; et al. (Analytica Chimica Acta, 2025)

Corrigendum to “Intestinal flora analysis and serum metabolomics reveal the effectiveness of Bacillus coagulans BC66 in treating bacterial enteritis in bullfrogs” [Aquaculture Volume 594, 15 January 2025, 741341] - Zehui Su; Fu Gao; Rui Shu; Kai Cai; Shuguang Fang; Xiaoting Lei; Dan Li; Kun Hu (Aquaculture, 2025)

Intestinal flora analysis and serum metabolomics reveal the effectiveness of Bacillus coagulans BC66 in treating bacterial enteritis in bullfrogs - Zehui Su; Fu Gao; Rui Shu; Kai Cai; Shuguang Fang; Xiaoting Lei; Dan Li; Kun Hu (Aquaculture, 2025)

Tetrabromobisphenol A induced p38-MAPK/AMPKα activation downstream-triggered CHOP signal contributing to neuronal apoptosis and death - Jui-Ming Liu; Shing-Hwa Liu; Shih-Chang Fu; Wei-Cheng Lai; Kai-Min Fang; Ken-An Lin; Jun-An Ke; Chun-Ying Kuo; Chin-Chuan Su; Ya-Wen Chen (Toxicology, 2025)

Screening and isolation of polyethylene microplastic degrading bacteria from mangrove sediments in southern China - Yinglin He; Chang Fang; Zeqian Zeng; Bing Fu; Ziyi Cui; Jun Wang; Huirong Yang (Science of The Total Environment, 2025)

Exploring the spatial heterogeneity of soil organic carbon and the influence of coastal factors: A case study in the Yellow River Delta, China - Youxiao Wang; Yingjun Sun; Qi Wang; Pingjie Fu; Yaohui Liu; Fang Wang; Fei Meng (Science of The Total Environment, 2025)

Mutation of rice SM1 enhances solid leaf midrib formation and increases methane emissions - Hongrui Jiang; Weimin Cheng; Chunpeng Chen; Cheng Fang; Yue Zhan; Liangzhi Tao; Yang Yang; Xianzhong Huang; Kun Wu; Xiangdong Fu; Yuejin Wu; Binmei Liu; et al. (Plant Science, 2025)

Valorization of corn stalk hydrochar by similar steam explosion during hydrothermal carbonization: Structure evolution and pyrolysis behavior - Zhenfei Liu; Fang Wang; Hongyue Fu; Yuwan Sheng; Xiuli Shen; Weiming Yi; Deli Zhang (Journal of Cleaner Production, 2025)

Dissolved oxygen activated by single-atom-state iron coupled with sodium dithionite for norfloxacin degradation: Efficiency and mechanism - Wei Song; Sen Xu; Caixia Fu; Ruiyi Huang; Hongze Fang; Li Li; Dachao Lin; Yuning Fang; Xing Du; Zhihong Wang (Journal of Cleaner Production, 2025)

Can biodegradable film replace polyethylene film to obtain similar mulching effects on soil functions and maize productivity in irrigation region? A three-year experimental appraisal - Xiao-Bin Xiong; Peng-Yang Wang; Ze-Ying Zhao; Jing Wang; Shu-Tong Liu; Fu-Jian Mei; Wen-Ying Wang; Yi-Bo Wang; Xiang-Wen Fang; Ying Zhu; Jin-Lin Zhang; Ning Wang; et al. (Journal of Cleaner Production, 2025)

Enhancing rainwater harvesting efficiency in karst terrains: The role of road intercepted soil-epikarst lateral flow - Zhiyong Fu; Peining Liang; Hamid M. Behzad; Rongjie Fang; Sheng Wang; Jie Zhao; Hongsong Chen (Journal of Environmental Management, 2025)

Low-temperature glucose foaming to construct three-dimensionally porous bulk CoMo catalyst for thiophene hydrodesulfurization - Yeqiang Du; Longzhou Ren; Wenjing Song; Ziqi Wan; Qinqin Zhang; Liancheng Bing; Fang Wang; Guangjian Wang; Haitao Fu; Dezhi Han (Fuel, 2025)

Comprehensive physicochemical indicators analysis and quality evaluation model construction for the post-harvest ripening rapeseeds - Qiuhui Xu; Jie Wang; Dan Wang; Xin Lv; Li Fu; Ping He; Desheng Mei; Hong Chen; Fang Wei (Food Chemistry, 2025)

Multifunctional role of surfactant in fabricating polyamide nanofiltration membranes for Li+/Mg2+ separation - Shang Fang; Kecheng Guan; Aiwen Zhang; Liheng Dai; Siyu Zhou; Wenming Fu; Mengyang Hu; Ping Xu; Pengfei Zhang; Zhan Li; Zhaohuan Mai; Hideto Matsuyama (Desalination, 2025)

Observing the evolution of 1D nanostructures in liquids: Advances and application - Junyu Zhang; Fang Fu; Liangping Xiao; Mi Lu (Chemical Engineering Journal, 2025)

Visible-light excitable polymers with ultra-long phosphorescence afterglow achieved by boron-based dative bonds - Wei-Guang Chen; Yan-Fang Zhuang; Yan Wang; Zhi-Jian Chen; Yi-Fan Lv; Fu Song; Yu Chen (Chemical Engineering Journal, 2025)

Separation of the ionospheric and thermospheric contributions in the data from the Triple Ionosophere PhotoMeter onboard the Feng-Yun 3E satellite - Fang Jiang; Tian Mao; Jin-Song Wang; Xiu-Qing Hu; Xiao-Xin Zhang; Liping Fu; Nan Jia; Tianfang Wang (Science China Earth Sciences, 2025)

Intermittent fasting shifts the diurnal transcriptome atlas of transcription factors - Min Fu; Siyu Lu; Lijun Gong; Yiming Zhou; Fang Wei; Zhigui Duan; Rong Xiang; Frank J. Gonzalez; Guolin Li (Molecular and Cellular Biochemistry, 2025)

CircHAT1 regulates the proliferation and phenotype switch of vascular smooth muscle cells in lower extremity arteriosclerosis obliterans through targeting SFRS1 - Xian-ying Huang; Fang-yong Fu; Kai Qian; Qiao-li Feng; Sai Cao; Wei-yu Wu; Yuan-lin Luo; Wei-jie Chen; Zhi Zhang; Shui-chuan Huang (Molecular and Cellular Biochemistry, 2025)

CARD9 regulates myocardial inflammation, oxidative stress, and vascular dysfunction in hypertensive rats by activating MAPK/p38 pathway in combination with NOD2 - XiangBin Xin; Jing Zhang; YanQin Du; XiaoTing Jang; XinYi Tian; Fu Ma; Fang Chen (Molecular & Cellular Toxicology, 2025)

Comparison of molecular testing methods for diagnosing non-tuberculous mycobacterial infections - Leilei Wang; Yu Chen; Qingqing Wang; Jue Pan; Rong Bao; Wenting Jin; Yumeng Yao; Tingting Fang; Na Li; Sichun Luan; Xiaoyu Yin; Le Qin; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

A domain-decomposition-based parallel approach for 3D geological modeling using radial basis functions interpolation on GPUs - Hong Li; Huizhu Ni; Jinming Fu; Bo Wan; Deping Chu; Fang Fang; Run Wang; Guoxi Ma; Xin Zhou (Earth Science Informatics, 2025)

Multi-step gene set analysis identified HTR3 family genes involving childhood acute lymphoblastic leukemia susceptibility - Xiao Liu; Honghao Guo; Meiyun Kang; Wenfeng Fu; Huiqin Li; Hongsheng Ji; Jiou Zhao; Yongjun Fang; Mulong Du; Yao Xue (Archives of Toxicology, 2025)

Autonomous net inspection and cleaning in sea-based fish farms: A review - Jiaying Fu; Da Liu; Yingchao He; Fang Cheng (Computers and Electronics in Agriculture, 2024)

Impact of urban landscape patterns on butterfly diversity in Fuzhou City parks - Ying Lin; Shanjun Huang; Wenqiang Fang; Yaling Huang; Chenfei Gao; Yankai Huang; Ruoxian Zheng; Weicong Fu (Science of The Total Environment, 2024)

Sequential oxidation procedures with KMnO4: Component characteristics of labile reducing capacity fractions in anaerobic sediments - Xuemei Chen; Zhijun Li; Songjie Fu; Lanwei Liang; Xiaohan Liu; Fang Hu; Wen Zhang; Yonghong Bi; Yang Jiao; Sen Gu; Qingman Li (Science of The Total Environment, 2024)

Investigating the effects of COVID-19 on sperm in male smokers: A prospective integrated proteomic and metabolomic study - ChengLu Wang; JiaCheng Zhang; Fang Gao; Min Zheng; XiaoHua Fu; KeBing Yang (Reproductive Toxicology, 2024)

Facet-induced fractionation of humic acid by hematite and the promoted-photodegradation of 17β-estradiol catalyzed by hematite-humic complex - Ziyan Zhou; Hao Wu; Boming Fu; Dingding Wu; Xinhao Wang; Davide. Vione; Xin Jin; Yanfen Fang; Cheng Gu (Journal of Hazardous Materials, 2024)

Mitigating risks from atrazine drift to soybeans through foliar pre-spraying with a degrading bacterium - Xin Wen; Leilei Xiang; Jean Damascene Harindintwali; Yu Wang; Chao He; Yuhao Fu; Siqi Wei; Syed A. Hashsham; Jiandong Jiang; Xin Jiang; Fang Wang (Journal of Hazardous Materials, 2024)

Detecting and attributing the impact of human activities on grassland aboveground biomass in China's Loess Plateau - Jian-Zhou Wei; Jiu-Ying Pei; Chao Fang; Jordi Sardans; Josep Peñuelas; Fu-Qiang Huang; Xu-Long Zhang; Kai Zheng (Journal of Environmental Management, 2024)

Light driven depolymerization of tobacco waste: A multi-scale simulations - Jia-hao Wang; Xian-jie Zhang; Lin-can Fang; Wen-xian Chen; An-Fu Hu; Gui-lin Zhuang (Journal of Environmental Chemical Engineering, 2024)

Advances in structure-hypoglycemic activity relationship and mechanisms of berry polysaccharides - Su Jiang-Peng; Fang Jia-Qin; Liu Chuang; Liu Shou-Ping; Chen Chun; Tan Chin-Ping; Wang Ping-Ping; Peng Yun-Ping; Fu Xiong (Food Bioscience, 2024)

Characterization of core microbiota of barley seeds from different continents for origin tracing and quarantine pathogen assessment - Xin Zhou; Fang Liu; Chun-Chun Wang; Hui-Li Zhang; Peng Zhao; Fu-Hong Xie; Dian-Ming Hu; Wei-Jun Duan; Lei Cai (Food Microbiology, 2024)

Synergistically enhanced heterogeneous activation of dissolved oxygen for aqueous carbamazepine degradation over S(III) coupled with siderite - Yuning Fang; Fei Wang; Hongze Fang; Zhaosheng Lei; Wei Song; Caixia Fu; Xing Du; Zhihong Wang; Zhiwei Zhao (Environmental Pollution, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

High efficiency removal of antibiotic resistance gene with designer zinc-finger protein - Jianghao Yu; Meng Fang; Lulu Shi; Jiaming Zhu; Chengzhang Fu; Youming Zhang; Hai Xu; Ling Li; Yu Shen; Mingyu Wang (Bioresource Technology, 2024)

Chemical composition, odor characteristics and risk value analysis of odorants in particleboards - Fang Yang; Xianwu Zou; Liming Zhu; Bin Lv; Yuejin Fu; Bo Liu; Lina Tang; Qian Chen (Atmospheric Pollution Research, 2024)

How the landscape pattern and landscape elements affect the source-based soundscape diversity - Weicong Fu; Jingkai Huang; Chengyu Ran; Wenqiang Fang; Shiyuan Fan; Yujie Zhao; Peilin Huang; Ziluo Huang; Jiaying Dong; Yuqing Huang; Ziru Chen (Urban Ecosystems, 2024)

Divergent Response of Two Bark Beetle–Fungal Symbiotic Systems to Host Monoterpenes Reflects Niche Partitioning Strategies - Zezhen Bai; Jiaxing Fang; Chunmei Yu; Sufang Zhang; Fu Liu; Fuzhong Han; Guorong Zhou; Jianhua Ma; Xiangbo Kong (Journal of Chemical Ecology, 2024)

Thalassospira aquimaris sp. nov. and Winogradskyella marincola sp. nov. two marine bacteria isolated from an agar-degrading co-culture - Zi-Yue Fu; Dao-Feng Zhang; Meng-Han Huang; Hong-Chuan Wang; Xiao-Ye Chen; Yu-Fang Yao; Yang Yuan; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

Genetic characteristics and pathogenicity of variant porcine parvovirus 1 in northern China - Huiwei Deng; Mengting Wang; Guangyi Cong; Fang Fu; Li Feng (Veterinary Microbiology, 2024)

Short-term sedimentary evidence for increasing diatoms in Arctic fjords in a warming world - Fu-Tao Fang; Zhuo-Yi Zhu; Fred Wenger; Jian-Zhong Ge; Jin-Zhou Du; Bing Deng; Hong-Mei Ma; Rui-Feng Zhang; Yu Zhang (Science of The Total Environment, 2024)

Sustainability-inspired upcycling of plastic waste into porous carbon nanobulks for water decontamination via peroxymonosulfate activation - Kun Pang; Fangyu Fu; Haoqi Wang; Shun Ding; Yanfen Fang; Xiang Liu (Science of The Total Environment, 2024)

Remote sensing estimates of global sea surface nitrate: Methodology and validation - Aifen Zhong; Difeng Wang; Fang Gong; Weidong Zhu; Dongyang Fu; Zhuoqi Zheng; Jingjing Huang; Xianqiang He; Yan Bai (Science of The Total Environment, 2024)

Active methane release from the early Cambrian seafloor? Clues from Ba isotopes - Meng Cheng (程猛); Wei Wei; Xinyang Chen; Haiyang Wang; Lianjun Feng; Zhenbing She; Yong Fu; Thomas J. Algeo; Fang Huang; Chao Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Biofilm enhanced the mitigations of antibiotics and resistome in sulfadiazine and trimethoprim co-contaminated soils - Zhi Mei; Fang Wang; Yuhao Fu; Yu Liu; Syed A. Hashsham; Yu Wang; Jean Damascene Harindintwali; Qingyuan Dou; Marko Virta; Xin Jiang; Yu Deng; Tong Zhang; et al. (Journal of Hazardous Materials, 2024)

Comprehensive evaluation of the distribution, transport and ecological risk of heavy metals in intra-urban river sediments using high-resolution techniques - Kang Liao; Weijie Li; Zhiwei Huang; Shu Lin; Lingfang Fu; Wei Liu; Huaiyang Fang; Hong Deng (Environmental Pollution, 2024)

Retraction Note: Changes in ecological networks and eco-environmental effects on urban ecosystem in China’s typical urban agglomerations - Ying Fang; Jing Wang; Shihang Fu; Tianlin Zhai; Longyang Huang (Environmental Science and Pollution Research, 2024)

Real-time tilapia fillet defect segmentation on edge device for robotic trimming - Yingchao He; Weidong Xu; Da Liu; Maozhen Qu; Jiaying Fu; Fang Cheng (Computers and Electronics in Agriculture, 2024)

Corrigendum to “Biochar as a partner of plants and beneficial microorganisms to assist in-situ bioremediation of heavy metal contaminated soil” [Sci. Total Environ. 923 (2024) 171442] - Jieting Wu; Xiaofan Fu; Lei Zhao; Jin Lv; Sidi Lv; Jing Shang; Jiaxuan Lv; Shuxuan Du; Haijuan Guo; Fang Ma (Science of The Total Environment, 2024)

Hourly effect of atmospheric reactive nitrogen species on the onset of acute ischemic stroke: Insight from the Shanghai Stroke Service System Database - Kun Fang; Lan Hong; Yiran Zhang; Nan Cao; Jialiang Feng; Ming Hu; Qingyan Fu; Yang Zheng; Qundi Yang; Yuzhuo Wang; Jinyitao Wang; Shunyao Wang; et al. (Science of The Total Environment, 2024)

Environmental exposure patterns to 94 current-use pesticides in women of reproductive age who are preparing for pregnancy - Tian Tian; Fang Liu; Yu Fu; Junjie Ao; Shujian Lin; Qianhui Cheng; Kalbinur Kayim; Fei Kong; Linlin Wang; Xiaoyu Long; Yuanyuan Wang; Jie Qiao (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Robust data-driven wave excitation force estimation for wave energy converters with nonlinear probabilistic modelling - Yanhua Liu; Shuo Shi; Ying Fang; Aolong Fu (Ocean Engineering, 2024)

Manure sterilization reduced antibiotic resistance genes in lettuce endophytes - Qingyuan Dou; Ying Liang; Yuhao Fu; Zhi Mei; Leilei Xiang; Rehan Ahmad; Wei Zhao; Xin Jiang; Syed A. Hashsham; James M. Tiedje; Fang Wang (Journal of Cleaner Production, 2024)

Effects of aeration coupled with microbial fuel cell on nitrogen removal and electricity production for biogas slurry - Siyu Li; Fang Wang; Xizhen Yang; Yulu Wang; Deli Zhang; Fuli Yang; Peng Fu; Weiming Yi (Journal of Environmental Chemical Engineering, 2024)

PSO-SLIC algorithm: A novel automated method for the generation of high-homogeneity slope units using DEM data - Yange Li; Bangjie Fu; Zheng Han; Zhenxiong Fang; Ningsheng Chen; Guisheng Hu; Weidong Wang; Guangqi Chen (Geomorphology, 2024)

A pair of cadinane-type sesquiterpene enantiomers and other chemical constituents from the whole plants of Chloranthus henryi - Meng-Li He; Lian-Lian Xu; Shi-Qin Fu; Yang Liu; Yong-Ming Luo; Fang-You Chen (Biochemical Systematics and Ecology, 2024)

In-situ remediation of cadmium contamination in paddy fields: from rhizosphere soil to rice kernel - Hai Yan Long; Guang Fu Feng; Jun Fang (Environmental Geochemistry and Health, 2024)

Magnetic conjugated microporous polymer for rapid extraction and sensitive analysis of environmental endocrine disruptors in environmental waters and dairy products - Hai-Long Jiang; Fu-Shuai Kang; Ye-Fei Fan; Xia Wang; Yun-Liang Lin; Lu Liu; Wei Liu; Yan-Fang Zhao; Ru-Song Zhao (Analytica Chimica Acta, 2024)

Triple Ionosophere PhotoMeter onboard Fengyun-3E satellite: Data validation and ionosphere information extraction - Fang Jiang; Tian Mao; LiPing Fu; Jin-Song Wang (Advances in Space Research, 2024)

Therapeutic Effect of Smilax glabra Roxb. on Weaning Rats Against Pb-Induced Nephrotoxicity Based on Network Pharmacology - Chongmei Tian; Meiting Yu; Yuejuan Fang; Yaping Zhao; Liping Fu; Jingbai Chen; Daozong Xia (Biological Trace Element Research, 2024)

Iron minerals enhance Fe(II)-mediated abiotic As(III) oxidation - Xin Zhang; Qingling Fu; Hongqing Hu; Jun Zhu; Linchuan Fang (Chemosphere, 2024)

Emission characteristic, spatial distribution, and health risk of polycyclic aromatic compounds (PAHs, NPAHs, and OPAHs) from light-duty gasoline and diesel vehicles based on on-road measurements - Jiaqi Fu; Tiange Fang; Yutong Gao; Ting Wang; Zhenyu Jia; Dongping Guo; Hongjun Mao (Science of The Total Environment, 2024)

Dissolved oxygen fluctuation alters dissolved organic carbon stability and can accumulate resistant fraction - Yu-Qing Li; Fu-Tao Fang; Cong Zeng; Zhuo-Yi Zhu (Marine Chemistry, 2024)

Manganese/iron organic frame material derivatives for rapid catalytic oxidation of metronidazole: Performance and mechanism - Hongyang Jiang; Zhiyong Zhang; Mingze Fang; Jiuming Hu; Ming-Lai Fu; Lei Chen; Baoling Yuan (Journal of Water Process Engineering, 2024)

A novel environmentally-friendly filler of the asphalt mastic: Organic modified waste shells - Song Xu; Shaoxu Cai; Chanlin Zhang; Lei Fang; Chongyu Bian; Xiaobin Zou; Dabao Fu (Journal of Cleaner Production, 2024)

Utilizing spontaneous plants for sustainable development in residential green spaces: Insights from environmental drivers and niche analysis in Fuzhou City, China - Chengyu Ran; Junyi Pan; Yuxin Lin; Tongyan Li; Yaling Huang; Jingkai Huang; Shiyuan Fan; Wenqiang Fang; Shuang Zhao; Yuxiang Liu; Jiali Jin; Weicong Fu (Journal of Environmental Management, 2024)

Self-hydrogen transfer hydrogenolysis of β-O-4 bonds in lignin model compounds over NiCu/Al2O3 catalyst - Fa-Peng Wu; Le-Le Qiu; Yun-Peng Zhao; Zong-Pin Fu; Jing Liang; Jian Xiao; Jian Li; Fang-Jing Liu; Jing-Pei Cao (Fuel, 2024)

Understanding iodine adsorption sites on monolithic N/O co-doped carbon fibers with scaffolding structure - Hongquan Fu; Yue Tang; Qiao Yuan; Jingming Chang; Fang Liao; Juan Zhang; Hejun Gao; Yi Yang; Yunwen Liao (Fuel, 2024)

Degradation of sulfamethazine in coastal aquaculture tailwater by Na2S2O4@iron-electrode electrooxidation combined with ceramic membrane process - Wei Song; Yuning Fang; Hongze Fang; Deming Gu; Xing Du; Sen Xu; Caixia Fu; Yu Zhou; Zhihong Wang (Environmental Pollution, 2024)

Enhanced Fenton-like catalysis via interfacial regulation of g-C3N4 for efficient aromatic organic pollutant degradation - Bin Zhou; Qingsong Liu; Caihong Zheng; Yao Ge; Lili Huang; Haoyang Fu; Shengqiong Fang (Environmental Pollution, 2024)

Molybdenum isotopic evidence for the initiation of a big mantle wedge beneath eastern Asia - Wei Fang; Li-Qun Dai; Zi-Fu Zhao; Qi Chen; Jun Yan; Dayu Zhang; Ding-Sheng Jiang (Chemical Geology, 2024)

Temporal variation of mercury and methyl mercury in water and accumulation by phytoplankton in the eutrophic estuary, northern Taiwan - Tien Hsi Fang; Fu Wei Chang (Marine Pollution Bulletin, 2024)

Climate change impacts on magnitude and frequency of urban floods under scenario and model uncertainties - Luyao Wang; Zhenyu Huang; Bin Gan; Zhouping Zhang; Haohuan Fu; Dengmao Fang; Runmin Dong; Yang Liu; WeiPeng Zhang; Ruyi Li; Xin Dong (Journal of Environmental Management, 2024)

Dynamic changes of key metabolites in Longjing green tea during processing revealed by widely targeted metabolomic profiling and sensory experiments - Lin Zeng; Yan-Qing Fu; Ying Gao; Fang Wang; Shuang Liang; Jun-Feng Yin; Marie-Laure Fauconnier; Lijing Ke; Yong-Quan Xu (Food Chemistry, 2024)

Dynamics changes in metabolites and pancreatic lipase inhibitory ability of instant dark tea during liquid-state fermentation by Aspergillus niger - Haoran Sun; Ranqin Fan; Rui Fang; Shanshan Shen; Yu Wang; Jialin Fu; Rui Hou; Runchen Sun; Shinuo Bao; Qi Chen; Pengxiang Yue; Xueling Gao (Food Chemistry, 2024)

Arching effect in slopes under excavation: Classification and features - Kun Fang; Shixun Jia; Huiming Tang; Ruizhi Zhou; Zheng Kong; Yulei Fu; Penju An; Bocheng Zhang; Qiong Wu (Engineering Geology, 2024)

Stabilizing Cu0/Cu2+ interface by hydroxy-rich amorphous SiO2 for enhanced electrocatalytic CO2 reduction to ethylene - Jie Zhu; Sifan Wang; Jiaji Zhang; Zhecheng Fang; Weitao Ji; Gaobo Lin; Lei Guo; Bolong Li; Jianghao Wang; Jie Fu (Chemical Engineering Journal, 2024)

Challenges and opportunities in human dimensions behind cat–wildlife conflict - Changjian Fu; Fang Wang; Yumeng Zhao; Qin Zhu; Yunchao Luo; Yuhang Li; Ziye Zhang; Xueting Yan; Taozhu Sun; Yang Liu; Zhongqiu Li (Conservation Biology, 2024)
Because global anthropogenic activities cause vast biodiversity loss, human dimensions research is essential to forming management plans applicable to biodiversity conservation outside wilderness areas. Engaging public participation is crucial in this context to achieve social and environmental benefits. However, knowledge gaps remain in understanding how a balance between conservation and public demands can be reached and how complicated sociocultural contexts in the Anthropocene can be incorporated in conservation planning. We examined China's nationwide conflict between free‐ranging cats (owned cats that are allowed to go outdoors or homeless cats living outdoors) and wildlife to examine how a consensus between compassion and biodiversity conservation can help in decision‐making. We surveyed a random sample of people in China online. Over 9000 questionnaires were completed (44.2% response). In aggregate, respondents reported approximately 29 million free‐ranging owned cats and that over 5 million domestic cats per year become feral in mainland China. Respondents who were cat owners, female, and religious were more likely to deny the negative impacts of cats on wildlife and ongoing management strategies and more supportive of stray cat shelters, adoption, and community‐based fund raising than nonowners, male, and nonreligious respondents ( p p

MEvo-GAN: A Multi-Scale Evolutionary Generative Adversarial Network for Underwater Image Enhancement - Feiran Fu; Peng Liu; Zhen Shao; Jing Xu; Ming Fang (Journal of Marine Science and Engineering, 2024)
In underwater imaging, achieving high-quality imagery is essential but challenging due to factors such as wavelength-dependent absorption and complex lighting dynamics. This paper introduces MEvo-GAN, a novel methodology designed to address these challenges by combining generative adversarial networks with genetic algorithms. The key innovation lies in the integration of genetic algorithm principles with multi-scale generator and discriminator structures in Generative Adversarial Networks (GANs). This approach enhances image details and structural integrity while significantly improving training stability. This combination enables more effective exploration and optimization of the solution space, leading to reduced oscillation, mitigated mode collapse, and smoother convergence to high-quality generative outcomes. By analyzing various public datasets in a quantitative and qualitative manner, the results confirm the effectiveness of MEvo-GAN in improving the clarity, color fidelity, and detail accuracy of underwater images. The results of the experiments on the UIEB dataset are remarkable, with MEvo-GAN attaining a Peak Signal-to-Noise Ratio (PSNR) of 21.2758, Structural Similarity Index (SSIM) of 0.8662, and Underwater Color Image Quality Evaluation (UCIQE) of 0.6597.

In-situ trace element and Sr isotope in mantle xenoliths from the West Qinling orogen: Evidence for carbonate metasomatism - Wei Fang; Li-Qun Dai; Zi-Fu Zhao; Guo-Chao Sun (Lithos, 2024)

Co-exposure of decabromodiphenyl ethane and cadmium increases toxicity to earthworms: Enrichment, oxidative stress, damage and molecular binding mechanisms - Zhihua Qiao; Xinlin Sun; Mengru Fu; Shanqi Zhou; Yanna Han; Xuan Zhao; Kailin Gong; Cheng Peng; Wei Zhang; Fang Liu; Chunmei Ye; Jie Yang (Journal of Hazardous Materials, 2024)

Construction of blackberry polysaccharide nano-selenium particles: Structure features and regulation effects of glucose/lipid metabolism in HepG2 cells - Dou Zu-Man; Zhang Yu-Long; Tang Chun-Yang; Liu Chuang; Fang Jia-Qin; Huang Qiang; Chen Chun; You Li-Jun; Tan Chin-Ping; Niu Hui; Fu Xiong (Food Research International, 2024)

A comparative evaluation of biochar and Paenarthrobacter sp. AT5 for reducing atrazine risks to soybeans and bacterial communities in black soil - Jean Damascene Harindintwali; Chao He; Xin Wen; Yu Liu; Mingyi Wang; Yuhao Fu; Leilei Xiang; Jiandong Jiang; Xin Jiang; Fang Wang (Environmental Research, 2024)

Thermodynamic corrections of high salinity system for selective lithium extraction from brines with LiMn2O4/λ-MnO2 - Penglin Wang; Shiyu Zhou; Yu Fu; Hualiang Fang; Shuai Gu; Jianguo Yu (Desalination, 2024)

Ternary-coordination-regulated polyamide nanofiltration membranes for Li+/Mg2+ separation - Shang Fang; Kecheng Guan; Siyu Zhou; Qiangqiang Song; Yongxuan Shi; Wenming Fu; Zhan Li; Ping Xu; Mengyang Hu; Zhaohuan Mai; Pengfei Zhang; Hideto Matsuyama (Desalination, 2024)

FPS-U2Net: Combining U2Net and multi-level aggregation architecture for fire point segmentation in remote sensing images - Wei Fang; Yuxiang Fu; Victor S. Sheng (Computers & Geosciences, 2024)

Construction of 2D/2D NH2-TiO2/ReS2 molecular-connected heterojunction to achieve selective carrier transport for photocatalytic hydrogen production - Huihui Weng; Houjiang Liu; Guijun Yang; Jiawei Ding; Chuangchuang Gong; Yuanyuan Fu; Jin Cui; Liying Ma; Chunnian He; Naiqin Zhao; Fang He (Chemical Engineering Journal, 2024)

A comprehensive N-glycome map of porcine sperm membrane before and after capacitation - Yueyue Li; Yujia Zhai; Bin Fu; Yuanlin He; Ying Feng; Fang Ma; Haojie Lu (Carbohydrate Polymers, 2024)

Divergent responses of soil microbial community to long-term nitrogen and phosphorus additions in a subtropical Chinese fir plantation - Fangchao Wang; Qiao Liu; Xiaofei Hu; Xiang-Min Fang; Shengnan Wang; Fu-Sheng Chen (CATENA, 2024)

Weak geostrophic wind driven ventilation in street canyons with trees and green walls: Cooperating or opposing dispersions of airborne pollutants? - Yu-Fei Tang; Hao Chen; Ming Yang; Zhi-Cheng Tan; Fu-Yun Zhao; Jiang-Hua Guo; Yueping Fang (Building and Environment, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Deep soil microbial carbon use efficiency responds stronger to nitrogen deposition than top soil in tropical forests, southern China - Yamin Jiang; Tianyan Su; Huafeng Wang; Qiu Yang; Jingli Lu; Qunyou Fu; Han Mao; Wenxian Xu; Yiqi Luo; Wenjie Liu; Huai Yang; Mengyang Fang (Plant and Soil, 2024)

Distinct effects of canopy vs understory and organic vs inorganic N deposition on root resource acquisition strategies of subtropical Moso bamboo plants - Lin Wang; Baogang Zhang; Yunying Fang; Huajun Yin; Shenglei Fu; Scott X. Chang; Yanjiang Cai (Science of The Total Environment, 2024)

Underlying mechanisms governing on distribution and stratification of DOM during seasonal freeze-thaw cycles - Weiying Feng; Yuxin Deng; Fang Yang; Tingting Li; Fu Wang; Qi Zhang; Haipeng Yao; Haiqing Liao (Science of The Total Environment, 2024)

Sulfur enhances iron plaque formation and stress resistance to reduce the transfer of Cd and As in the soil-rice system - Fei Miao; Xin Zhang; Qingling Fu; Hongqing Hu; Md. Shoffikul Islam; Linchuan Fang; Jun Zhu (Science of The Total Environment, 2024)

Bi-2-(2-phenethyl)chromone derivatives from agarwood of Aquilaria filaria in the Philippines - Hong-Run Yang; Hao Wang; Pei Wang; Fang-Zheng Liu; Hong-Xing Chai; Cai-Hong Cai; Li Yang; Jing-Zhe Yuan; Bei Jiang; Wen-Li Mei; Hao-Fu Dai (Phytochemistry, 2024)

Co-occurrence patterns of gut microbiome, antibiotic resistome and the perturbation of dietary uptake in captive giant pandas - Yuhao Fu; Feiran Jia; Jingfang Su; Xinyao Xu; Yuqin Zhang; Xiangzhen Li; Xin Jiang; Andreas Schäffer; Marko Virta; James M. Tiedje; Fang Wang (Journal of Hazardous Materials, 2024)

Novel (2,6-difluorobenzoyl)urea-activated fluorescent probe for fluorine-containing-pesticide detection - Yulong Liu; Fang Sun; Binbin Jia; Zishi Wang; Mingli Yue; Liu Yang; Ying Fu; Fei Ye (Journal of Environmental Chemical Engineering, 2024)

Enteral nutrition in the management of acute pancreatitis: Modulates gut microbiome and alleviates inflammation - Fang-Yuan Yang; Yi-Jing Cai; Xiao-Ying Niu; Shun-Fu Wang; Yu-Qi Wang; Sabola Eluby Esmie; Rui-Cong Chen; Sheng-Jie Dai; Hong-Ru Kong; Hong-Wei Sun; Ke-Qing Shi (Food Bioscience, 2024)

Soluble and insoluble fractions of soy protein isolate affect the properties of its high-moisture extrudates - Liwei Fu; Zhaojun Wang; Benu Adhikari; Zhiyong He; Maomao Zeng; Fang Qin; Jie Chen (Food Bioscience, 2024)

Mo-Mg isotopes trace the role of serpentinite in generating arc magmatism - Qing-Chen Yang; Wei Fang; Li-Qun Dai; Zi-Fu Zhao; Guo-Chao Sun; Bing Gong (Chemical Geology, 2024)

Reactive Oxygen Species-Mediated Mitophagy and Cell Apoptosis are Involved in the Toxicity of Aluminum Chloride Exposure in GC-2spd - Hui- xin Peng; Fu Chai; Ke-heng Chen; Yan-xin Huang; Guang-ji Wei; Huixiong Yuan; Yan-fang Pang; Shi-hua Luo; Chun-fang Wang; Wen-cheng Chen (Biological Trace Element Research, 2024)

Algae-bacteria consortia promotes the cell growth of marine microalgae Phaeodactylum tricornutum and Chrysotila roscoffensis - Jiaqi Fang; Yan Sun; Zhujun Zhu; Jian Li; Pengfei Cheng; Spiros N. Agathos; Yuanyuan Fu; Lin Zhang; Chengxu Zhou; Jichang Han (Algal Research, 2024)

Hot spots and trends in microbial disease research on cultural heritage: a bibliometric analysis - Weilin Chen; Baorong Fu; Fang Ma; Zhe He; Ming Li (Environmental Science and Pollution Research, 2024)

Combating antibiotic resistance in the human-impacted environment with carbon-based materials: Applications and challenges - Yuhao Fu; Fang Wang; Leilei Xiang; Jean Damascene Harindintwali; Martin Elsner; Wulf Amelung; Stephan Kueppers; Xin Jiang; Marko Virta; Mika Sillanpää; Andreas Schäffer; Yong-guan Zhu; et al. (Critical Reviews in Environmental Science and Technology, 2024)

Early detection of rubber tree powdery mildew using UAV-based hyperspectral imagery and deep learning - Tiwei Zeng; Yong Wang; Yuqi Yang; Qifu Liang; Jihua Fang; Yuan Li; Huiming Zhang; Wei Fu; Juan Wang; Xirui Zhang (Computers and Electronics in Agriculture, 2024)

Formation of reactive intermediates in paddy water from different temperature zones for the promotion of abiotic ammonification - Yu Zeng; Mingyang Zhang; Qinglong Fu; Ning Chen; Yujun Wang; Dongmei Zhou; Guodong Fang (Water Research, 2024)

New insights into functional divergence and adaptive evolution of uncultured bacteria in anammox community by complete genome-centric analysis - Yi-Cheng Wang; Yanping Mao; Hui-Min Fu; Jin Wang; Xun Weng; Zi-Hao Liu; Xiao-Wei Xu; Peng Yan; Fang Fang; Jin-Song Guo; Yu Shen; You-Peng Chen (Science of The Total Environment, 2024)

Biochar as a partner of plants and beneficial microorganisms to assist in-situ bioremediation of heavy metal contaminated soil - Jieting Wu; Xiaofan Fu; Lei Zhao; Jin Lv; Sidi Lv; Jing Shang; Jiaxuan Lv; Shuxuan Du; Haijuan Guo; Fang Ma (Science of The Total Environment, 2024)

A dynamic von Mises-based model to evaluate the impact of urbanization and climate change on flood timing in Yangtze and Huaihe River Basins, China - Pengcheng Xu; Dong Wang; Yuankun Wang; Vijay P. Singh; Zhilang Zhang; Xiaosan Shang; Hongyuan Fang; Yangyang Xie; Gengxi Zhang; Saiyan Liu; Xiaolei Fu (Journal of Hydrology, 2024)

Exposure to heavy metallic and trace essential elements and risk of diminished ovarian reserve in reproductive age women: A case-control study - Tian Tian; Zheng Wang; Fang Liu; Yu Fu; Fei Kong; Yuanyuan Wang; Qin Li; Xiaoyu Long; Jie Qiao (Journal of Hazardous Materials, 2024)

Synergistic mitigation of atrazine-induced oxidative stress on soybeans in black soil using biochar and Paenarthrobacter sp. AT5 - Jean Damascene Harindintwali; Xin Wen; Chao He; Mingxu Zhao; Jianhao Wang; Qingyuan Dou; Leilei Xiang; Yuhao Fu; Daniel S. Alessi; Xin Jiang; Jiandong Jiang; Fang Wang (Journal of Environmental Management, 2024)

Zygotic quiescence prolongs the reproductive cycle in Berchemia sinica (Rhamnaceae) - Fang Ma; Yaolei Fu; Wenjun Wei; Ziwei Li; Jing Liu; Baoxia Bi; Wenzhe Liu (Flora, 2024)

Distribution characteristics of reactive silicon in six water bodies in the Yangtze River Basin in China - Xuemei Chen; Lanwei Liang; Songjie Fu; Xu Bao; Sen Gu; Yang Jiao; Fang Hu; Abdur Rahman; Qingman Li (Environmental Research, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

The evolution and formation of centromeric repeats analysis in Vitis vinifera - Dan Pei; Xue Yu; Weihong Fu; Xuhui Ma; Jinggui Fang (Planta, 2024)

Proteomics Sequencing Reveals the Role of TGF-β Signaling Pathway in the Peripheral Blood of Offspring Rats Exposed to Fluoride - Fang-fang Yu; Shui-yuan Yu; Lei-zhen Duan; Shuo Yang; Xiang-bo Hou; Yu-hui Du; Ming-hui Gao; Juan Zuo; Lei Sun; Xiao-li Fu; Zhi-yuan Li; Hui Huang; et al. (Biological Trace Element Research, 2024)

Exploring the impact of ESG ratings on enterprises' green technology innovation - Mingtao Zhao; Xuebao Fu; Guobing Fang; Lianbiao Cui; Abdelmohsen A. Nassani (Environment, Development and Sustainability, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Petrogenetic link between leucogranite and spodumene pegmatite in Lhozhag, eastern Himalaya: Constraints from U–(Th)–Pb geochronology and Li–Nd–Hf isotopes - Lei Yang; Jia-Min Wang; Xiao-Chi Liu; Fang-Yang Hu; Kang-Shi Hou; Jian-Gang Fu; Guang-Ming Li; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2024)

Decolorization and detoxification of Brilliant Crocein GR by a newly enriched thermophilic consortium - Fang Tian; Guang Guo; Weilian Fu; Shiji Li; Keqiang Ding; Feng Yang; Chengyue Liang (Journal of Environmental Management, 2024)

Analysis of novel In2S3/polyimide Z-scheme heterojunctions with enhanced photocatalytic target compound degradation efficiency - Min Fu; Mei Yang; Jinwu Bai; Yi Li; Meng Fang; Peng Lu; Xue Kuang (Journal of Environmental Chemical Engineering, 2024)

Crystal mush rejuvenation in the formation of Triassic dacites in Mengku, SE Tibetan Plateau - Feng Cong; Fu-Yuan Wu; Wen-Chang Li; Zai-Bo Sun; Xiao-Chi Liu; De-Feng He; Wei-Qiang Ji; Fang-Yang Hu; Shao-Hua Zhang; Xiao-Ming Huang (Journal of Asian Earth Sciences, 2024)

Fluid-metasomatized rocks with extremely low δ26Mg values in subducted oceanic lithosphere: Implications for mantle Mg isotope heterogeneity and the origin of low-δ26Mg magmas - Jia-Wei Xiong; Yi-Xiang Chen; Marco Scambelluri; Xin-Yue Qiao; Yu Chen; Fang Huang; Donato Belmonte; Zi-Fu Zhao (Geochimica et Cosmochimica Acta, 2024)

Moisture content of tea dhool for the scenting process affects the aroma quality and volatile compounds of osmanthus black tea - Xin Meng; Jie-Qiong Wang; Fang Wang; Ying Gao; Chao-Hong Fu; Qizhen Du; Zhi-Hui Feng; Jian-Xin Chen; Jun-Feng Yin; Yong-Quan Xu (Food Chemistry, 2024)

Storm-induced nitrogen transport via surface runoff, interflow and groundwater in a pomelo agricultural watershed, southeast China - Yao Wang; Fenfang Wang; Yan Fang; Yuqi Fu; Nengwang Chen (Environmental Pollution, 2024)

Modelling of sulfur chemistry in a fog episode in northern China and implication for the efficacy of SO2 emission control - Leyi Yuan; Mingxu Liu; Xinyi Dang; Hao Wu; Fang Shang; Lianfang Wei; Pingqing Fu; Yu Song; Min Hu (Atmospheric Environment, 2024)

A Proactive Intervention Study in Metabolic Syndrome High-Risk Populations Using Phenome-Based Actionable P4 Medicine Strategy - Qiongrong Huang; Zhiyuan Hu; Qiwen Zheng; Xuemei Mao; Wenxi Lv; Fei Wu; Dapeng Fu; Cuihong Lu; Changqing Zeng; Fei Wang; Qiang Zeng; Qiaojun Fang; et al. (Phenomics, 2024)

Comment on “Risk of gastric cancer among long‑term proton pump inhibitor users: a population‑based cohort study” - Shih-Wei Lai; Bing-Fang Hwang; Chiu-Shong Liu; Kuan-Fu Liao (European Journal of Clinical Pharmacology, 2024)

High-performance plastic-derived metal-free catalysts for organic pollutants degradation via Fenton-like reaction - Yu Hou; Qi Fu; Huajie Zhong; Jiaxing Yu; Yuan Tao; Zeyu Gong; Jianqiang Li; Songbo Wei; Junlang Qiu; Junhui Wang; Fang Zhu; Gangfeng Ouyang (Science of The Total Environment, 2024)

Motility behavior and physiological response mechanisms of aerobic denitrifier, Enterobacter cloacae strain HNR under high salt stress: Insights from individual cells to populations - Meng Cheng; Hui-Min Fu; Zheng Mao; Peng Yan; Xun Weng; Teng-Fei Ma; Xiao-Wei Xu; Jin-Song Guo; Fang Fang; You-Peng Chen (Science of The Total Environment, 2024)

Titanite geochemistry traces extreme differentiation of granitic magma in the collisional orogen - Kun Zhou; He-Zhi Ma; Yi-Xiang Chen; Fang-Yue Wang; Zi-Fu Zhao (Lithos, 2024)

Co-occurrence of organophosphate esters and phosphorus fractions in river sediments: Implications for pollution prediction and environment risk assessment - Lingfang Fu; Yuxin Liu; Shu Lin; Jieer Xiao; Weijie Li; Yang Yu; Hailong Zeng; Ping Li; Huaiyang Fang (Journal of Hazardous Materials, 2024)

T-2 toxin induces mitochondrial dysfunction in chondrocytes via the p53-cyclophilin D pathway - Fang-fang Yu; Shui-yuan Yu; Lei Sun; Juan Zuo; Kang-ting Luo; Miao Wang; Xiao-li Fu; Feng Zhang; Hui Huang; Guo-yu Zhou; Yan-jie Wang; Yue Ba (Journal of Hazardous Materials, 2024)

Role of inflammatory lipid and fatty acid metabolic abnormalities induced by plastic additives exposure in childhood asthma - Zhiyu Chen; Fang Li; Lei Fu; Yu Xia; Ying Luo; Ang Guo; Xiaona Zhu; Huifang Zhong; Qian Luo (Journal of Environmental Sciences, 2024)

Late Ordovician lingulid brachiopods from the Pingliang Formation (Shaanxi Province, North China): Morphological and ecological implications - Yue Liang; Rao Fu; Yazhou Hu; Fan Liu; Baopeng Song; Mei Luo; Xinyi Ren; Jiayue Wang; Caibin Zhang; Ruisen Fang; Xuan Yang; Lars E. Holmer; et al. (Journal of Asian Earth Sciences, 2024)

Methyl jasmonate regulation of pectin polysaccharides in Cosmos bipinnatus roots: A mechanistic insight into alleviating cadmium toxicity - Chun-Yu Fan; Xiao-Fang Yu; Yu-Jia Liu; Xiao-Xuan Zeng; Fu-Wen Luo; Xian-Tong Wang; Xuan Yang; Xiao-Yu Wang; Xiao Xue; Li-Juan Yang; Ting Lei; Ming-Yan Jiang; et al. (Environmental Pollution, 2024)

Flutter control optimization for a 5000 m suspension bridge with active aerodynamic flaps: a CFD-enabled strategy - Zilong Wang; Lin Zhao; Yiheng Fu; Genshen Fang; Wei Cui; Ke Li; Yaojun Ge (Engineering Structures, 2024)

Embedding hydrogel electrodes into hydrogel Electrolyte: An 3D protecting strategy for stretchable High-Performance supercapacitor - Chuanling Mu; Jun Fang; Junlian Nie; Lu Fu; Wen Li (Chemical Engineering Journal, 2024)

Revealing the role of CCoAOMT1: fine-tuning bHLH transcription factors for optimal anther development - Zesen Lai; Jianzheng Wang; Ying Fu; Menghan Wang; Hong Ma; Shiqing Peng; Fang Chang (Science China Life Sciences, 2024)

ACT001 alleviates inflammation and pyroptosis through the PPAR-γ/NF-κB signaling pathway in LPS-induced alveolar macrophages - Qiang Fu; Na Shen; Tao Fang; Hewei Zhang; Yanbo Di; Xuan Liu; Chao Du; Jianshuang Guo (Genes & Genomics, 2024)

Observing eddy dye patches induced by shear instabilities in the surf zone on a plane beach - Chunping Ren; Nannan Fu; Chong Yu; Yuchuan Bai; Kezhao Fang (Acta Oceanologica Sinica, 2024)

Progress and evolution of hotspots in butterfly diversity research in green spaces - Ying Lin; Shanjun Huang; Wenqiang Fang; Shiyuan Fan; Chengyu Ran; Emily Dang; Weicong Fu; Zhipeng Zhu (Environmental Science and Pollution Research, 2024)

Exploring the adverse effects of 1,3,6,8-tetrabromo-9H-carbazole in atherosclerotic model mice by metabolomic profiling integrated with mechanism studies in vitro - Tong Xu; Yu Jiang; Hualing Fu; Guanglei Yang; Xiaoxu Hu; Yangsheng Chen; Qian Zhang; Yuxi Wang; Yilan Wang; Heidi Qunhui Xie; Fang Han; Li Xu; et al. (Chemosphere, 2024)

Unequal prefecture-level water footprints in China: The urban-rural divide - Ziyan Fu; Siao Sun; Chuanglin Fang (Science of The Total Environment, 2024)

Characteristics of bacterial community and extracellular enzymes in response to atrazine application in black soil - Tiancong Gao; Haixia Tian; Leilei Xiang; Ziqi Wang; Yuhao Fu; Jing Shi; Xin Wen; Xin Jiang; Wenxiang He; Syed A. Hashsham; Fang Wang (Environmental Pollution, 2024)

Harsh environment resistible and recyclable thermoplastic polyurea adhesive based on stable and density hydrogen bonds - Dongqi Wang; Kai Yang; Sisi Cheng; Meishan Fu; Zhihong Wang; Lixia Li; Xin Zhao; Lijing Han; Wenzhi Ren; Fang Yang; Ruoyu Zhang (Chemical Engineering Journal, 2024)

Synergetic construction of color and multifunction for sustainable lyocell fabric by microbial nano pigment - Jing Wu; Ranran Fu; Maochang Xiao; Qiumeng Zheng; Lin Wu; Kuanjun Fang; Yanfei Ren (Chemical Engineering Journal, 2024)

Seascapes Shaped the Local Adaptation and Population Structure of South China Coast Yellowfin Seabream (Acanthopagrus latus) - Wenhao Wang; Junrou Huang; Yan Hu; Jianxiang Feng; Dong Gao; Wenyu Fang; Meng Xu; Chunlei Ma; Zhenqiang Fu; Qinglong Chen; Xuanguang Liang; Jianguo Lu (Marine Biotechnology, 2024)

Identification of flowering genes in Camellia perpetua by comparative transcriptome analysis - Jing-jing Yu; Jia Cui; Han Huang; Dong-can Cen; Fang Liu; Zeng-Fu Xu; Yi Wang (Functional & Integrative Genomics, 2024)

Dynamic Effect of Landslides Triggered by Earthquake: A Case Study in Moxi Town of Luding County, China - Hongfu Zhou; Fei Ye; Wenxi Fu; Bin Liu; Tian Fang; Rui Li (Journal of Earth Science, 2024)

The microclimate impact of treetop walk based on plant community simulation - Ying Lin; Shanjun Huang; Han Xu; Wenqiang Fang; Chenfei Gao; Jingkai Huang; Weicong Fu (Environmental Science and Pollution Research, 2024)

Luteolin inhibits the JAK/STAT pathway to alleviate auditory cell apoptosis of acquired sensorineural hearing loss based on network pharmacology, molecular docking, molecular dynamics simulation, and experiments in vitro - Fang Guo; Yingyuan Guo; Dejun Zhang; Zeming Fu; Shuang Han; Yining Wan; Guofang Guan (Toxicology and Applied Pharmacology, 2024)

Garnet geochemistry reveals late-stage oxidation of tin-bearing fractionated granite - Jin-Xiang Li; Lin Ding; Noreen J. Evans; Fang Xu; Wei-Ming Fan; Li-Yun Zhang; Fu-Long Cai; Qiu-Yun Guan; Ya-Hui Yue; Jing Xie (Lithos, 2024)

Efficient activation of peracetic acid by multi-valent Cu7S4 for the degradation and detoxication of tetracycline hydrochloride: Cu3+ acts as an active site - Lu Song; Qi Fang; Qingyun Yang; Xijun Fu; Yining Lu; Tao Cai; Mengzhe Zou; Qingyi Zeng (Journal of Water Process Engineering, 2024)

Physiological and transcriptomic changes drive robust responses in Paenarthrobacter sp. AT5 to co-exposure of sulfamethoxazole and atrazine - Jean Damascene Harindintwali; Qingyuan Dou; Xin Wen; Leilei Xiang; Yuhao Fu; Lei Xia; Zhongjun Jia; Xin Jiang; Jiandong Jiang; Fang Wang (Journal of Hazardous Materials, 2024)

Soil properties and organochlorine compounds co-shape the microbial community structure: A case study of an obsolete site - Yu Liu; Fang Wang; Ziquan Wang; Leilei Xiang; Yuhao Fu; Zhiliang Zhao; Fredrick Orori Kengara; Zhi Mei; Chao He; Yongrong Bian; Ravi Naidu; Xin Jiang (Environmental Research, 2024)

A Ni/Co-free high-entropy layered cathode with suppressed phase transition and near-zero strain for high-voltage sodium-ion batteries - Ziqing Wang; Lei Fang; Xiaoguang Fu; Shengfeng Zhang; Huabin Kong; Hongwei Chen; Fang Fu (Chemical Engineering Journal, 2024)

Spatial variation of organic carbon storage and aggregate sizes in the sediment of the Zhangjiang mangrove ecosystem - Ran Yan; Jianxiang Feng; Tao Fu; Qiqi Chen; Zhenyu Wang; Fang Kang; Jing Fang; Guanmin Huang; Qingshu Yang (CATENA, 2024)

Simvastatin ameliorates synaptic plasticity impairment in chronic mild stress-induced depressed mice by modulating hippocampal NMDA receptor - Xu-Ben Yu; Kai-Long Zhong; Chuang Chen; Jing Fu; Fang Chen; Hong-Min Zhou; Xiu-Hua Zhang; Kwonseop Kim; Jing-Ye Pan (Psychopharmacology, 2024)

Prime editing: current advances and therapeutic opportunities in human diseases - Yidian Fu; Xiaoyu He; Xin D. Gao; Fang Li; Shengfang Ge; Zhi Yang; Xianqun Fan (Science Bulletin, 2023)

Revealing the dynamic changes of lipids in coffee beans during roasting based on UHPLC-QE-HR-AM/MS/MS - Jinrui Zhu; Li Zhou; Minjie Zhao; Fang Wei; Haiyan Fu; Eric Marchioni (Food Research International, 2023)

Effects of external environment on promoter methylation of PIK3R5 and related pathway regulation in steroid-induced femoral head necrosis - Wentao Qin; Mingyang Jiang; Shenyi Lu; Yang Hu; Fu Gan; Weijun Fang; Dongxu Chen; Zhandong Bo (Environmental Research, 2023)

Metal-organic frameworks (MOFs)-derived Mn2SnO4@C anode based on dual lithium storage mechanism for high-performance lithium-ion capacitors - You-Kang Duan; Zhi-Wei Li; Shi-Chun Zhang; Tong Su; Yan-Fang Ma; Ai-Jun Jiao; Zhen-Hai Fu (Chemical Engineering Journal, 2023)

Molybdenum isotopic heterogeneity for intraplate basalts and its origin - Wei Fang; Li-Qun Dai; Zi-Fu Zhao (Chemical Geology, 2023)

Mo isotopes record recycling of anoxic sediment in a Paleo-oceanic subduction zone - Xiang Fu; Wei Fang; Li-Qun Dai; Zi-Fu Zhao; Bing Gong; Yong-Fei Zheng (Chemical Geology, 2023)

Effects of lead contamination on histology, antioxidant and intestinal microbiota responses in freshwater crayfish, Procambarus clarkii - Yulong Li; Xingwang Zhou; Wei Guo; Yunyin Fu; Guoliang Ruan; Liu Fang; Qian Wang (Aquatic Toxicology, 2023)

Phenylalanine diminishes M1 macrophage inflammation - Qingzhuo Zhang; Siyuan Chen; Yan Guo; Fang He; Jian Fu; Wenkai Ren (Science China Life Sciences, 2023)

Tree species mixture effect on extracellular enzyme kinetics varies with enzyme type and soil depth in subtropical plantations - Xue-Li Jiang; Rong Mao; Zhong-Liang Li; Fu-Sheng Chen; Bin Xu; Jin He; Yu-Xin Huang; Xiang-Min Fang (Plant and Soil, 2023)

Lidocaine pretreatment attenuates inflammatory response and protects against sepsis-induced acute lung injury via inhibiting potassium efflux-dependent NLRP3 activation - Kai Su; Xin-Tao Li; Fang-Xiao Hong; Mu Jin; Fu-Shan Xue (Inflammation Research, 2023)

Deriving fine-scale patterns of sea surface temperature in coral reef habitats using the Landsat 8 thermal infrared sensor - Xiu-Ling Zuo; Ke-Fu Yu; Bin-Ni Qin; Xiao-Peng Duan; Zuo-Fang Yao; Fen-Zhen Su (Frontiers in Marine Science, 2023)
The available sea surface temperature (SST) products are too coarse to assess the fine-scale (<1 km) SST variations related to coral bleaching. In this study, we proposed an optimal SST inversion model using Landsat 8 thermal infrared sensor (TIRS) images to derive fine-scale SST patterns in the coral reef habitats of the Xisha Islands, South China Sea. Our study included two parts: 1) six SST inversion models were developed using the radiative transfer method and the split window (SW) algorithm in the hot season and cool season, from which the optimal SST inversion model was determined; and 2) the optimal model was applied to 47 Landsat 8 TIRS images to derive the SST spatial and temporal pattern among the geomorphic zones of six reefs in hot and cool season conditions. Compared with the measured sea temperature data and the verified MODIS SST products, the SST6 model using the SW algorithm was optimal, with an RMSE of approximately 0.64°C in the hot season. The average SST results usually had a pattern of reef flat > lagoon > reef slope/offshore sea. The reef flat was usually approximately 0.05°C–0.2°C hotter than the lagoon in the hot season. The SST in the lagoon also increased from south to north and the shallow lagoon was usually warmer than the deep lagoon in the hot season. Our results suggested that scleractinian corals in the reef flat and the lagoon were more susceptible to bleaching-level thermal stress than other geomorphic zones. During the cool season, the SST fluctuated markedly among coral reefs and geomorphic zones.

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Lanostane triterpenoids with anti-proliferative and PTP1B/α-glucosidase inhibitory activities from the fruiting bodies of Ganoderma calidophilum - Li Yang; Ting-Ting Zhang; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Jia-Ju Lu; Zhi-Fang Yu; Hao-Fu Dai; You-Xing Zhao (Phytochemistry, 2023)

Numerical simulation of flow instability induced by a fixed cylinder placed near a plane wall in oscillating flow - Zi-Fang Li; Jiang-Hua Li; Jian-Zhao Wu; Kai-Leong Chong; Bo-Fu Wang; Quan Zhou; Yu-Lu Liu (Ocean Engineering, 2023)

Mineralogy, petrology and P-T conditions of the spodumene pegmatites and surrounding meta-sediments in Lhozhag, eastern Himalaya - Jia-Min Wang; Kang-Shi Hou; Lei Yang; Xiao-Chi Liu; Ru-Cheng Wang; Guang-Ming Li; Jian-Gang Fu; Fang-Yang Hu; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2023)

Source control on the acid mine drainage produced by the oxidation of pyrite and sulfur-containing uranium tailings based on the microbially induced carbonate precipitation technology - Yao Zhang; Qi Fang; Junwen Lv; Yukui Fu; Jiahua Zhu; Guojian Peng; Mi Li; Xiaoyan Wu; Hongqiang Wang; Zhenyu Chen (Journal of Cleaner Production, 2023)

Polyphenols modulate microalgae metabolism with a particular increment in lipid accumulation - Li-Gong Zou; Dan-Lin Zheng; Yi-Tong Yao; Fu-Fang Wen; Da-Wei Li; Yu-Feng Yang; Wei-Dong Yang; Srinivasan Balamurugan; Hang Fai Kwok; Hong-Ye Li (Fuel, 2023)

Centrifugation forced ice-concentrate separation to enhance suspension freezing desalination performance - Jingyu Wei; Peng Chen; Yalin Pan; Zhengnan Fang; Tao Fu; Jingxian Zhang; Guangyuan Meng; Jun Zhu; Lehua Zhang (Desalination, 2023)

Fucoxanthin from marine microalgae: A promising bioactive compound for industrial production and food application - Han Sun; Shufang Yang; Weiyang Zhao; Qing Kong; Changliang Zhu; Xiaodan Fu; Fang Zhang; Zhemin Liu; Yuming Zhan; Haijin Mou; Yongjin He (Critical Reviews in Food Science and Nutrition, 2023)

Fruit detachment force of multiple varieties kiwifruit with different fruit-stem angles for designing universal robotic picking end-effector - Wentai Fang; Zhenchao Wu; Weiwu Li; Xiaoming Sun; Wulan Mao; Rui Li; Yaqoob Majeed; Longsheng Fu (Computers and Electronics in Agriculture, 2023)

Structure-diversified terpenoids from Salvia prattii and their protective activity against alcoholic liver diseases - Xiu-wen Yin; Xiang-xiang Bian; Yan-fang Chen; Ming Zhang; Lan Wu; Fu-cai Ren; Fu-rong Yang; Xiang-dong Pu; Bing-yuan Yang; Chuan-pu Shen (Phytochemistry, 2023)

Magnetic biochar/quaternary phosphonium salt reduced antibiotic resistome and pathobiome on pakchoi leaves - Zhi Mei; Yuhao Fu; Fang Wang; Leilei Xiang; Fang Hu; Jean Damascene Harindintwali; Mingyi Wang; Marko Virta; Syed A. Hashsham; Xin Jiang; James M. Tiedje (Journal of Hazardous Materials, 2023)

Potential use of gluten hydrolysate as a plasticizer in high-moisture soy protein–gluten extrudates - Zhaojun Wang; Yan Ji; Liwei Fu; Hongyang Pan; Zhiyong He; Maomao Zeng; Fang Qin; Jie Chen (Journal of Food Engineering, 2023)

The effect of glycerol additive on high value-added chemicals from tobacco waste pyrolysis - Jia-hao Wang; Xian-jie Zhang; Qian Xia; Shui yang Fang; An-fu Hu; Jun Wen; Sheng-jun Zhou; Wen-xian Chen; Gui-lin Zhuang (Journal of Environmental Chemical Engineering, 2023)

Occurrence and carcinogenic risk assessment of N-nitrosamines in some dried aquatic products in China - Siting Huang; Wusheng Fu; Qinmei Fang; Lei Ni; Renjin Zheng; Ling Yong; Zheng Huang; Jie Pang; Zhong Lin; Honglin Lin; Rongde Dai (Food Control, 2023)

Impact of wild fish faeces to deep sea dissolved organic carbon as revealed by laboratory incubations - Zhuo-Yi Zhu; Fu-Tao Fang; Shipan Hossen; Yuan Zhao; Zuo-Zhi Chen; Cong Zeng; Meng Zhou (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Influences of humic acids released during sludge thermal hydrolysis on anaerobic digestion: New insights from enzymatic perspectives - Fang Huang; Hongbo Liu; Jiaxin Wen; Shan Huang; Zhiyong Zheng; Xuedong Zhang; Bo Fu; Yajie Li; Aijie Wang; He Liu (Chemical Engineering Journal, 2023)

Triplet chromophoric dissolved organic matter regulating the phototransformation and toxicity of imidacloprid in paddy water - Yu Zeng; Qinglong Fu; Dionysios D. Dionysiou; Mingyang Zhang; Mabo Li; Bo Ye; Ning Chen; Juan Gao; Yujun Wang; Dongmei Zhou; Guodong Fang (Chemical Engineering Journal, 2023)

Peroxymonosulfate based in situ chemical oxidation: An efficient strategy for mitigation of membrane fouling in real seawater reverse osmosis desalination - Yu Hou; Huangsheng Yang; Qi Fu; Jiaxing Yu; Huajie Zhong; Wei Lin; Junhui Wang; Jingyun Fang; Fang Zhu; Gangfeng Ouyang (Chemical Engineering Journal, 2023)

Multiple Dimensions of using Mesenchymal Stem Cells for Treating Liver Diseases: From Bench to Beside - Lijun Chen; Ning Zhang; Yuqi Huang; Qi Zhang; Yangxin Fang; Jiamin Fu; Yin Yuan; Lu Chen; Xin Chen; Zhenyu Xu; Yifei Li; Hiromi Izawa; et al. (Stem Cell Reviews and Reports, 2023)

RIPF-Unet for regional landslides detection: a novel deep learning model boosted by reversed image pyramid features - Bangjie Fu; Yange Li; Zheng Han; Zhenxiong Fang; Ningsheng Chen; Guisheng Hu; Weidong Wang (Natural Hazards, 2023)

The therapeutic value of adipose-derived pericyte transplantation after intracerebral hemorrhage in rats - Xin Zhang; Ying Zhou; Qiongxia Liu; Fang Wang; Lin Fu; Yizhi Wei; Yuanliang Ye; Yujie Guo (Journal of Molecular Histology, 2023)

Factors Controlling the Pore Development of Low-Mature Marine–Continental Transitional Shale: A Case Study of the Upper Permian Longtan Shale, Western Guizhou, South China - Manting Zhang; Mingyi Hu; Sile Wei; Quansheng Cai; Wei Fu; Fang Shi; Lei Zhang; Haiyan Ding (Journal of Marine Science and Engineering, 2023)
The Upper Permian Longtan Shale is a significant reservoir in western Guizhou. To clarify the main factors controlling the low-mature marine–continental transitional shale pore development in western Guizhou, pore types were classified with scanning electron microscopy (SEM), and the pore developmental stages and morphological structures were quantitatively characterized by nitrogen adsorption isotherm analyses. Additionally, the qualitative or semi-quantitative relationships between the pore developmental stages and the main controlling factors were established via geochemical analysis. The results showed that the Longtan Shale pores include intergranular pores, intragranular pores, organic pores, and microfractures. The intergranular pore structures were categorized into ink-bottle, slit, layered, and irregular types. The intragranular pores were found to be of the elliptical, nearly circular, ink-bottle, and irregular varieties. The organic pores were categorized into elliptical, bubble-like, and irregular polygonal variants. The microfractures were only of the elongated type. The clay-mineral-related intergranular pores were the predominant pore type. The organic pores were found to be poorly developed. The mesopores were predominant, followed by macropores. The shale pore diameters ranged between 1 nm and 100 nm, and they are characterized by multiple peaks. The specific surface area (SSA) was primarily provided by nanopores in the range of 5 nm to 10 nm, such that the smaller pores provided a greater contribution to the SSA, and they are more conducive to shale gas adsorption and accumulation. Clay mineral content was the dominant internal factor controlling pore development and the SSA, with the illite–smectite mixed layer being the most obvious controlling factor. While too low or too high clay mineral content is adverse to macropore development, brittle mineral content, carbonate mineral content, and total organic carbon (TOC) content are adverse to pore development and the SSA. Thermal maturity has no remarkable control effect on pore volume and the SSA of non-organic pores.

Bisphenol P and bisphenol M promote triple-negative breast cancer metastasis through activation of AKT pathways - Jinmi Liu; Haiping Wang; Xiaoying Hou; Limei Fan; Fang Yang; Yuhang Dai; Yufei Deng; Zhengqi Fu; Xiji Shu; Binlian Sun; Yuchen Liu (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Tracing surface water pollution in China’s supply chain - Siao Sun; Megan Konar; Qiuhong Tang; Guangtao Fu; Chuanglin Fang; Jing Wang; Yong Ni; Ting Ma (Journal of Hydrology, 2023)

Laboratory tidal microcosm deciphers responses of sediment archaeal and bacterial communities to microplastic exposure - Chang Fang; Yinglin He; Yuting Yang; Bing Fu; Sentao Pan; Fang Jiao; Jun Wang; Huirong Yang (Journal of Hazardous Materials, 2023)

Maternal di-(2-ethylhexyl) phthalate exposure elicits offspring IFN-λ upregulation: Insights from birth cohort, murine model, and in vitro mechanistic analysis - Fu-Chen Kuo; Mei-Lan Tsai; Shin-Ting Wu; Sih-Syuan Li; Chia-Fang Wu; Shu-Lin Wang; Michael W.Y. Chan; Jau-Ling Suen; Ming-Tsang Wu; Chih-Hsing Hung (Food and Chemical Toxicology, 2023)

Climatic effect from oyster reef restoration in Spartina alterniflora invaded intertidal mudflat: From the perspective of CH4 and N2O production - Wenjing Fu; Xiaoke Pang; Yifan Zhao; Chenglong Han; Yufei Liu; Xue Yu; Jianfeng Feng; Jing Fang; Bo Zhang; Xueqiang Lu (Estuarine, Coastal and Shelf Science, 2023)

Energy-oriented control retrofit for existing HVAC system adopting data-driven MPC – Methodology, implementation and field test - Bao Yue; Bing Su; Fu Xiao; Anbang Li; Kehua Li; Shen Li; Rui Yan; Qiuzhuang Lian; Ao Li; Yuanyang Li; Xing Fang; Xingang Liang (Energy and Buildings, 2023)

Magnesium–oxygen isotope constraints on the origin of rodingites in oceanic lithosphere - Mei-Shan Zhao; Yi-Xiang Chen; Jia-Wei Xiong; Xin-Yue Qiao; Yong-Fei Zheng; Wen-Yong Duan; Fang Huang; Zi-Fu Zhao (Chemical Geology, 2023)

A high-resolution inventory of ammonia emissions from agricultural fertilizer application and crop residue in Taiwan - Chia-Hua Hsu; Fang-Yi Cheng; Chi-Ling Chen; Dong-Hong Wu; Tzu-Ying Chen; Kuo-Fu Liao; Wen-Lung Lay; Yi-Ting Zhang (Atmospheric Environment, 2023)

Systemic lupus erythematosus with high disease activity identification based on machine learning - Da-Cheng Wang; Wang-Dong Xu; Zhen Qin; Lu Fu; You-Yu Lan; Xiao-Yan Liu; An-Fang Huang (Inflammation Research, 2023)

mTORC1/rpS6 and mTORC2/PKC regulate spermatogenesis through Arp3-mediated actin microfilament organization in Eriocheir sinensis - Zhen-Fang Li; Hong-Yu Qi; Jia-Ming Wang; Zhan Zhao; Fu-Qing Tan; Wan-Xi Yang (Cell and Tissue Research, 2023)

Effects of different shelters on feeding, molting, survival, and growth of Scylla paramamosain - Dongping Zhou; Lei Liu; Xinlian Huang; Wei Fang; Yuanyuan Fu; Yuquan Li; Chunlin Wang (Frontiers in Marine Science, 2023)
Providing shelters is considered an effective method to prevent self-harm and improve the survival rate of Scylla paramamosain . In this study, four shelter groups—the shelters of which included fine sand, arched tiles, PVC pipes, and trapezoidal net cages—and one group without shelters were established to investigate the effects of shelters on S. paramamosain by calculating their feeding rate, molting rate, survival rate, and growth index. The results showed that the feeding rates of the fine sand and PVC pipe groups were greater than 12% and that the feeding rates of the arched tile and trapezoidal net cage groups were greater than 9%, while the feeding rate of the group without shelters was only 6.7%. The food conversion rates of both the fine sand and PVC pipe groups exceeded 21%. In contrast, the food conversion rate of the non-shelter group was the lowest at 14%. The molting rates of the fine sand and PVC pipe groups were the highest, reaching 29% in the later stages of the experiment, while the molting rate of the non-shelter group was only 19%. There was no significant difference in survival rates among the groups during the first 20 days of the experiment. However, on the 60th day, the survival rate of the fine sand group was 92%, while the non-shelter group had a survival rate of 79%. The experimental results showed that the incidence of cheliped injuries in the fine sand group was 16%, while it was 25% in the non-shelter group. During the daytime, the occupancy rate of burrows by the four shelter groups was 60–70%, while during the night, the occupancy rate of each shelter decreased to 40–50%, and there was no significant difference in occupancy rates among the shelter groups during the night. The weight and full carapace width of S. paramamosain in the fine sand and PVC pipe groups were significantly higher than those in the other groups ( P< 0.05), and the weight gain rate and specific growth rate of the fine sand and PVC pipe groups were significantly higher than those of the other groups ( P < 0.05). Research has shown that fine sand and PVC pipes, as shelters for S. paramamosain , can effectively prevent cannibalism, increase feeding rates and survival rates, and promote growth and molting. This study provides scientific guidance for the proper selection of shelters in the farming process of S. paramamosain .

Production of single-crystal Cu plates by electrodeposition on high-index Cu foils - Xingguang Li; Zhihong Zhang; Zhibin Zhang; Jinzong Kou; Muhong Wu; Mengze Zhao; Ruixi Qiao; Zhiqiang Ding; Zhiqiang Zhang; Fang Liu; Xiaonan Yang; Dingxin Zou; et al. (Science Bulletin, 2023)

Efficient lipid synthesis of Chlorella pyrenoidosa promoted under heavy metals from electric arc furnace slag - Qing Yu; Tian-Ji Liu; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Yu-Ran Wang; Le-Le Kang; Rui Ji; Fu-Ping Wang; Xiao-Man Wang; Bao Liu; Shuang Cai; et al. (Journal of Cleaner Production, 2023)

High-moisture extrusion of soy protein: Effects of insoluble dietary fiber on anisotropic extrudates - Qian Deng; Zhaojun Wang; Liwei Fu; Zhiyong He; Maomao Zeng; Fang Qin; Jie Chen (Food Hydrocolloids, 2023)

TiO2 nanoparticles affect spermatogenesis and adhesion junctions via the ROS-mediated mTOR signalling pathway in Eriocheir sinensis testes - Lan-Min Wang; Ke Jia; Zhen-Fang Li; Hong-Yu Qi; Ding-Xi Liu; Ya-Jing Liang; Shuang-Li Hao; Fu-Qing Tan; Wan-Xi Yang (Environmental Pollution, 2023)

Antibiotic resistance genes in food production systems support One Health opinions - James M. Tiedje; Yuhao Fu; Zhi Mei; Andreas Schäffer; Qingyuan Dou; Wulf Amelung; Martin Elsner; Joseph Adu-Gyamfi; Lee Heng; Marko Virta; Xin Jiang; Hauke Smidt; et al. (Current Opinion in Environmental Science & Health, 2023)

Graph neural network-based spatio-temporal indoor environment prediction and optimal control for central air-conditioning systems - Jing Zhang; Fu Xiao; Ao Li; Tianyou Ma; Kan Xu; Hanbei Zhang; Rui Yan; Xing Fang; Yuanyang Li; Dan Wang (Building and Environment, 2023)

Microecological health assessment of water environment and sediment based on metagenomics: a case study of Guixi River in Chongqing, China - Xia Su; Fu-qing Xu; Shang-jie Chen; Fang Gou; Yun-chun Shi; Zhi-lin Xing; Ren-qing Peng; Ying-ying Deng; Ten Zhang; Juan Xiong; Tian-tao Zhao (Environmental Monitoring and Assessment, 2023)

Inhibition of sediment erosion and phosphorus release by remediation strategy of contaminated sediment backfilling - Xiaocui Li; Lei Huang; Danny Reible; Xiong Zeng; Siwen Liu; Jiahao Fu; Kai Wang; Hongwei Fang (Water Research, 2023)

Effects of ball milling on biochar adsorption of contaminants in water: A meta-analysis - Jean Damascene Harindintwali; Chao He; Leilei Xiang; Qingyuan Dou; Yu Liu; Mingyi Wang; Xin Wen; Yuhao Fu; Mahbub Ul Islam; Scott X. Chang; Stephan Kueppers; Sabry M. Shaheen; et al. (Science of The Total Environment, 2023)

AraENCODE: A comprehensive epigenomic database of Arabidopsis thaliana - Zhenji Wang; Minghao Liu; Fuming Lai; Qiangqiang Fu; Liang Xie; Yaping Fang; Qiangwei Zhou; Guoliang Li (Molecular Plant, 2023)

Barium isotope behavior during interaction between serpentinite-derived fluids and metamorphic rocks in the continental subduction zone - Anxia Chen; Yi-Xiang Chen; Xiaofeng Gu; Zhen Zeng; Zicong Xiao; Hans-Peter Schertl; Xiqiu Han; Zi-Fu Zhao; Fang Huang (Geochimica et Cosmochimica Acta, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Loss of TRIM24 promotes IL-10 expression via CBP/p300-dependent IFNβ1 transcription during macrophage activation - Zhaoyuan Hui; Yuanzheng Fu; Yunyun Chen; Jie Yin; Hui Fang; Yifan Tu; Ying Gu; Jiawei Zhang (Inflammation Research, 2023)

Thin wire segmentation and reconstruction based on a novel image overlap-partitioning and stitching algorithm in apple fruiting wall architecture for robotic picking - Hanhui Jiang; Xiaoming Sun; Wentai Fang; Longsheng Fu; Rui Li; Fernando Auat Cheein; Yaqoob Majeed (Computers and Electronics in Agriculture, 2023)

Unraveling the structure and function of bacterioferritin in Candidatus Kuenenia stuttgartiensis: Iron storage sites maintain cellular iron homeostasis - Jin Wang; Que Wang; Yu-Jiao Tang; Hui-Min Fu; Fang Fang; Jin-Song Guo; Peng Yan; You-Peng Chen (Water Research, 2023)

Volatile fatty acid production in anaerobic fermentation of food waste saccharified residue: Effect of substrate concentration - Qingyan Wang; Guangming Zhang; Le Chen; Nan Yang; Yan Wu; Wei Fang; Ru Zhang; Xinyi Wang; Chuan Fu; Panyue Zhang (Waste Management, 2023)

Controlling Dzyaloshinskii-Moriya interaction in a centrosymmetric nonsymmorphic crystal - Zhongyi Zhang; Shengshan Qin; Jiadong Zang; Chen Fang; Jiangping Hu; Fu-Chun Zhang (Science Bulletin, 2023)

Mechanistic insights into the migration behavior of cadmium (Cd) in the soil and groundwater systems at a construction site: Experimental and numerical analysis - Da–Mao Xu; Ze–Lin Xu; Zi–Qi Mu; Bai–Hong An; Xiao–Wen Fang; Rong–Bing Fu (Journal of Environmental Chemical Engineering, 2023)

Molybdenum isotopes record recycling of subducting sediment in active continental margin, Northeast China - Wei Fang; Li-Qun Dai; Xiang Fu; Zi-Fu Zhao; Bing Gong; Yong-Fei Zheng (Chemical Geology, 2023)

Genome-wide Association Study of Root Hair Length in Maize - Li Xuhui; Lu Siqi; Chen Weiwei; Zhu Hang; Lin Huanzhang; Fu Danwen; Fan Lina; Fang Junteng; Hu Yuanqiang; Zhang Xiangbo; Chang Hailong; Qi Yongwen (Tropical Plant Biology, 2023)

Fine mapping and genetic analysis identified a C2H2-type zinc finger as a candidate gene for heading date regulation in wheat - Yuting Li; Hongchun Xiong; Huijun Guo; Chunyun Zhou; Meiyu Fu; Yongdun Xie; Linshu Zhao; Jiayu Gu; Shirong Zhao; Yuping Ding; Chaojie Wang; Ahsan Irshad; et al. (Theoretical and Applied Genetics, 2023)

Leaky Gut Plays a Critical Role in the Pathophysiology of Autism in Mice by Activating the Lipopolysaccharide-Mediated Toll-Like Receptor 4–Myeloid Differentiation Factor 88–Nuclear Factor Kappa B Signaling Pathway - Fang Li; Haoran Ke; Siqi Wang; Wei Mao; Cexiong Fu; Xi Chen; Qingqing Fu; Xiaori Qin; Yonghua Huang; Bidan Li; Shibing Li; Jingying Xing; et al. (Neuroscience Bulletin, 2023)
Increased intestinal barrier permeability, leaky gut, has been reported in patients with autism. However, its contribution to the development of autism has not been determined. We selected dextran sulfate sodium (DSS) to disrupt and metformin to repair the intestinal barrier in BTBR T + tf/J autistic mice to test this hypothesis. DSS treatment resulted in a decreased affinity for social proximity; however, autistic behaviors in mice were improved after the administration of metformin. We found an increased affinity for social proximity/social memory and decreased repetitive and anxiety-related behaviors. The concentration of lipopolysaccharides in blood decreased after the administration of metformin. The expression levels of the key molecules in the toll-like receptor 4 (TLR4)–myeloid differentiation factor 88 (MyD88)–nuclear factor kappa B (NF-κB) pathway and their downstream inflammatory cytokines in the cerebral cortex were both repressed. Thus, “leaky gut” could be a trigger for the development of autism via activation of the lipopolysaccharide-mediated TLR4–MyD88–NF-κB pathway.

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

Lupus nephritis or not? A simple and clinically friendly machine learning pipeline to help diagnosis of lupus nephritis - Da-Cheng Wang; Wang-Dong Xu; Shen-Nan Wang; Xiang Wang; Wei Leng; Lu Fu; Xiao-Yan Liu; Zhen Qin; An-Fang Huang (Inflammation Research, 2023)

Prenatal diagnosis in the fetal hyperechogenic kidneys: assessment using chromosomal microarray analysis and exome sequencing - Ruibin Huang; Fang Fu; Hang Zhou; Lu Zhang; Tingying Lei; Ken Cheng; Shujuan Yan; Fei Guo; You Wang; Chunling Ma; Ru Li; Qiuxia Yu; et al. (Human Genetics, 2023)

Study on Geomechanical and Physical Models of Necking-Type Slopes - Kun Fang; Huiming Tang; Jichen Zhu; Zijin Fu; Pengju An; Bocheng Zhang; Chunyan Tang (Journal of Earth Science, 2023)

Relationship between bisphenol A and the cardiovascular disease metabolic risk factors in American adults: A population-based study - Mingcong Chen; Yang Yang; Krishna Baral; Yicheng Fu; Yang Meng; Yang Zhang; Fang Sun; Mingyi Zhao (Chemosphere, 2023)

A 209,000-year-old history of methane seepage activity controlled by multiple factors in the South China Sea - Ganglan Zhang; Jun Cao; Yinan Deng; Hongfei Lai; Xuexiao Jiang; Yunxin Fang; Zenggui Kuang; Shengxiong Yang; Qianyong Liang; Piaoer Fu; Tiantian Sun; Meng Jin; et al. (Marine and Petroleum Geology, 2023)

A pH-responsive fluorescent nanopesticide for selective delivery and visualization in pine wood nematode control - Wei Gan; Xiangbo Kong; Jiaxing Fang; Xia Shi; Sufang Zhang; Yongxia Li; Liangjian Qu; Fu Liu; Zhen Zhang; Fengbi Zhang; Xingyao Zhang (Chemical Engineering Journal, 2023)

Occurrence and ecological risk assessment of 16 phthalates in surface water of the mainstream of the Yangtze River, China - Jia-Nan Ren; Ning-Zheng Zhu; Xiang-Zhou Meng; Chong-Jing Gao; Kai Li; Li-Min Jin; Ting-Ting Shang; Fang-Ting Ai; Ming-Hong Cai; Jian-Fu Zhao (Environmental Science and Pollution Research, 2023)

EchoAI: A deep-learning based model for classification of echinoderms in global oceans - Zhinuo Zhou; Ge-Yi Fu; Yi Fang; Ye Yuan; Hong-Bin Shen; Chun-Sheng Wang; Xue-Wei Xu; Peng Zhou; Xiaoyong Pan (Frontiers in Marine Science, 2023)
Introduction In response to the need for automated classification in global marine biological studies, deep learning is applied to image-based classification of marine echinoderms. Methods Images of marine echinoderms are collected and classified according to their systematic taxonomy. The images belong to 5 classes, 38 orders, 145 families, 459 genera, and 1021 species, respectively. The deep learning model, EfficientNetV2, outperforms the competing model and is chosen for developing the automated classification tool, EchoAI. Then, the EfficientNetV2-based tool, EchoAI is applied to each taxonomic level. Results The accuracy for the test dataset was 0.980 (class), 0.876 (order), 0.738 (family), 0.612 (genus), and 0.469 (species), respectively. Online prediction service is provided. Discussion The EchoAI model and results are facilitated for investigating the diversity, abundance and distribution of species at the global scale, and the methodological strategy can also be applied to image classification of other categories of marine organisms, which is of great significance for global marine studies. EchoAI is freely available at http://www.csbio.sjtu.edu.cn/bioinf/EchoAI/ for academic use.

A novel pollination robot for kiwifruit flower based on preferential flowers selection and precisely target - Changqing Gao; Leilei He; Wentai Fang; Zhenchao Wu; Hanhui Jiang; Rui Li; Longsheng Fu (Computers and Electronics in Agriculture, 2023)

Molecular insights into enhanced nitrogen removal induced by trace fluoroquinolone antibiotics in an anammox system - Xuejiao Qiao; Chenkun Fu; Yizhen Chen; Fang Fang; Yaoyu Zhang; Lingyun Ding; Kai Yang; Baozhu Pan; Nan Xu; Ke Yu; Huchun Tao; Lijuan Zhang (Bioresource Technology, 2023)

Composition, Distribution, and Source Apportionment of Organochlorine Pesticides (OCPs) in Soil of a Chemical Industrial Park and its Surrounding in the Northeast of Qinghai-Tibet Plateau - Xiaojun Li; Lixia Cao; Xin Lin; Wanlong Fu; Zongqiang Gong; Xiangfeng Zeng; Huajun Fang; Zhiheng Li (Water, Air, & Soil Pollution, 2023)

How do montane plants manage to survive? Inferring from non-structural carbohydrates - Wensheng Chen; Huihui Ding; Jiangrong Li; Fangwei Fu; Yueyao Li; Siying Xiao; Di Xu; Jie Lu; Jiangping Fang (Trees, 2023)

A rapid and sensitive single-cell proteomic method based on fast liquid-chromatography separation, retention time prediction and MS1-only acquisition - Wei Fang; Zhuokun Du; Linlin Kong; Bin Fu; Guibin Wang; Yangjun Zhang; Weijie Qin (Analytica Chimica Acta, 2023)

GSK2795039 prevents RIP1-RIP3-MLKL-mediated cardiomyocyte necroptosis in doxorubicin-induced heart failure through inhibition of NADPH oxidase-derived oxidative stress - Xiao-Juan Zhang; Lu Li; Ai-Ling Wang; Hong-Xia Guo; Hui-Ping Zhao; Rui-Fang Chi; Hui-Yu Xu; Li-Guo Yang; Bao Li; Fu-Zhong Qin; Jia-Pu Wang (Toxicology and Applied Pharmacology, 2023)

Polylactic acid microplastics induce higher biotoxicity of decabromodiphenyl ethane on earthworms (Eisenia fetida) compared to polyethylene and polypropylene microplastics - Yanna Han; Mengru Fu; Jinhong Wu; Shanqi Zhou; Zhihua Qiao; Cheng Peng; Wei Zhang; Fang Liu; Chunmei Ye; Jie Yang (Science of The Total Environment, 2023)

Quantifying and assessing the infiltration potential of green infrastructure in urban areas using a layered hydrological model - Xiaoran Fu; Jiahong Liu; Zhonggen Wang; Dong Wang; Weiwei Shao; Chao Mei; Jia Wang; Yan-fang Sang (Journal of Hydrology, 2023)

Achieving ultrahigh energy storage properties with superior stability in novel (Ba(1-)Bi )(Ti(1-)Zn0.5Sn0.5)O3 relaxor ferroelectric ceramics via chemical modification - Ming Yin; Guang-Jian Bai; Peng Li; Ji-Gong Hao; Wei Li; Wei-Fang Han; Yu-Chao Li; Chun-Ming Wang; Guo-Rong Li; Peng Fu (Chemical Engineering Journal, 2023)

Influence of aerosol physicochemical properties on CCN activation during the Asian winter monsoon at the summit of Mt. Lu, China - Jing Duan; Yong Chen; Xiaopeng Zhang; Wenling Wang; Shujun Zhong; Jun Li; Guangxian Lu; Chungang Fang; Lijun Guo; Pingqing Fu (Atmospheric Environment, 2023)

24-Epibrassinolide Enhances Resistance Against Colletotrichum fructicola by Promoting Lignin Biosynthesis in Camellia sinensis L. - Lan Zhang; Zheng Zhang; Golam Jalal Ahammed; Xiaorong Wang; Huihan Fang; Peng Yan; Li-Ping Zhang; Shibei Ge; Jianyu Fu; Wen-Yan Han; Xin Li (Journal of Plant Growth Regulation, 2023)

Whole exome sequencing improves genetic diagnosis of fetal clubfoot - Ruibin Huang; Hang Zhou; Chunling Ma; Fang Fu; Ken Cheng; You Wang; Ru Li; Tingying Lei; Qiuxia Yu; Dan Wang; Shujuan Yan; Xin Yang; et al. (Human Genetics, 2023)

Hydraulic determinants of drought-induced tree mortality and changes in tree abundance between two tropical forests with different water availability - Yong-Qiang Wang; Hui-Qing Song; Ya-Jun Chen; Pei-Li Fu; Jiao-Lin Zhang; Kun-Fang Cao; Shi-Dan Zhu (Agricultural and Forest Meteorology, 2023)

Nightside 135.6 nm emission enhancements of mid/low latitudes during geomagnetic storms as observed by the ionosphere PhotoMeter (IPM) on the Chinese meteorological satellite FY-3D - Fang Jiang; Tian Mao; XiaoXin Zhang; Li-Ping Fu (Advances in Space Research, 2023)

Occurrence, spatial distribution, and risk assessment of brominated flame retardants in farmland soils of typical provinces in China - Mabinty Sarah Tholley; Lartey Young George; Mengru Fu; Zhihua Qiao; Gehui Wang; Siyuan Ling; Cheng Peng; Wei Zhang; Chunmei Ye; Fang Liu; Jie Yang (Chemosphere, 2023)

Co-hydrothermal carbonization of polyvinyl chloride and lignocellulose biomasses for chlorine and inorganics removal - Jing Zhang; Yuhan Chen; Xu Xia; Binbin Fu; Chuanjin Lin; Guangchao Jia; Xin Cui; Fang Liu; Peitao Zhao; Yimin Li (Waste Management, 2023)

Overlooked roles of Cl2O and Cl2 in micropollutant abatement and DBP formation by chlorination - Xin Yang; Anna Wang; Zhechao Hua; Wenrui Wei; Yilong Cao; Bingyue Fu; Shuping Chen; Zijun Dong; Jingyun Fang (Water Research, 2023)

Water transfer infrastructure buffers water scarcity risks to supply chains - Siao Sun; Qiuhong Tang; Megan Konar; Chuanglin Fang; Haixing Liu; Xingcai Liu; Guangtao Fu (Water Research, 2023)

Chlorpyrifos induces neuronal cell death via both oxidative stress and Akt activation downstream-regulated CHOP-triggered apoptotic pathways - Jhe-Wei Lin; Shih-Chang Fu; Jui-Ming Liu; Shing-Hwa Liu; Kuan-I Lee; Kai-Min Fang; Ren-Jun Hsu; Chun-Fa Huang; Kun-Min Liu; Kai-Chih Chang; Chin-Chuan Su; Ya-Wen Chen (Toxicology in Vitro, 2023)

PFAS-induced lipidomic dysregulations and their associations with developmental toxicity in zebrafish embryos - Zhiyi Yang; Lei Fu; Mengxi Cao; Fang Li; Jingguang Li; Zhiyu Chen; Ang Guo; Huifang Zhong; Wenbo Li; Yong Liang; Qian Luo (Science of The Total Environment, 2023)

Distinct contribution of aqueous solutions and hydrous melts to the mantle sources: Geochemical evidence from Late Paleozoic igneous rocks in Southwestern Tianshan, Western China - Li-Tao Ma; Li-Qun Dai; Zi-Fu Zhao; Fang Huang; Bing Gong (Lithos, 2023)

Potassium isotope fractionation during granitic magmatic differentiation: Mineral-pair perspectives - Tian-Yi Huang; Fang-Zhen Teng; Ze-Zhou Wang; Yong-Sheng He; Zhi-Chao Liu; Fu-Yuan Wu (Geochimica et Cosmochimica Acta, 2023)

Integrated untargeted metabolome, full-length sequencing, and transcriptome analyses reveal insights into the fruit quality at different harvest times of Chaenomeles speciosa - Qingying Fang; Han Zheng; Guosheng Fu; Minzhen Yin; Lu Jiang; Yujiao Zhao; Liangping Zha; Shanshan Chu; Huasheng Peng; Luqi Huang (Food Research International, 2023)

Improving ACE inhibitory activity of hazelnut peptide modified by plastein: Physicochemical properties and action mechanism - Wentian Song; Junxi Fu; Qi Zeng; Hongyan Lu; Ji Wang; Li Fang; Xiaoting Liu; Weihong Min; Chunlei Liu (Food Chemistry, 2023)

Single and combined toxicity assessment of primary or UV-aged microplastics and adsorbed organic pollutants on microalga Chlorella pyrenoidosa - Wei Song; Caixia Fu; Yuning Fang; Zhuoyue Wang; Ji Li; Xiaolei Zhang; Kalpana Bhatt; Lu Liu; Ningjie Wang; Fang Liu; Shunni Zhu (Environmental Pollution, 2023)

Interface engineering of hybrid ZnCo2O4@Ni2.5Mo6S6.7 structures for flexible energy storage and alkaline water splitting - Wen-Duo Yang; Rong-Da Zhao; Fang-Yu Guo; Jun Xiang; Sroeurb Loy; Liang Liu; Jia-Yu Dai; Fu-Fa Wu (Chemical Engineering Journal, 2023)

Tailored chemically bonded metal phosphide@carbon nanowire arrays on foam metal as an all-in-one anode for ultrahigh-area-capacity sodium-ion batteries - Yuyan Qiu; Fang Fu; Miao Hu; Pei Kang Shen; Jinliang Zhu (Chemical Engineering Journal, 2023)

Low 15d-PGJ2 status is associated with oxidative stress in chronic obstructive pulmonary disease patients - Shi-Xue Ma; Guo-Fang Xie; Pu Fang; Min-Min Tang; You-Peng Deng; Yu-Jin Lu; Wei Cao; Lin Fu (Inflammation Research, 2023)

Effects of Soil Hydraulic Properties on Soil Moisture Estimation - Xiaolei Fu; Haishen Lyu; Zhongbo Yu; Xiaolei Jiang; Yongjian Ding; Donghai Zheng; Jinbai Huang; Hongyuan Fang (Journal of Meteorological Research, 2023)

Antiherbivore effect of Cuscuta campestris against Spodoptera frugiperda - Chang-Lin Sung; Fang-Yu Hu; Yi Li; Shin-Fu Tsai; Wen-Po Chuang (Arthropod-Plant Interactions, 2023)

Personalizing atomoxetine dosing in children with ADHD: what can we learn from current supporting evidence - Di Fu; Hong-Li Guo; Ya-Hui Hu; Wei-Rong Fang; Qian-Qi Liu; Jing Xu; Dan-Dan Wu; Feng Chen (European Journal of Clinical Pharmacology, 2023)

Water microecology is affected by seasons but not sediments: A spatiotemporal dynamics survey of bacterial community composition in Lake Changshou—The largest artificial lake in southwest China - Ai-ling Chen; Fu-qing Xu; Xia Su; Fu-pan Zhang; Wan-chao Tian; Shang-jie Chen; Fang Gou; Zhi-lin Xing; Jin-xin Xiang; Juan Li; Tian-tao Zhao (Marine Pollution Bulletin, 2023)

Hypoxia alters glucose and lipid metabolisms in golden pompano (Trachinotus blochii) - Tian Jiang; Jun Long Sun; Yue Gu; Fu Cheng Yao; Ye Song Liang; Yi Fan Liu; Kai Xi Zhang; Fei Biao Song; Li Zhou; Zhong Wei Wang; Jian Fang Gui; Jian Luo (Aquaculture, 2023)

The distinct resistance mechanisms of cyanobacteria and green algae to sulfamethoxazole and its implications for environmental risk assessment - Yibo Zhang; Ming Li; Fang Chang; Malan Yi; Hongmei Ge; Jie Fu; Chenyuan Dang (Science of The Total Environment, 2023)

The growth-regulating factor PdbGRF1 positively regulates the salt stress response in Populus davidiana × P. bolleana - Zhong-Yuan Liu; Ya-Ting Han; Chun-Yao Wang; Xiao-Jin Lei; Yuan-Yuan Wang; Wen-Fang Dong; Qing-Jun Xie; Yu-Jie Fu; Cai-Qiu Gao (Plant Science, 2023)

Insight into photo-fenton catalytic degradation of tetracycline by environmental friendly nanocomposite 1T-2H hybrid phases MoS2/Fe3O4/g-C3N4 - Rongchao Yang; Guangzhu Zhou; Cuizhen Wang; Yin Liu; Yanyun Zhao; Yinming Li; Xiaoning Fu; Jingyi Chi; Xi Chen; Hui Fang; Zheng Qin (Journal of Cleaner Production, 2023)

Learn then match: A fast coarse-to-fine depth image-based indoor localization framework for dark environments via deep learning and keypoint-based geometry alignment - Qing Li; Rui Cao; Jiasong Zhu; Hao Fu; Baoding Zhou; Xu Fang; Sen Jia; Shenman Zhang; Kanglin Liu; Qingquan Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Influence and economic analysis of heat storage in the non-heating season on the heat extraction capacity of mid-deep borehole heat exchangers - Haiyu Fu; Liang Fang; Mingzhi Yu; Ping Cui; Wenke Zhang; Yudong Mao; Zhaoyi Zhuang; Zhaohong Fang (Energy and Buildings, 2023)

Four-armed host-defense peptidomimetics-augmented vanadium carbide MXene-based microneedle array for efficient photo-excited bacteria-killing - Xiaoqian Feng; Dongyi Xian; Jintao Fu; Rui Luo; Wenhao Wang; Yuwei Zheng; Qing He; Zhan Ouyang; Shaobin Fang; Wancong Zhang; Daojun Liu; Shijie Tang; et al. (Chemical Engineering Journal, 2023)

Efficient inverted CsPbI3 perovskite solar cells fabricated in common air - Chunyan Lu; Xiaodong Li; Xuemin Guo; Sheng Fu; Wenxiao Zhang; Haobo Yuan; Junfeng Fang (Chemical Engineering Journal, 2023)

Doping engineering of carrier transporting layers for ambient-air-stable lead-free rudorffite solar cells prepared by thermal-assisted doctor blade coating - Kai-Chi Hsiao; Yen-Fu Yu; Ching-Mei Ho; Meng-Huan Jao; Yu-Hsiang Chang; Shih-Hsuan Chen; Yin-Hsuan Chang; Wei-Fang Su; Kun-Mu Lee; Ming-Chung Wu (Chemical Engineering Journal, 2023)

Influence of thermal hydrolysis on sludge anaerobic digestion: Release of humic acid promotes electron transport of methanogen - Cheng Zhao; Hongbo Liu; He Liu; Xinmin Zhan; Xuedong Zhang; Bo Fu; Mingze Shi; Shuailing Lu; Fang Huang; Minhua Cui; Yajie Li (Chemical Engineering Journal, 2023)

Storm splitting process and the associated mechanisms for a long-lived hailstorm - Xin Guo; Xueliang Guo; Danhong Fu; Juan Fang (Atmospheric Research, 2023)

Highly efficient removal of hexavalent chromium by magnetic Fe–C composite from reed straw and electric furnace dust waste - Fu-Ping Wang; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Xi Zhang; Ai-Min Ji; Le-Le Kang; Rui Ji; Qing Yu; Di Gao; Xiao-Man Wang; Zhen Fang (Environmental Science and Pollution Research, 2022)

BCI system with lower-limb robot improves rehabilitation in spinal cord injury patients through short-term training: a pilot study - Zhengzhe Cui; Yongqiang Li; Sisi Huang; Xixi Wu; Xiangxiang Fu; Fei Liu; Xiaojiao Wan; Xue Wang; Yuting Zhang; Huaide Qiu; Fang Chen; Peijin Yang; et al. (Cognitive Neurodynamics, 2022)

Evaluating the Effect of Anisotropy on Hydraulic Stimulation in a Slate Geothermal Reservoir - Meng-Chia Weng; Po-Lin Wu; Chih-Hung Fang; Yu-Yao Fu; Yen-Che Liao; Chih-Hsi Liu (Rock Mechanics and Rock Engineering, 2022)

Caffeine alleviates acute liver injury by inducing the expression of NEDD4L and deceasing GRP78 level via ubiquitination - Xing-Wang Hu; Xiang-Min Li; Ai-Min Wang; Yong-Ming Fu; Fang-Jie Zhang; Feng Zeng; Li-Ping Cao; Hui Long; Ying-Hui Xiong; Ji Xu; Jia Li (Inflammation Research, 2022)

mTORC1/C2 regulate spermatogenesis in Eriocheir sinensis via alterations in the actin filament network and cell junctions - Zhen-Fang Li; Shuang-Li Hao; Lan-Min Wang; Hong-Yu Qi; Jia-Ming Wang; Fu-Qing Tan; Wan-Xi Yang (Cell and Tissue Research, 2022)

A histological study of vascular wall resident stem cells in venous malformations - Hou-Fu Xia; Wen-Qiang Lai; Gao-Hong Chen; Ye Li; Qi-Hui Xie; Yu-Lin Jia; Gang Chen; Yi-Fang Zhao (Cell and Tissue Research, 2022)

The combined effect of titanium dioxide nanoparticles and cypermethrin on male reproductive toxicity in rats - Yuxin Li; Mingqing Zhong; Xianzhi He; Ruoyu Zhang; Yu Fu; Ruolan You; Feiyan Tao; Lei Fang; Yuanyuan Li; Qingfeng Zhai (Environmental Science and Pollution Research, 2022)

Evaluation of Port–Hinterland Synergy Level Considering Fixed Asset Allocation and Social Commodity Circulation under the “Dual Circulation” Development Pattern - Zhaohui Li; Yujin Huang; Fan Yang; Yi Li; Yan Fang; Rui Fu (Journal of Marine Science and Engineering, 2022)
“Port–hinterland synergy” means the development of port and hinterland should promote each other. The “dual circulation” development pattern indicates the requirement of exploring the domestic transportation demand and promoting the integration between ports and hinterlands. However, the current research on the synergy level between ports and hinterlands is not enough to meet the needs of constructing a “dual circulation” development pattern, and few studies have explored the influencing factors of port–hinterland synergy level directly, especially in the context of the new development pattern of “dual circulation”. After investigating the synergetic mechanism between ports and hinterlands, this study proposes to further consider the influence of fixed assets allocation and social commodity circulation on the synergy level under the “dual circulation” pattern. So, fixed asset investment and three different forms of commodity circulation activities are selected to represent the corresponding hinterland’s economic activities and added into the evaluation indices. To assess ports’ responsiveness to different kinds of transport demand, throughputs of each port are divided into those of domestic and foreign countries. Then this paper evaluates the level of port–hinterland synergy by the coupling synergy model, and the influence degree of these activities on the synergy level was studied with the partial least squares regression (PLS). The results show that there is heterogeneity in regional and port positioning in the port–hinterland synergy level, and that four selected economic activities’ improvement can enhance the port–hinterland synergy level. Among them, retail industry has the strongest positive effect, followed by tertiary industry, import and export trade, and fixed asset investment.

Spatial variation of heavy metals and their ecological risk and health risks to local residents in a typical e-waste dismantling area of southeastern China - Jia Fang; Luyao Zhang; Shengting Rao; Minghua Zhang; Keli Zhao; Weijun Fu (Environmental Monitoring and Assessment, 2022)

Shaking table test and numerical analysis of single-layer reticulated domes with or without three-dimensional isolation bearing - Gui-Bo Nie; Dong-fang Li; Xu-dong Zhi; Fu-yang Wang; Chen-xiao Zhang (Bulletin of Earthquake Engineering, 2022)

Development of an Escherichia coli whole cell biocatalyst for the production of hyperoside - Guo-Si Li; Fu-Cheng Zhu; Pei-Pei Wei; Fang-Li Gu; Qi-Ling Xu; Meng-Hua Ma (Biotechnology Letters, 2022)

Endothelial cells induce degradation of ECM through enhanced secretion of MMP14 carried on extracellular vesicles in venous malformation - Gao-Hong Chen; Jie-Gang Yang; Hou-Fu Xia; Lin-Zhou Zhang; Yin-Hsueh Chen; Kui-Ming Wang; Xu Duan; Lian-Zhi Wu; Yi-Fang Zhao; Gang Chen (Cell and Tissue Research, 2022)

Deciphering the Heterogeneity of Mitochondrial Functions During Hematopoietic Lineage Differentiation - Haoyue Liang; Shuxu Dong; Weichao Fu; Sen Zhang; Wenying Yu; Fang Dong; Baolin He; Jinhong Wang; Yingdai Gao; Yuan Zhou; Yongxin Ru (Stem Cell Reviews and Reports, 2022)

Taurine supplementation improves hippocampal metabolism in immature rats with intrauterine growth restriction (IUGR) through protecting neurons and reducing gliosis - Qiong Fang; Jing Liu; Lang Chen; Qiaobin Chen; Yan Wang; Zuanfang Li; Wei Fu; Ying Liu (Metabolic Brain Disease, 2022)

The safety degree evaluation of marine biodiversity in China - Xiu-Mei Fu; Wan-Yu Wu; Fang Yang; Shan-Shan Jiang; Shi-Qi Wang; Xiao-Yan Li; Hui-Ying Tang; Ying Liu; Chang-Yun Wang (Journal of Coastal Conservation, 2022)

IL-38, a potential therapeutic agent for lupus, inhibits lupus progression - Wang-Dong Xu; Lin-Chong Su; Lu Fu; You-Yu Lan; Xiao-Yan Liu; Qi Huang; Qian Wu; Jie Zhou; An-Fang Huang (Inflammation Research, 2022)

The activity, segmentation, and evolution characteristics of large-scale landslides along the Anninghe active fault zone, Southwest China - Hongfu Zhou; Fei Ye; Wenxi Fu; Yuting Wei; Yadong Qin; Wenqing Tang; Tian Fang (Bulletin of Engineering Geology and the Environment, 2022)

Reliable reference genes for qPCR normalization in females of the mirid predator, Cyrtorhinus lividipennis (Hemiptera: Miridae) - Kui Hu; Ke Chen; Baobao Fu; Jianqi Liu; Yan Li; Qinjian Pan; Fang Liu (Biologia, 2022)

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

Vertical patterns of chlorophyll a in the euphotic layer are related to mesoscale eddies in the South China Sea - Mei-Lin Wu; You-Shao Wang; Yu-Tu Wang; Fu-Lin Sun; Xiaomei Li; Fang-Fang Gu; Jing-Chang Xiang (Frontiers in Marine Science, 2022)
Phytoplankton closely connects with the hydrodynamics and biogeochemical environment of the ocean. While research focusing on both the physiochemical factors and hydrodynamics regulating phytoplankton has already been conducted, the coupling mechanism between mesoscale eddies and the vertical distribution of phyto plankton in the South China Sea (SCS) is still not well understood. Here, phytoplankton was studied under one weak-cold and two warm eddies along the 18°N transect in the SCS. The results show that the vertical distribution of chlorophyll (chl- a ) presented a similar pattern at all four sampling stations. The mixed layer is less than 50 m. It is the same as the meridional salinity gradients that may be distinguished above a depth of 60 m. The subsurface chlorophyll maximum at the edge of a warm (WI) and cold eddy (CI) at E413 and E411 was shallower than that at the edge of a warm eddy (WII) at E407 and E409, indicating that temperature and salinity may be the important driving factors. On the whole, mesoscale eddies had a significant influence on the vertical pattern of chl- a in the SCS during the study period.

Lipofundin mediates major inhibition of intravenous propofol on phorbol myristate acetate and Escherichia coli-induced neutrophil extracellular traps - Ming-Shan Chen; Kung-Ssu Yang; Wen-Chun Lin; Chien-Liang Fang; Hsin-Fu Chen; Shew-Meei Sheu (Molecular Biology Reports, 2022)

PPARγ Dysfunction in the Medial Prefrontal Cortex Mediates High-Fat Diet-Induced Depression - Cong-Cong Fu; Xin-Yi Zhang; Liu Xu; Hui-Xian Huang; Shuang Xu; Qiao-Qi Wu; Zhen Wang; Xi Gu; Li-Fang Lin; Song Lin; Ying-Ying Fang; Xiong Cao; et al. (Molecular Neurobiology, 2022)

Selective serotonin reuptake inhibitor use and the risk of hepatocellular carcinoma - Shih-Wei Lai; Bing-Fang Hwang; Chiu-Shong Liu; Kuan-Fu Liao (European Journal of Clinical Pharmacology, 2022)

RETRACTED ARTICLE: Changes in ecological networks and eco-environmental effects on urban ecosystem in China’s typical urban agglomerations - Ying Fang; Jing Wang; Shihang Fu; Tianlin Zhai; Longyang Huang (Environmental Science and Pollution Research, 2022)

An ortholog of the MADS-box gene SEPALLATA3 regulates stamen development in the woody plant Jatropha curcas - Mei-Li Zhao; Zhi-Fang Zhou; Mao-Sheng Chen; Chuan-Jia Xu; Zeng-Fu Xu (Planta, 2022)

Community Competition Is the Microorganism Feedback to Sedimentary Carbon Degradation Process in Aquaculture Tidal Flats - Min Zhou; Fu-Tao Fang; Cong Zeng; Li-Hong Zhang; Cheng-Xu Zhou; Zhuo-Yi Zhu (Frontiers in Marine Science, 2022)
How the microbial community response to carbon degradation is unclear, while it plays an essential role in predicting microbial community shift and determining carbon cycling. Surface sediments in two contrasting aquacultural tidal flat sites in Fujian Province, China, were collected in October, 2020. In addition to 16s rRNA gene high-throughput sequencing for determining bacteria and archaea biodiversity, an amino acids-based molecular degradation index DI was used to quantify the carbon degradation status. The results revealed that the microorganism response to DI at the family level was community competition. Specifically, the winning microbes that grew under carbon degradation (i.e., operational taxa unit numbers negatively related with the degradation index) accounted for only 18% of the total family number, but accounted for 54% of the total operational taxa unit numbers. Network analysis confirmed the oppressive relation between winners and the rest (losers + centrists), and further suggested the losers survival strategy as uniting the centrists. These findings shed new light on microorganism feedback to carbon degradation, and provide a scientific basis for the explanation of microbial community shift under progressive carbon degradation.

Genome-wide SNP analysis reveals the selection signatures of two indigenous buffalo breeds in Sichuan - Wei Wang; Donghui Fang; Yi Shi; Fang He; Jia Gan; Maozhong Fu; Xiaodong Deng; Tao Zhang; Hongbing Shen; Shengchao Zhong; Yueda Aguo; Luxi Chen; et al. (Conservation Genetics Resources, 2022)
Sichuan Province spawned abundant of indigenous buffalo varieties, which probably harbor valuable gene resources beneficial to the genetic improvement of buffalo. However, limited genetic information was publicly available. To better understand their selection signatures between different populations, we performed a restriction site-associated DNA sequencing (RADseq) to explore genome-wide SNPs among two indigenous breeds of Sichuan buffaloes. As a result, a total of 2,110,077 high-quality SNPs were finally obtained. Population genetic analysis indicated a obviously genetic differentiation between two breeds. The detection of selective genes showed that 995 and 910 protein-coding genes underwent positive selection in Yibin buffalo (GYBS) and Dechang buffalo (XCS). Further functional analysis revealed distinctly discrepant selection in two breeds. Candidate genes that positively selected from Yibin buffaloes have mainly occurred in functions closely related to meat quality, complex living environment adaption capability, and disease resistance. While they were significantly enriched in cell proliferation and cell components in Dechang buffalo, indicating the selection pressure primarily derived from the requirement of organism growth and development speed during breed formation. Our dataset constitutes a promising reservoir of genome-wide SNP markers of Sichuan buffaloes and provides potentially traits selected in different local populations. Such comprehensive genetic resources offer an unprecedented opportunity for genetic association analysis of economically important traits and precision breeding programs in buffaloes.

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Overexpression of a putative 12-oxophytodienoate reductase gene, EpOPR1, enhances acetylshikonin production in Echium plantagineum - Jiangyan Fu; Ran Ren; Suo Jin; Rongjun Fang; Zhongling Wen; Minkai Yang; Xuan Wang; Bao Liu; Tongming Yin; Guihua Lu; Yonghua Yang; Jinliang Qi (In Vitro Cellular & Developmental Biology - Plant, 2022)

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

Correction to: Chitosan‑based hydrogels to treat hydrofluoric acid burns and prevent infection - Shu‑Wei Huang; Fang‑Ching Yeh; You‑Ren Ji; Ying‑Fu Su; Ying‑shih Su; Ming‑Hsien Chiang; Shian‑Chiuan Tzeng; Chien‑Yao Fu; Aristine Cheng; Yung‑Chih Wang; Yi‑Tzu Lee (Drug Delivery and Translational Research, 2022)

Improving River-Stage Forecasting Using Hybrid Models Based on the Combination of Multiple Additive Regression Trees and Runge–Kutta Schemes - Jiun-Huei Jang; Kun-Fang Lee; Jin-Cheng Fu (Water Resources Management, 2022)

A Neural Circuit Mechanism Controlling Breathing by Leptin in the Nucleus Tractus Solitarii - Hongxiao Yu; Luo Shi; Jinting Chen; Shirui Jun; Yinchao Hao; Shuang Wang; Congrui Fu; Xiang Zhang; Haiyan Lu; Sheng Wang; Fang Yuan (Neuroscience Bulletin, 2022)

New monoterpenoids from the stigmas of Crocus sativus - Qing-Wei Fang; Wen-Wei Fu; Jin-Ling Yang; Yue Lu; Jiang-Cheng Chen; Pei-Ying Wu; Xue Zhang; Hong-Xi Xu (Journal of Natural Medicines, 2022)

Characteristics of fine particulate matter (PM2.5) at Jinsha Site Museum, Chengdu, China - Jialin Deng; Luman Jiang; Wenwen Miao; Junke Zhang; Guiming Dong; Ke Liu; Juncheng Chen; Tong Peng; Yao Fu; Yunpei Zhou; Xue Huang; Mengqian Hu; et al. (Environmental Science and Pollution Research, 2022)

Not out of the woods yet: Signatures of the prolonged negative genetic consequences of a population bottleneck in a rapidly re‐expanding wader, the black‐faced spoonbill Platalea minor - Shou‐Hsien Li; Yang Liu; Chia‐Fen Yeh; Yuchen Fu; Carol K. L. Yeung; Chun‐Cheng Lee; Chi‐Cheng Chiu; Tung Hui Kuo; Fang‐Tse Chan; Yu‐Chia Chen; Wen‐Ya Ko; Cheng‐Te Yao (Molecular Ecology, 2022)
The long‐term persistence of a population which has suffered a bottleneck partly depends on how historical demographic dynamics impacted its genetic diversity and the accumulation of deleterious mutations. Here we provide genomic evidence for the genetic effect of a recent population bottleneck in the endangered black‐faced spoonbill ( Platalea minor ) after its rapid population recovery. Our data suggest that the bird's effective population size, N e , had been relatively stable (7500–9000) since 22,000 years ago; however, a recent brief yet severe bottleneck ( N e = 20) which we here estimated to occur around the 1940s wiped out >99% of its historical N e in roughly three generations. Despite a >15‐fold population recovery since 1988, we found that black‐faced spoonbill population has higher levels of inbreeding (7.4 times more runs of homozygosity) than its sister species, the royal spoonbill ( P. regia ), which is not thought to have undergone a marked population contraction. Although the two spoonbills have similar levels of genome‐wide genetic diversity, our results suggest that selection on more genes was relaxed in the black‐faced spoonbill; moreover individual black‐faced spoonbills carry more putatively deleterious mutations (Grantham's score > 50), and may therefore express more deleterious phenotypic effects than royal spoonbills. Here we demonstrate the value of using genomic indices to monitor levels of genetic erosion, inbreeding and mutation load in species with conservation concerns. To mitigate the prolonged negative genetic effect of a population bottleneck, we recommend that all possible measures should be employed to maintain population growth of a threatened species.

Recent advances in tissue stem cells - Xin Fu; Qiang He; Yu Tao; Mengdi Wang; Wei Wang; Yalong Wang; Qing Cissy Yu; Fang Zhang; Xiaoyu Zhang; Ye-Guang Chen; Dong Gao; Ping Hu; et al. (Science China Life Sciences, 2021)

Responses of leaf litter decomposability to nitrogen and phosphorus additions are associated with cell wall carbohydrate composition in a subtropical plantation - Xiang-Min Fang; Xiu-Lan Zhang; Ying-Ying Zong; Wen-Qing Li; Jian-Jun Li; Li-Ping Guo; Huimin Wang; Fu-Sheng Chen (Plant and Soil, 2021)

Spatial variation, water quality, and health risk assessment of trace elements in groundwater in Beijing and Shijiazhuang, North China Plain - Han Fang; Zhifen Lin; Xiaoli Fu (Environmental Science and Pollution Research, 2021)

An Agrobacterium-mediated non-antibiotic selection-based transformation system for rice (Oryza sativa ssp. indica) cultivar “93-11” successfully produces TAC1-silenced transgenic plants - Jingjing Hou; Hao Chen; Yuzhen Fang; Ying Zhu; Bing Han; Chuanqing Sun; Yongcai Fu (In Vitro Cellular & Developmental Biology - Plant, 2021)

Lipidomic analyses reveal enhanced lipolysis in planthoppers feeding on resistant host plants - Xiaohong Zheng; Yeyun Xin; Yaxin Peng; Junhan Shan; Ning Zhang; Di Wu; Jianping Guo; Jin Huang; Wei Guan; Shaojie Shi; Cong Zhou; Rongzhi Chen; et al. (Science China Life Sciences, 2021)

Phytolith evidence for early agriculture in the East Liao River Basin, Northeast China - Jiangyong Wang; Linan Sun; Qi Fang; Jiaxin Fu; Baojian Liu; Ying Liu; Xiangmei Kong; Honghao Niu; Guizai Gao; Meng Meng; Dongmei Jie (Archaeological and Anthropological Sciences, 2021)

Tracing Nutrients and Organic Matter Changes in Eutrophic Wenchang (China) and Oligotrophic Krka (Croatia) Estuaries: A Comparative Study - You-You Hao; Zhuo-Yi Zhu; Fu-Tao Fang; Tihana Novak; Milan Čanković; Enis Hrustić; Zrinka Ljubešić; Ming Li; Jin-Zhou Du; Rui-Feng Zhang; Blaženka Gašparović (Frontiers in Marine Science, 2021)
Estuaries modify the concentration and composition of riverine nutrients and organic matter (OM), which eventually determine the riverine flux effect to coasts. Nutrients, organic carbon (OC), pigments, and amino acids (AAs) from the samples collected in the eutrophic Wenchang River Estuary (WRE) in China and the oligotrophic Krka River Estuary (KRE) in Croatia were analyzed in order to have a better understanding of how estuaries regulate terrestrial materials. We found a clear increase of dissolved inorganic nitrogen (DIN) concentration and its subsequent decrease due to the removal of DIN (over 100 μM) in the WRE, whereas DIN showed minor variation lengthwise in the KRE, i.e., with the salinity changes, ranging between 1.0 and 5.8 μM. The elevated algae-derived OC, dissolved organic nitrogen, and particulate AAs nitrogen suggest that the OM assimilation may explain approximately one-third of the DIN removal in the WRE, whereas in the oligotrophic KRE, such inorganic to organic transformation is not likely to be significant. Due to the prominent estuarine nitrogen removal/assimilation process, DIN/dissolved inorganic phosphorus (DIP) ratio was as high as 425 in the upper WRE under strong riverine influence, but it declined to as low as 5.4 at the mouth of WRE, that is even lower than DIN/DIP ratio at the mouth of oligotrophic KRE (12). When compared with other rivers worldwide, the Wenchang River showed high nutrients and organic carbon yields. Given the contrasting estuarine process (e.g., DIN removal) between the KRE and the WRE, apparent high nutrient yield from eutrophic rivers should be viewed with caution in ocean studies as the final impact to coastal zone could be similar to the oligotrophic rivers like the KRE.

Talaromyces Marneffei Infection in an HIV-Negative Child with a CARD9 Mutation in China: A Case Report and Review of the Literature - Cheng-yan You; Fang Hu; Si-wei Lu; Dan-dan Pi; Feng Xu; Cheng-jun Liu; Yue-qiang Fu (Mycopathologia, 2021)

Resource status and protection strategies of mangroves in China - Xiu-Mei Fu; Hui-Ying Tang; Yang Liu; Meng-Qi Zhang; Shan-Shan Jiang; Fang Yang; Xiao-Yan Li; Chang-Yun Wang (Journal of Coastal Conservation, 2021)
Mangrove is a typical natural landscape with great ecological, social and economic functions and values, and should be highly valued and protected. However, in the past few decades, mangrove resources have suffered serious damage, and there are also many deficiencies in mangrove protection. Chinese mangroves, as an important part of the global mangroves, are of great research value. In the present study, the status and historical dynamic process of Chinese mangrove resources were investigated and discussed to illustrate the problems of resources from three aspects, including mangrove distribution, area and plant species. Based on field research, literature research and data analysis, it was revealed that Chinese mangroves are distributed in eight provinces and regions along the southeast coast with an area of 35,749.25 hm 2 , 38 species and 40 nature reserves. The protection situation and deficiencies were analyzed from the establishment and management of nature reserves. Based on the resource status and problems, reasonable strategies were proposed to protect and manage mangroves mainly from four aspects, including publicity and education, resources restoration and protection technology, legal system establishment, and comprehensive protection and management.

Ecological carrying capacity of alpine grassland in the Qinghai–Tibet Plateau based on the structural dynamics method - Yi-ping Fang; Fu-biao Zhu; Shu-hua Yi; Xiao-ping Qiu; Yong-jiang Ding (Environment, Development and Sustainability, 2021)

Chitosan-based hydrogels to treat hydrofluoric acid burns and prevent infection - Shu-Wei Huang; Fang-Ching Yeh; You-Ren Ji; Ying-Fu Su; Ying-shih Su; Ming-Hsien Chiang; Shian-Chiuan Tzeng; Chien-Yao Fu; Aristine Cheng; Yung-Chih Wang; Yi-Tzu Lee (Drug Delivery and Translational Research, 2021)

Landslide distribution and sliding mode control along the Anninghe fault zone at the eastern edge of the Tibetan Plateau - Hong-fu Zhou; Bin Liu; Fei Ye; Wen-xi Fu; Wen-qing Tang; Ya-dong Qin; Tian Fang (Journal of Mountain Science, 2021)

RSF1 requires CEBP/β and hSNF2H to promote IL-1β-mediated angiogenesis: the clinical and therapeutic relevance of RSF1 overexpression and amplification in myxofibrosarcomas - Chien-Feng Li; Ti-Chen Chan; Cheng-I. Wang; Fu-Min Fang; Po-Chun Lin; Shih-Chen Yu; Hsuan-Ying Huang (Angiogenesis, 2021)

Mercury horizontal spatial distribution in paddy field and accumulation of mercury in rice as well as their influencing factors in a typical mining area of Tongren City, Guizhou, China - Jingjing Du; Fang Liu; Ling Zhao; Chong Liu; Zhaocong Fu; Ying Teng (Journal of Environmental Health Science and Engineering, 2021)

Lignin Synthesis Related Genes with Potential Significance in the Response of Upland Cotton to Fusarium Wilt Identified by Transcriptome Profiling - Jianan Hou; Fu’an Zhao; Xiaojie Yang; Wu Li; Deyi Xie; Zhongjie Tang; Shuping Lv; Lihong Nie; Yao Sun; Mengmeng Wang; Yajing Zhu; Xiaopei Bo; et al. (Tropical Plant Biology, 2021)
Fusarium wilt, caused by the fungus Fusarium oxysporum Schlecht. f. sp. vasinfectum (Fov) is a destructive soil-borne cotton disease. To profile the genes and pathways responding to Fov infection, we compared transcriptomic responses before and after F. oxysporum inoculation in a highly resistant cotton cultivar, Yumian21, and a highly susceptible cultivar, Jimian11. Although the overall gene expression pattern was downregulated in both cultivars, the global gene expression in the resistant cultivar was stronger than that in the susceptible cultivar. In addition, the expressed genes of two cultivars mostly differed in “cellular process,” “single-organism process,” “metabolic process,” and “response to stimulus” functional groups in the biological process Gene Ontology category: the upregulated differentially expressed genes (DEG) were largely enriched in the resistant cultivar, while the downregulated DEGs were largely enriched in the susceptible cultivar. Phenylpropanoid biosynthesis and phenylalanine metabolism are the key metabolic pathways in cotton in response to Fov. We found that lignin plays a potential role in cotton resistance to Fov. Two coding genes, caffeic acid 3-O-methyltransferase and peroxidase2 , as well as the two transcription factors MYB46 and MYB86 , are possibly involved in the accumulation and synthesis of lignin. Furthermore, the result showed that the quantification of lignin could be potentially used as a selection tool to identify Fusarium wilt resistant cotton.

Rhizosphere microbiome modulated effects of biochar on ryegrass 15N uptake and rhizodeposited 13C allocation in soil - Yingyi Fu; Amit Kumar; Lijun Chen; Yuji Jiang; Ning Ling; Runze Wang; Qiong Pan; Bhupinder Pal Singh; Marc Redmile-Gordon; Lu Luan; Qin Li; Quan Shi; et al. (Plant and Soil, 2021)

Taurine improves the differentiation of neural stem cells in fetal rats with intrauterine growth restriction via activation of the PKA-CREB-BDNF signaling pathway - Qiong Fang; Jing Liu; Lang Chen; Qiaobin Chen; Jun Ke; Jiuyun Zhang; Ying Liu; Wei Fu (Metabolic Brain Disease, 2021)

Multi-GNSS PPP/INS tightly coupled integration with atmospheric augmentation and its application in urban vehicle navigation - Shengfeng Gu; Chunqi Dai; Wentao Fang; Fu Zheng; Yintong Wang; Quan Zhang; Yidong Lou; Xiaoji Niu (Journal of Geodesy, 2021)

B3GNT3 acts as a carcinogenic factor in endometrial cancer via facilitating cell growth, invasion and migration through regulating RhoA/RAC1 pathway-associated markers - Ji-Shui Wang; Fang Ruan; Li-Zhu Guo; Feng-Ge Wang; Fu-Ling Wang; Hong-Min An (Genes & Genomics, 2021)

Comparative proteomic analysis of the fungal pathogen Neoscytalidium dimidiatum infection in the pitaya - Limei Pan; Rong Zhang; Fang Lu; Chengming Liu; Jiaxin Fu (Horticulture, Environment, and Biotechnology, 2021)

microRNA-184 enhances the sensitivity of pheochromocytoma-12 cells to doxorubicin by targeting ADAM22 - Nairui Zhao; Na Su; Guangya Wang; Dongxia Fu; Fang Gao; Yunna Zhang (Molecular & Cellular Toxicology, 2021)

Correction to: Central Blockade of E-Prostanoid 3 Receptor Ameliorated Hypertension Partially by Attenuating Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus of Spontaneously Hypertensive Rats - Fang-Fang Wang; Juan Bai; Xiao-Jing Yu; Xiao-Lian Shi; Jin-Jun Liu; Kai-Li Liu; Li-Yan Fu; Qing Su; Hong-Bao Li; Kai B. Kang; Qiu-Yue Yi; Shu-Qiu Wang; et al. (Cardiovascular Toxicology, 2021)

Central Blockade of E-Prostanoid 3 Receptor Ameliorated Hypertension Partially by Attenuating Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus of Spontaneously Hypertensive Rats - Fang-Fang Wang; Juan Ba; Xiao-Jing Yu; Xiao-Lian Shi; Jin-Jun Liu; Kai-Li Liu; Li-Yan Fu; Qing Su; Hong-Bao Li; Kai B. Kang; Qiu-Yue Yi; Shu-Qiu Wang; et al. (Cardiovascular Toxicology, 2021)

Genetic diversity and population structure of Tibetan sheep breeds determined by whole genome resequencing - Lei-Lei Li; Shi-Ke Ma; Wei Peng; You-Gui Fang; Hai-Rui Duo; Hong-Yun Fu; Gong-Xue Jia (Tropical Animal Health and Production, 2021)

Litter addition and understory removal influenced soil organic carbon quality and mineral nitrogen supply in a subtropical plantation forest - Xiang-Min Fang; G. Geoff Wang; Zhi-Jun Xu; Ying-Ying Zong; Xiu-Lan Zhang; Jian-Jun Li; Huimin Wang; Fu-Sheng Chen (Plant and Soil, 2021)

Cloning and functional analysis of EpGHQH1 in shikonin production of Echium plantagineum - Jiangyan Fu; Guihua Lu; Minkai Yang; Hua Zhao; Wencai Jie; Aliya Fazal; Xuan Wang; Zhongling Wen; Rongjun Fang; Bao Liu; Tongming Yin; Jinliang Qi; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Lactobacillus rhamnosus JYLR-005 Prevents Thiram-Induced Tibial Dyschondroplasia by Enhancing Bone-Related Growth Performance in Chickens - Fang Liu; Anan Kong; Pengfei Fu; Qin-qin Cao; Kun-sheng Tao; Di-yi Liu; Xue-bing Wang; Zong-xi Tong; Mujeeb Ur Rehman; Shu-cheng Huang (Probiotics and Antimicrobial Proteins, 2021)

Compound heterozygous mutation of the ASXL3 gene causes autosomal recessive congenital heart disease - Fang Fu; Ru Li; Ting-ying Lei; Dan Wang; Xin Yang; Jin Han; Min Pan; Li Zhen; Jian Li; Fa-tao Li; Xiang-yi Jing; Dong-zhi Li; et al. (Human Genetics, 2021)

Respiratory Control by Phox2b-expressing Neurons in a Locus Coeruleus–preBötzinger Complex Circuit - Na Liu; Congrui Fu; Hongxiao Yu; Yakun Wang; Luo Shi; Yinchao Hao; Fang Yuan; Xiangjian Zhang; Sheng Wang (Neuroscience Bulletin, 2021)

Safety of protease inhibitors and Arbidol for SARS-CoV-2 pneumonia in Zhejiang Province, China - Yong-zheng Guo; Kai-jin Xu; Yong-tao Li; Jia-dan Fu; Min Xu; Ling Yu; Ji-fang Sheng; Biao Zhu (Journal of Zhejiang University-SCIENCE B, 2020)

Does underweight amplify the relationship between short-term particulate matter exposure and blood pressure in children and adolescents: a large cross-sectional study in a metropolis of China - Jia Hu; Han Fu; Hui Shen; Chen-gang Teng; Wei Yang; Hai-bing Yang; Fang Liu (Environmental Science and Pollution Research, 2020)

Experimentally Induced Sepsis Causes Extensive Hypomyelination in the Prefrontal Cortex and Hippocampus in Neonatal Rats - Peixian Huang; Xuan Chen; Xiaoli Hu; Qiuping Zhou; Lanfen Lin; Shuqi Jiang; Hui Fu; Yajie Xiong; Hongke Zeng; Ming Fang; Chunbo Chen; Yiyu Deng (NeuroMolecular Medicine, 2020)

Silencing of long non-coding RNA CRNDE promotes autophagy and alleviates neonatal hypoxic-ischemic brain damage in rats - Chun-Hua Fu; Fang-Fang Lai; Sai Chen; Cai-Xia Yan; Bing-Hong Zhang; Cheng-Zhi Fang; Gao-Hua Wang (Molecular and Cellular Biochemistry, 2020)

Responses of Denitrification Rate and Denitrifying Bacterial Communities Carrying nirS and nirK Genes to Grazing in Peatland - Xin Fang; Rongbo Zheng; Xuelian Guo; Qian Fu; Kun Zhang (Journal of Soil Science and Plant Nutrition, 2020)

Next-generation sequencing and single-cell RT-PCR reveal a distinct variable gene usage of porcine antibody repertoire following PEDV vaccination - Ren Li; Fang Fu; Li Feng; PingHuang Liu (Science China Life Sciences, 2020)

Identification and evaluation of tobacco cytoplasmic male sterile line Nta(gla)S K326 generated from asymmetric protoplast fusion of Nicotiana glauca and N. tabacum followed by backcrossing with N. tabacum K326 - Xue-Jun Chen; Zhi-Jun Tong; Bing-Guang Xiao; Yong-Ping Li; Fang-Chan Jiao; Yong Li; Tao Pang; Dun-Huang Fang; Xing-Fu Wu; Yi-Han Zhang; He Xie; Ge Bai; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Variations in vegetation dynamics and its cause in national key ecological function zones in China - Jiaqiang Du; Shifeng Fang; Zhilu Sheng; Jinhua Wu; Zhanjun Quan; Qing Fu (Environmental Science and Pollution Research, 2020)

Antifungal, anti-inflamatory and neuritogenic activity of newly-isolated compounds from Disporopsis aspersa - Fang-Li Gang; Feng Zhu; Chao-Fu Yang; Xiao-Ting Li; Hua Yang; Ming-Xia Sun; Wen-Jun Wu; Ji-Wen Zhang (Natural Product Research, 2020)

Reversal of Social Recognition Deficit in Adult Mice with MECP2 Duplication via Normalization of MeCP2 in the Medial Prefrontal Cortex - Bin Yu; Bo Yuan; Jian-Kun Dai; Tian-lin Cheng; Sheng-Nan Xia; Ling-Jie He; Yi-Ting Yuan; Yue-Fang Zhang; Hua-Tai Xu; Fu-Qiang Xu; Zhi-Feng Liang; Zi-Long Qiu (Neuroscience Bulletin, 2020)

Enhanced pyrogallol toxicity to cyanobacterium Microcystis aeruginosa with increasing alkalinity - Yunni Gao; Qinqin Fu; Jing Lu; Hui Yang; Philip T. Orr; Fang Zhang; Jing Dong; Man Zhang; Qianhong Gu; Chuanjiang Zhou; Michele A. Burford (Journal of Applied Phycology, 2020)

Epidemiology and HBGA-susceptibility investigation of a G9P[8] rotavirus outbreak in a school in Lechang, China - Lun-Ai Guo; Meng Zhang; Yu-zhen Hou; Haitao Hu; Ling Fang; Ming Tan; Qiong Huang; Hui Li; Li-Mei Sun; Xi Jiang; Wen-Fang Tan; Shixing Tang; et al. (Archives of Virology, 2020)

Variation in radial growth and wood density of Cyclocarya paliurus across its natural distribution - Shengzuo Fang; Daiyan Sun; Xulan Shang; Xiangxiang Fu; Wanxia Yang (New Forests, 2020)

The Complete Genome of Emcibacter congregatus ZYLT, a Marine Bacterium Encoding a CRISPR-Cas 9 Immune System - Zhe Zhao; Rui-an Zhang; Ge-yi Fu; Ran Zhang; Yan-fang Nie; Cong Sun; Min Wu (Current Microbiology, 2020)

Global Profiling of Alternative Splicing in Callus Induction of Immature Maize Embryo - Xuemei Du; Ting Fang; Yan Liu; Liying Huang; Xiaoli Wang; Jie Zhang; Yangbo Cui; Maosen Zang; Guoying Wang; Junjie Fu; Yunjun Liu (In Vitro Cellular & Developmental Biology - Plant, 2020)

Antibacterial activity and action mode of chlorogenic acid against Salmonella Enteritidis, a foodborne pathogen in chilled fresh chicken - Zhilan Sun; Xinxiao Zhang; Haihong Wu; Hongyi Wang; Huan Bian; Yongzhi Zhu; Weimin Xu; Fang Liu; Daoying Wang; Longyun Fu (World Journal of Microbiology and Biotechnology, 2020)

Magnetotail dipolarization fronts and particle acceleration: A review - Huishan Fu; Elena E. Grigorenko; Christine Gabrielse; Chengming Liu; San Lu; K. J. Hwang; Xuzhi Zhou; Zhe Wang; Fang Chen (Science China Earth Sciences, 2020)

Spatiotemporal changes in vegetation coverage and its causes in China since the Chinese economic reform - Jiaqiang Du; Zhanjun Quan; Shifeng Fang; Chengcheng Liu; Jinhua Wu; Qing Fu (Environmental Science and Pollution Research, 2020)

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Characteristics and Prognosis of Talaromyces marneffei Infection in Non-HIV-Infected Children in Southern China - Jing Guo; Bing-Kun Li; Tian-Min Li; Fang-Lin Wei; Yu-Jiao Fu; Yan-Qing Zheng; Kai-Su Pan; Chun-Yang Huang; Cun-Wei Cao (Mycopathologia, 2019)

Marine 3D seismic volumes from 2D seismic survey with large streamer feathering - Liang-Fu Lin; Ho-Han Hsu; Char-Shine Liu; Kuo-Han Chao; Chia-Chun Ko; Shye-Dong Chiu; Hsin-Sung Hsieh; Yu-Fang Ma; Song-Chuen Chen (Marine Geophysical Research, 2019)

Major advances in studies of the physical geography and living environment of China during the past 70 years and future prospects - Fahu Chen; Bojie Fu; Jun Xia; Duo Wu; Shaohong Wu; Yili Zhang; Hang Sun; Yu Liu; Xiaomin Fang; Boqiang Qin; Xin Li; Tingjun Zhang; et al. (Science China Earth Sciences, 2019)

Expression of AHI1 Rescues Amyloidogenic Pathology in Alzheimer’s Disease Model Cells - Lai-Lei Ting; Hsien-Tsung Lu; Shu-Fen Yen; Thi Huong Ngo; Fang-Yu Tu; I-Shih Tsai; Yi-Hua Tsai; Fu-Yen Chang; Xiao-Jiang Li; Shihua Li; Ching-Kuo Lee; Shu-Huei Kao; et al. (Molecular Neurobiology, 2019)

Interferon gamma inhibits transmissible gastroenteritis virus infection mediated by an IRF1 signaling pathway - Lingling Shan; Fang Fu; Mei Xue; Xiangdong Zhu; Liang Li; Li Feng; Pinghuang Liu (Archives of Virology, 2019)

Effects of nutrient addition on foliar phosphorus fractions and their resorption in different-aged leaves of Chinese fir in subtropical China - Fang-Chao Wang; Xiang-Min Fang; G. Geoff Wang; Rong Mao; Xiao-Fan Lin; Huimin Wang; Fu-Sheng Chen (Plant and Soil, 2019)

Differentiation of the Agonists and Antagonists of the α7 Nicotinic Acetylcholine Receptor - Guanzhao Wu; Qingliang Xu; Yilei Bao; Yuwei Liu; Qian Li; Zhengyu Fang; Jingyi Fu; Yuhang Ding; Zhiqing Liang; Tao Jiang; Rilei Yu (Journal of Ocean University of China, 2019)

The effects of simulated deposited nitrogen on nutrient dynamics in decomposing litters across a wide quality spectrum using a 15N tracing technique - Xue-Min Ye; Yang Zhang; Fu-Sheng Chen; G. Geoff Wang; Xiang-Min Fang; Xiao-Fan Lin; Song-Ze Wan; Ping He (Plant and Soil, 2019)

The Core Role of Bacillus subtilis and Aspergillus fumigatus in Pile-Fermentation Processing of Qingzhuan Brick Tea - Qian Xu; Min Sun; Jingming Ning; Shimao Fang; Ziling Ye; Junhai Chen; Ruiyan Fu (Indian Journal of Microbiology, 2019)

Comprehensive Assessment and Rechecking of Rainfall Threshold for Flash Floods Based on the Disaster Information - Wenlin Yuan; Lei Fu; Qianyu Gao; Fang Wan (Water Resources Management, 2019)

The Inhibitory Effects of Nitrogen Deposition on Asymbiotic Nitrogen Fixation are Divergent Between a Tropical and a Temperate Forest - Mianhai Zheng; Wei Zhang; Yiqi Luo; Shiqiang Wan; Shenglei Fu; Senhao Wang; Nan Liu; Qing Ye; Junhua Yan; Bi Zou; Chengliang Fang; Yuxi Ju; et al. (Ecosystems, 2019)

Spatial variation of the relationship between transport accessibility and the level of economic development in Qinghai-Tibet Plateau, China - Xue-ting Yang; Xiao-ping Qiu; Yi-ping Fang; Yun Xu; Fu-biao Zhu (Journal of Mountain Science, 2019)

Evolutionary and functional implications of 3′ untranslated region length of mRNAs by comprehensive investigation among four taxonomically diverse metazoan species - Wei Wang; Dong-hui Fang; Jia Gan; Yi Shi; Hui Tang; Huai Wang; Mao-zhong Fu; Jun Yi (Genes & Genomics, 2019)

Identification, evolution and alternative splicing profile analysis of the splicing factor 30 (SPF30) in plant species - Di Zhang; Jing-Fang Yang; Bei Gao; Tie-Yuan Liu; Ge-Fei Hao; Guang-Fu Yang; Li-Jun Fu; Mo-Xian Chen; Jianhua Zhang (Planta, 2019)

Nitrogen deposition effect on forest litter decomposition is interactively regulated by endogenous litter quality and exogenous resource supply - Fu-Sheng Chen; G. Geoff Wang; Xiang-Min Fang; Song-Ze Wan; Yang Zhang; Chao Liang (Plant and Soil, 2019)

Health risk assessment of heavy metals in Cyprinus carpio (Cyprinidae) from the upper Mekong River - Ji Lai Zhang; Li Fang; Jing Yi Song; Xia Luo; Kai Dao Fu; Li Qiang Chen (Environmental Science and Pollution Research, 2019)

Influence of provenance and shade on biomass production and triterpenoid accumulation in Cyclocarya paliurus - Bo Deng; Shengzuo Fang; Xulan Shang; Xiangxiang Fu; Yan Li (Agroforestry Systems, 2019)

Microsatellite records for volume 11, issue 1 - Da-Qing Chen; Zaijie Dong; Min Fang; Jianjun Fu; Xiang-Yang Jia; Bingjie Jiang; Jingmiao Li; Qingqing Li; Suhui Liao; Ping Liu; Yulin Liu; Guocheng Shu; et al. (Conservation Genetics Resources, 2019)

Genome-wide detection of additional fetal chromosomal abnormalities by cell-free DNA testing of 15,626 consecutive pregnant women - Hong Yao; Ya Gao; Jia Zhao; Rong Zhang; Huixin Xu; Huamei Hu; Yanmei Luo; Yuying Yuan; Meili Fu; Hongyun Zhang; Hui Jiang; Wei Wang; et al. (Science China Life Sciences, 2019)

Genome-wide identification and functional analysis of the splicing component SYF2/NTC31/p29 across different plant species - Yuan Tian; Mo-Xian Chen; Jing-Fang Yang; H. H. K. Achala; Bei Gao; Ge-Fei Hao; Guang-Fu Yang; Zhi-Yong Dian; Qi-Juan Hu; Di Zhang; Jianhua Zhang; Ying-Gao Liu (Planta, 2019)

The effects of simulated acid rain on internal nutrient cycling and the ratios of Mg, Al, Ca, N, and P in tea plants of a subtropical plantation - Xiao-Fei Hu; An-Qi Wu; Fang-Chao Wang; Fu-Sheng Chen (Environmental Monitoring and Assessment, 2019)

Programmed cell death induced by cadmium stress and/or boron deprivation in tobacco (Nicotiana tabacum L.) cultivar Bright Yellow 2 cells - Li Ping Jiang; Lin Zi; Xiao Fang Liu; Zi-Xi Liu; Lai Fu Zhong; Xiang Xin Xue (In Vitro Cellular & Developmental Biology - Plant, 2019)

Role of permafrost in resilience of social-ecological system and its spatio-temporal dynamics in the source regions of Yangtze and Yellow Rivers - Yi-ping Fang; Fu-biao Zhu; Shu-hua Yi; Xiao-ping Qiu; Yong-jian Ding (Journal of Mountain Science, 2019)

Nramp5 expression and functionality likely explain higher cadmium uptake in rice than in wheat and maize - Fu-Qing Sui; Jia-Dong Chang; Zhong Tang; Wen-Ju Liu; Xin-Yuan Huang; Fang-Jie Zhao (Plant and Soil, 2018)

Lack of Association Between DNMT3B Polymorphisms and Sporadic Parkinson’s Disease in a Han Chinese Population - Hong Pan; Jun-Yi Shen; Juan-Juan Du; Shi-Shuang Cui; Jin Liu; Yi-Qi Lin; Yi-Xi He; Yang Fu; Chao Gao; Gen Li; Sheng-Di Chen; Jian-Fang Ma (Neuroscience Bulletin, 2018)

Ambient air particulates-bound metallic elements sources identifications during winter and summer at a Science Park - Guor-Cheng Fang; Chao-Yang Huang; Yuan-Jie Zhuang; Wen-Chuan Huang; Kai-Hsiang Tsai; You-Fu Xiao (Environmental Geochemistry and Health, 2018)

Multi-Objective Differential Evolution-Chaos Shuffled Frog Leaping Algorithm for Water Resources System Optimization - Guohua Fang; Yuxue Guo; Xin Wen; Xiaomin Fu; Xiaohui Lei; Yu Tian; Ting Wang (Water Resources Management, 2018)

Radiocarbon ages of different fractions of peat on coastal lowland of Bohai Bay: marine influence? - Zhiwen Shang; Fu Wang; Jing Fang; Jianfen Li; Yongsheng Chen; Xingyu Jiang; Lizhu Tian; Hong Wang (Journal of Oceanology and Limnology, 2018)

Wet depositions of mercury during plum rain season in Taiwan - Guor-Cheng Fang; Wen-Chuan Huang; Yuan-Jie Zhuang; Chao-Yang Huang; Kai-Hsiang Tsai; You-Fu Xiao (Environmental Geochemistry and Health, 2018)

Plantar blood flow response to accumulated pressure stimulus in diabetic people with different peak plantar pressure: a non-randomized clinical trial - Fang Pu; Weiyan Ren; Hongyuan Fu; Xuan Zheng; Min Yang; Yih-Kuen Jan; Yubo Fan (Medical & Biological Engineering & Computing, 2018)

Genetic structure of six cattle populations revealed by transcriptome-wide SNPs and gene expression - Wei Wang; Huai Wang; Hui Tang; Jia Gan; Changgeng Shi; Qing Lu; Donghui Fang; Jun Yi; Maozhong Fu (Genes & Genomics, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Functional Role of Matrix gla Protein in Glioma Cell Migration - Mu-Hui Fu; Chih-Yen Wang; Yun-Ti Hsieh; Kuan-Min Fang; Shun-Fen Tzeng (Molecular Neurobiology, 2018)

Review of total suspended particles (TSP) and PM2.5 concentration variations in Asia during the years of 1998–2015 - Guor-Cheng Fang; Yuan-Jie Zhuang; Meng-Hsien Cho; Chao-Yang Huang; You-Fu Xiao; Kai-Hsiang Tsai (Environmental Geochemistry and Health, 2018)

Fatigue Magnification Factors of Arc-Soft-Toe Bracket Joints - Qiang Fu; Huajun Li; Hongqing Wang; Shuqing Wang; Dejiang Li; Qun Li; Hui Fang (Journal of Ocean University of China, 2018)

Vinpocetine Inhibits NF-κB-Dependent Inflammation in Acute Ischemic Stroke Patients - Fang Zhang; Chen Yan; Changjuan Wei; Yang Yao; Xiaofeng Ma; Zhongying Gong; Shoufeng Liu; Dawei Zang; Jieli Chen; Fu-Dong Shi; Junwei Hao (Translational Stroke Research, 2018)

Genetic variation and association mapping of aphid (Macrosiphoniella sanbourni) resistance in chrysanthemum (Chrysanthemum morifolium Ramat.) - Xiao Fu; Jiangshuo Su; Kaili Yu; Yifan Cai; Fei Zhang; Sumei Chen; Weimin Fang; Chen Fadi; Zhiyong Guan (Euphytica, 2018)

Concentrations and analysis of health risks of ambient air metallic elements at Longjing site in central Taiwan - Guor-Cheng Fang; Yu-Cheng Chen; Chaur-Tsuen Lo; Meng-Hsien Cho; Yuan-Jie Zhuang; Kai-Hsiang Tsai; Chao-Yang Huang; You-Fu Xiao (Environmental Geochemistry and Health, 2018)

Effects of altitude on county economic development in China - Fu-biao Zhu; Yi-ping Fang; Xue-ting Yang; Xiao-ping Qiu; Hu Yu (Journal of Mountain Science, 2018)

Experimental comparison of electroosmotic consolidation of wenzhou dredged clay sediment using intermittent current and polarity reversal - Hongtao Fu; Ziquan Fang; Jun Wang; Jinchun Chai; Yuanqiang Cai; Xueyu Geng; Jinqiang Jin; Fangyi Jin (Marine Georesources & Geotechnology, 2018)

The genetic and molecular basis of crop height based on a rice model - Fang Liu; Pandi Wang; Xiaobo Zhang; Xiaofei Li; Xiaohong Yan; Donghui Fu; Gang Wu (Planta, 2018)

Gradient effect of road transportation on economic development in different geomorphic regions - Xue-ting Yang; Yi-ping Fang; Xiao-ping Qiu; Fu-biao Zhu (Journal of Mountain Science, 2018)

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

Impacts of precipitation variation and soil and water conservation measures on runoff and sediment yield in the Loess Plateau Gully Region, China - Lu Xia; Xiao-yu Song; Na Fu; Chun-fang Meng; Huai-you Li; Yao-lin Li (Journal of Mountain Science, 2017)

Genome-wide analysis of GDSL-type esterases/lipases in Arabidopsis - Chia-Ping Lai; Li-Min Huang; Long-Fang O. Chen; Ming-Tsair Chan; Jei-Fu Shaw (Plant Molecular Biology, 2017)

Long-term fertilization increases soil nutrient accumulations but decreases biological activity in navel orange orchards of subtropical China - Song-Ze Wan; Han-Jiao Gu; Qing-Pei Yang; Xiao-Fei Hu; Xiang-Min Fang; Anand Narain Singh; Fu-Sheng Chen (Journal of Soils and Sediments, 2017)

Kitamycin C, a new antimycin-type antibiotic from Streptomyces antibioticus strain 200-09 - Fan Wang; Shu-Na Fu; Yi-Xuan Bao; Yu Yang; Hui-Fang Shen; Bi-Run Lin; Guang-Xiong Zhou (Natural Product Research, 2017)

Natural population structure and genetic differentiation for heterodicogamous plant: Cyclocarya paliurus (Batal.) Iljinskaja (Juglandaceae) - Xiaochun Li; Xiangxiang Fu; Xulan Shang; Wanxia Yang; Shengzuo Fang (Tree Genetics & Genomes, 2017)

Increasing acidity of rain in subtropical tea plantation alters aluminum and nutrient distributions at the root-soil interface and in plant tissues - Xiao-Fei Hu; Fu-Sheng Chen; Michael L. Wine; Xiang-Min Fang (Plant and Soil, 2017)

Nafamostat Mesilate Improves Neurological Outcome and Axonal Regeneration after Stroke in Rats - Yuan Liu; Chenhui Li; Jing Wang; Yinquan Fang; Hao Sun; Xia Tao; Xin-Fu Zhou; Hong Liao (Molecular Neurobiology, 2017)

Forest-type shift and subsequent intensive management affected soil organic carbon and microbial community in southeastern China - Xianghua Fang; Jinchi Zhang; Miaojing Meng; Xiaoping Guo; Yanwen Wu; Xin Liu; Keli Zhao; Lizhong Ding; Yangfeng Shao; Weijun Fu (European Journal of Forest Research, 2017)

Annual ambient atmospheric mercury speciation measurement from Longjing, a rural site in Taiwan - Guor-Cheng Fang; Chaur-Tsuen Lo; Meng-Hsien Cho; Yuan-Jie Zhuang; Kai-Hsiang Tsai; Chao-Yang Huang; You-Fu Xiao (Environmental Geochemistry and Health, 2017)

PM2.5 particulates and metallic elements (Ni, Cu, Zn, Cd and Pb) study in a mixed area of summer season in Shalu, Taiwan - Guor-Cheng Fang; You-Fu Xiao; Yuan-Jie Zhuang; Meng-Hsien Cho; Chao-Yang Huang; Kai-Hsiang Tsai (Environmental Geochemistry and Health, 2017)

Debris flows monitoring and localization using infrasonic signals - Xiao-peng Leng; Dun-long Liu; Fang-qiang Wei; Yong Hong; De-fu Dai (Journal of Mountain Science, 2017)

A dramatic blood plasticity in hibernating and 14-day hindlimb unloading Daurian ground squirrels (Spermophilus dauricus) - Huan-Xin Hu; Fang-Ying Du; Wei-Wei Fu; Shan-Feng Jiang; Jin Cao; Shen-Hui Xu; Hui-Ping Wang; Hui Chang; Nandu Goswami; Yun-Fang Gao (Journal of Comparative Physiology B, 2017)

Evaluation of Osseointegration in Titanium and Zirconia-Based Dental Implants with Surface Modification in a Miniature Pig Model - Tzong-Fu Kuo; Hung-Chieh Lu; Chien-Fang Tseng; Jen-Chang Yang; Sea-Fue Wang; Thomas Chung-Kuang Yang; Sheng-Yang Lee (Journal of Medical and Biological Engineering, 2017)

Combined iron and magnesium isotope geochemistry of pyroxenite xenoliths from Hannuoba, North China Craton: implications for mantle metasomatism - Xin Miao Zhao; Hui Hui Cao; Xue Mi; Noreen J. Evans; Yu Han Qi; Fang Huang; Hong Fu Zhang (Contributions to Mineralogy and Petrology, 2017)

Early-Life Social Isolation-Induced Depressive-Like Behavior in Rats Results in Microglial Activation and Neuronal Histone Methylation that Are Mitigated by Minocycline - Hong-Tao Wang; Fu-Lian Huang; Zhao-Lan Hu; Wen-Juan Zhang; Xiao-Qing Qiao; Yan-Qing Huang; Ru-Ping Dai; Fang Li; Chang-Qi Li (Neurotoxicity Research, 2017)

Role of the lipid-regulated NF-κB/IL-6/STAT3 axis in alpha-naphthyl isothiocyanate-induced liver injury - Zhong-Ze Fang; Naoki Tanaka; Dan Lu; Chang-Tao Jiang; Wei-Hua Zhang; Chunze Zhang; Zuo Du; Zhi-Wei Fu; Peng Gao; Yun-Feng Cao; Hong-Zhi Sun; Zhi-Tu Zhu; et al. (Archives of Toxicology, 2017)

A 2D integrated FEM model for surface water–groundwater flow of slopes under rainfall condition - Dong fang Tian; Hong Zheng; De fu Liu (Landslides, 2017)

Association of oral endothelin receptor antagonists with risks of cardiovascular events and mortality: meta-analysis of randomized controlled trials - Yu Pan; Chun Hu; Pei Hua Chen; Yan Hong Gu; Qing Yan Qiao; Li Hua Pan; Dong Chi Zhou; Hui Fang Gu; Shun Kun Fu; Hui Min Jin (European Journal of Clinical Pharmacology, 2017)

Toxicity and accumulation of zinc pyrithione in the liver and kidneys of Carassius auratus gibelio: association with P-glycoprotein expression - Tao Ren; Gui-Hong Fu; Teng-Fei Liu; Kun Hu; Hao-Ran Li; Wen-Hong Fang; Xian-Le Yang (Fish Physiology and Biochemistry, 2017)

Seasonal variations and sources study by way of back trajectories and ANOVA for ambient air pollutants (particulates and metallic elements) within a mixed area at Longjing, central Taiwan: 1-year observation - Guor-Cheng Fang; Chaur-Tsuen Lo; Yuan-Jie Zhuang; Meng-Hsien Cho; Chao-Yang Huang; You-Fu Xiao; Kai-Hsiang Tsai (Environmental Geochemistry and Health, 2017)

Enhanced Therapeutic Potential of Nano-Curcumin Against Subarachnoid Hemorrhage-Induced Blood–Brain Barrier Disruption Through Inhibition of Inflammatory Response and Oxidative Stress - Zong-yong Zhang; Ming Jiang; Jie Fang; Ming-feng Yang; Shuai Zhang; Yan-xin Yin; Da-wei Li; Lei-lei Mao; Xiao-yan Fu; Ya-jun Hou; Xiao-ting Fu; Cun-dong Fan; et al. (Molecular Neurobiology, 2017)

Application of high resolution SNP arrays in patients with congenital oral clefts in south China - TING-YING LEI; HONG-TAO WANG; FAN LI; YING-QIU CUI; FANG FU; RU LI; CAN LIAO (Journal of Genetics, 2016)

Identification of novel polymorphic microsatellite loci in the endangered Chinese sucker (Myxocyprinus asiaticus) - NIAN XU; DONG-MEI XU; YAN-FU QUE; FANG SHI; MEI-HUA XIONG; KE SHAO; WEI-TAO LI; BIN ZHU; ZHONG YANG (Journal of Genetics, 2016)

The angiotensin-I converting enzyme gene I/D variation contributes to end-stage renal disease risk in Chinese patients with type 2 diabetes receiving hemodialysis - Ming Lu; Jianzhong Zhang; Ming Li; Xiaoxu Ge; Xu Dai; Jiao Zhao; Mingzhou Fu; Tao Wang; Xiyao Fang; Can Li; Rong Zhang; Weijing Zhao; et al. (Molecular and Cellular Biochemistry, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Antidepressant-like effects of standardized gypenosides: involvement of brain-derived neurotrophic factor signaling in hippocampus - Rong-Hao Mu; Xiao-Yan Fang; Shuang-Shuang Wang; Cheng-Fu Li; Shao-Mei Chen; Xue-Mei Chen; Qing Liu; Yu-Cheng Li; Li-Tao Yi (Psychopharmacology, 2016)

DSePA Antagonizes High Glucose-Induced Neurotoxicity: Evidences for DNA Damage-Mediated p53 Phosphorylation and MAPKs and AKT Pathways - Kun Wang; Xiao-yan Fu; Xiao-ting Fu; Ya-jun Hou; Jie Fang; Shuai Zhang; Ming-feng Yang; Da-wei Li; Lei-lei Mao; Jing-yi Sun; Hui Yuan; Xiao-yi Yang; et al. (Molecular Neurobiology, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

GSK-3β promotes PA-induced apoptosis through changing β-arrestin 2 nucleus location in H9c2 cardiomyocytes - Fen Chang; Jing Liu; Hui Fu; Jinlan Wang; Fang Li; Hongwei Yue; Wenjing Li; Jing Zhao; Deling Yin (Apoptosis, 2016)

Investigation of absorption and scattering characteristics of kiwifruit tissue using a single integrating sphere system - Zhen-huan Fang; Xia-ping Fu; Xue-ming He (Journal of Zhejiang University-SCIENCE B, 2016)

Mapping the vegetation distribution of the permafrost zone on the Qinghai-Tibet Plateau - Zhi-wei Wang; Qian Wang; Lin Zhao; Xiao-dong Wu; Guang-yang Yue; De-fu Zou; Zhuo-tong Nan; Guang-yue Liu; Qiang-qiang Pang; Hong-bing Fang; Tong-hua Wu; Jian-zong Shi; et al. (Journal of Mountain Science, 2016)

Effects of seasonal variations on soil microbial community composition of two typical zonal vegetation types in the Wuyi Mountains - Ze-yan Wu; Wen-xiong Lin; Jian-juan Li; Jin-fu Liu; Bai-lian Li; Lin-kun Wu; Chang-xun Fang; Zhi-xing Zhang (Journal of Mountain Science, 2016)

Vertical distributions of aerosol optical properties during haze and floating dust weather in Shanghai - Qiong Liu; Yuan Wang; Zhongyu Kuang; Sihua Fang; Yonghang Chen; Yanming Kang; Hua Zhang; Daoyuan Wang; Yingying Fu (Journal of Meteorological Research, 2016)

TRMM-observed summer warm rain over the tropical and subtropical Pacific Ocean: Characteristics and regional differences - Fang Qin; Yunfei Fu (Journal of Meteorological Research, 2016)

Neuroprotection of Sevoflurane Against Ischemia/Reperfusion-Induced Brain Injury Through Inhibiting JNK3/Caspase-3 by Enhancing Akt Signaling Pathway - Xiang-Ru Wen; Yan-Yan Fu; Hong-Zhi Liu; Jian Wu; Xiao-Ping Shao; Xun-Bao Zhang; Man Tang; Yue Shi; Kai Ma; Fang Zhang; Yi-Wen Wang; Hui Tang; et al. (Molecular Neurobiology, 2016)

Transcriptome sequencing discovers genes related to fatty acid biosynthesis in the seeds of Eucommia ulmoides - Yan-zhi Feng; Lu Wang; Jian-min Fu; Ta-na Wuyun; Hong-yan Du; Xiao-feng Tan; Feng Zou; Fang-dong Li (Genes & Genomics, 2016)

Synthesis of some new thiazolo[3,2-a]pyrimidine derivatives and screening of their in vitro antibacterial and antitubercular activities - Dong Cai; Zhi-Hua Zhang; Yu Chen; Xin-Jia Yan; Shi-Ti Zhang; Liang-Jing Zou; Li-Hong Meng; Fang Li; Bing-Jie Fu (Medicinal Chemistry Research, 2016)

Cloning, expression, and characterization of Pseudomonas vesicularis MA103 β-1,3-xylanase in Escherichia coli ClearColi BL21(DE3) - Wen-Sing Liang; Tsuei-Yun Fang; Hong-Ting Lin; Tristan C. Liu; Wen-Jung Lu; Wen-Shyong Tzou; Shye-Jye Tang; Fu-Pang Lin; Shiu-Mei Liu; Chorng-Liang Pan (Fisheries Science, 2015)

Antiviral effect of lithium chloride on infection of cells by canine parvovirus - Pei Zhou; Xinliang Fu; Zhongshan Yan; Bo Fang; San Huang; Cheng Fu; Malin Hong; Shoujun Li (Archives of Virology, 2015)

Effect of in planta phosphorus on aluminum-induced inhibition of root elongation in wheat - Ji Feng Shao; Jing Che; Rong Fu Chen; Jian Feng Ma; Ren Fang Shen (Plant and Soil, 2015)

Upregulation of centromere protein H is associated with progression of renal cell carcinoma - Xun Wu; Youcheng Lin; Liping Shi; Yi Huang; Caiyong Lai; Yongqiang Wang; Meng Zhang; Shupeng Wang; Baoli Heng; Ganshen Yu; Xinghua Du; Lu Fang; et al. (Journal of Molecular Histology, 2015)

ALFF Value in Right Parahippocampal Gyrus Acts as a Potential Marker Monitoring Amyotrophic Lateral Sclerosis Progression: a Neuropsychological, Voxel-Based Morphometry, and Resting-State Functional MRI Study - Wenjia Zhu; Xiaoling Fu; Fang Cui; Fei Yang; Yuting Ren; Xiaoyun Zhang; Xiaolan Zhang; Zhaohui Chen; Li Ling; Xusheng Huang (Journal of Molecular Neuroscience, 2015)

Transcriptional Responses in Adult Zebrafish (Danio rerio) Exposed to Propranolol and Metoprolol - Liwei Sun; Fang Liu; Haigang Chen; Sisi Wang; Xia Lin; Jian Chi; Qing Zhu; Zhengwei Fu (Ecotoxicology, 2015)

Capecitabine plus oxaliplatin (XELOX) compared with 5-fluorouracil/leucovorin plus oxaliplatin (FOLFOXs) in advanced gastric cancer: meta-analysis of randomized controlled trials - Hong-Bin Xu; Fang Huang; Rui Su; Fu-Ming Shen; Qian-Zhou Lv (European Journal of Clinical Pharmacology, 2015)

A measurement of summertime dry deposition of ambient air particulates and associated metallic pollutants in Central Taiwan - Guor-Cheng Fang; Hung-Che Chiang; Yu-Cheng Chen; You-Fu Xiao; Chia-Ming Wu; Yu-Chen Kuo (Environmental Geochemistry and Health, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

Phylogenetic analysis of 32 porcine circovirus type 2 isolates from Shandong, China - Jianli Shi; Shaojian Xu; Fang Fu; Xiaoyan Cong; Xiaoyuan Yuan; Zhe Peng; Jiaqiang Wu; Wenbo Sun; Yijun Du; Jun Li; Baohua Huang; Jinbao Wang (Archives of Virology, 2015)

Effect of Saponin on the Phytoextraction of Pb, Cd and Zn from Soil Using Italian Ryegrass - Tengyi Zhu; Dafang Fu; Fang Yang (Bulletin of Environmental Contamination and Toxicology, 2015)

MiR-218-targeting-Bmi-1 mediates the suppressive effect of 1,6,7-trihydroxyxanthone on liver cancer cells - Wei-Ming Fu; Li-Peng Tang; Xiao Zhu; Ying-Fei Lu; Yan-Ling Zhang; Wayne Yuk-Wai LEE; Hua Wang; Yang Yu; Wei-Cheng Liang; Chun-Hay Ko; Hong-Xi Xu; Hsiang-Fu Kung; et al. (Apoptosis, 2015)

MiR-199a is overexpressed in plasma of type 2 diabetes patients which contributes to type 2 diabetes by targeting GLUT4 - Shuang-Tong Yan; Chun-Lin Li; Hui Tian; Jian Li; Yu Pei; Yu Liu; Yan-Ping Gong; Fu-Sheng Fang; Ban-Ruo Sun (Molecular and Cellular Biochemistry, 2014)

Isolation and characterization of 10 polymorphic microsatellite loci from the Chinese ratsnake (Zaocys dhumnades) - Rong-Fang Wang; Chao-Nan Zhu; Zhe Liu; Yan-Fu Qu (Conservation Genetics Resources, 2014)

Positional variation in grain mineral nutrients within a rice panicle and its relation to phytic acid concentration - Da Su; Faisal Sultan; Ning-chun Zhao; Bing-ting Lei; Fu-biao Wang; Gang Pan; Fang-min Cheng (Journal of Zhejiang University-SCIENCE B, 2014)

Identification and characterization of a novel phage display-derived peptide with affinity for human brain metastatic breast cancer - Bo Fu; Ying Zhang; Wei Long; Aifeng Zhang; Yafen Zhang; Yanli An; Fengqin Miao; Fang Nie; Mingli Li; Youji He; Jianqiong Zhang; Gaojun Teng (Biotechnology Letters, 2014)

SNAP25 Ameliorates Sensory Deficit in Rats with Spinal Cord Transection - Wei Wang; Fang Wang; Jia Liu; Wei Zhao; Qi Zhao; Mu He; Bao-Jiang Qian; Yang Xu; Ran Liu; Su-Juan Liu; Wei Liu; Jin Liu; et al. (Molecular Neurobiology, 2014)

Shift in abundance and structure of soil ammonia-oxidizing bacteria and archaea communities associated with four typical forest vegetations in subtropical region - Yong-Chun Li; Bu-Rong Liu; Song-Hao Li; Hua Qin; Wei-Jun Fu; Qiu-Fang Xu (Journal of Soils and Sediments, 2014)

Sodium fluoride induces apoptosis in the kidney of rats through caspase-mediated pathways and DNA damage - Guo Hua Song; Ji Ping Gao; Chun Fang Wang; Chao Yang Chen; Xiao Yan Yan; Min Guo; Yu Wang; Fu Bing Huang (Journal of Physiology and Biochemistry, 2014)

Isolation and characterization of microsatellite loci in the Ussuri mamushi (Gloydius ussuriensis) - Rong-Fang Wang; Yan-Qing Wu; Zhe Liu; Yan-Fu Qu (Conservation Genetics Resources, 2014)

Complex seismic wavefield interpolation based on the Bregman iteration method in the sparse transform domain - Fu-Yan Gou; Cai Liu; Yang Liu; Xuan Feng; Fang-Zi Cui (Applied Geophysics, 2014)

Two new eunicellin-based diterpenoids from the South China Sea gorgonian Muricella sibogae Nutting - Yuan-Ming Zhou; Min Chen; Xiu-Mei Fu; Yu-Chun Fang; Chang-Yun Wang (Natural Product Research, 2014)

Magnesium Lithospermate B Reduces Inflammatory Response in a Mouse Model of Hepatic Ischemia–Reperfusion Injury - Shaohua Song; Wenyu Liu; Fang Liu; Zhengxin Wang; Guoshan Ding; Wenyuan Guo; Zhiren Fu (Cell Biochemistry and Biophysics, 2014)

Cingulum Correlates of Cognitive Functions in Patients with Mild Cognitive Impairment and Early Alzheimer’s Disease: A Diffusion Spectrum Imaging Study - Yi-Cheng Lin; Yao-Chia Shih; Wen-Yih I. Tseng; Yu-Hsiu Chu; Meng-Tien Wu; Ta-Fu Chen; Pei-Fang Tang; Ming-Jang Chiu (Brain Topography, 2014)

Identifying novel salt-tolerant genes from Dunaliella salina using a Haematococcus pluvialis expression system - Wen-fang Gong; Li-na Zhao; Bin Hu; Xi-wen Chen; Feng Zhang; Zheng-mao Zhu; De-fu Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Microsatellite primer development for the king ratsnakes Elaphe carinata (Colubridae) - Yan-Qing Wu; Rong-Fang Wang; Long-Hui Lin; Yan-Fu Qu (Conservation Genetics Resources, 2014)

A Novel Co-immunoprecipitation Protocol Based on Protoplast Transient Gene Expression for Studying Protein–protein Interactions in Rice - Jia Wei Yang; Jia Xin Fu; Jing Li; Xiao Ling Cheng; Feng Li; Jing Fang Dong; Zhen Lan Liu; Chu Xiong Zhuang (Plant Molecular Biology Reporter, 2014)

UV-irradiation mutation of tetraspores of Gracilariopsis lemaneiformis and screening of thermotolerant strains - Feng Fu; Zheng-Hong Sui; Wei Zhou; Jin-Guo Wang; Lian-Peng Chang; Shu-Fang Ci (Journal of Applied Phycology, 2014)

Polycyclic aromatic hydrocarbons and organochlorine pesticides in rice hull from a typical e-waste recycling area in southeast China: temporal trend, source, and exposure assessment - Fang Liu; Chunyang Liao; Jianjie Fu; Jungang Lv; Qinzhao Xue; Guibin Jiang (Environmental Geochemistry and Health, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Identification of a novel frameshift mutation in PITX2 gene in a Chinese family with Axenfeld-Rieger syndrome - Hou-Fa Yin; Xiao-Yun Fang; Chong-Fei Jin; Jin-Fu Yin; Jin-Yu Li; Su-Juan Zhao; Qi Miao; Feng-Wei Song (Journal of Zhejiang University-SCIENCE B, 2014)

miR-124 Represses ROCK1 Expression to Promote Neurite Elongation Through Activation of the PI3K/Akt Signal Pathway - Xi Gu; Siying Meng; Shuhu Liu; Chunhong Jia; Yingying Fang; Shuji Li; Congcong Fu; Qiancheng Song; Lifang Lin; Xuemin Wang (Journal of Molecular Neuroscience, 2014)

Genetic variation in alkaloid accumulation in leaves of Nicotiana - Bo Sun; Fen Zhang; Guo-jun Zhou; Guo-hai Chu; Fang-fang Huang; Qiao-mei Wang; Li-feng Jin; Fu-cheng Lin; Jun Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Influence of HbA1c on short-term blood pressure variability in type 2 diabetic patients with diabetic nephropathy - Fang Liu; Min Wu; Yan-huan Feng; Hui Zhong; Tian-lei Cui; You-qun Huang; Ya-ping Liang; Yong-shu Diao; Li Zang; Ling Li; Jing Zang; Hong-yu Qiu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Altered miRNA Expression is Associated with Differentiation, Invasion, and Metastasis of Esophageal Squamous Cell Carcinoma (ESCC) in Patients from Huaian, China - Hai Long Fu; De Ping Wu; Xiu Fang Wang; Jian Guo Wang; Feng Jiao; Lei Lei Song; Hui Xie; Xu Yang Wen; Hu Sheng Shan; Yun Xiang Du; Ya Ping Zhao (Cell Biochemistry and Biophysics, 2013)

Breed-linked polymorphisms of porcine toll-like receptor 2 (TLR2) and TLR4 and the primary investigation on their relationship with prevention against Mycoplasma pneumoniae and bacterial LPS challenge - Xiaomin Fang; Xiao Liu; Cui Meng; Yanfeng Fu; Xuemin Wang; Bixia Li; Feng Tu; Fang Zhao; Shouwen Ren (Immunogenetics, 2013)

Association between CYP1A1 polymorphisms and esophageal cancer: a meta-analysis - Fang-Fang Shen; Fu-You Zhou; Qi-Si Xue; Ying Pan; Lu Zheng; Hua Zhang; Li-Dong Wang; Hou-Feng Zheng (Molecular Biology Reports, 2013)

Effect of mechanical stretch on the proliferation and differentiation of BMSCs from ovariectomized rats - Yuqiong Wu; Peng Zhang; Qinggang Dai; Xiao Yang; Runqing Fu; Lingyong Jiang; Bing Fang (Molecular and Cellular Biochemistry, 2013)

Research on the imaging of concrete defect based on the pulse compression technique - Chang-Zheng Li; Bi-Xing Zhang; Fang-Fang Shi; Fu-Li Xie (Applied Geophysics, 2013)

Effects of rosuvastatin on the production and activation of matrix metalloproteinase-2 and migration of cultured rat vascular smooth muscle cells induced by homocysteine - Ya-fei Shi; Ju-fang Chi; Wei-liang Tang; Fu-kang Xu; Long-bin Liu; Zheng Ji; Hai-tao Lv; Hang-yuan Guo (Journal of Zhejiang University-SCIENCE B, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Aluminum tolerance of wheat does not induce changes in dominant bacterial community composition or abundance in an acidic soil - Chao Wang; Xue Qiang Zhao; Rong Fu Chen; Hai Yan Chu; Ren Fang Shen (Plant and Soil, 2013)

Effects of zinc-substituted nano-hydroxyapatite coatings on bone integration with implant surfaces - Shi-fang Zhao; Wen-jing Dong; Qiao-hong Jiang; Fu-ming He; Xiao-xiang Wang; Guo-li Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Germination of phytoplankton resting cells from surface sediments in two areas of the S outhern C hinese coastal waters - Zhao‐Hui Wang; Yong‐Hu Fu; Wei Kang; Ju‐Fang Liang; Yang‐Guang Gu; Xiao‐Liang Jiang (Marine Ecology, 2013)
To understand the role of phytoplankton resting cells in the outbreak of algal blooms, particularly harmful algal blooms, surface sediments were collected monthly from A pril 2007 to M arch 2008 from two bays near the international ports in the S outhern C hinese coastal waters. Sieved sediments were incubated for 20 and 40 days, and germinated vegetative cells were observed. Altogether, 97 taxa were recorded, of which 50 were diatoms and 35 dinoflagellates. Vegetative cells of cyanobacteria, chlorophytes, dictyophytes, euglenophytes, haptophytes, and raphidophytes were also observed. Centric diatoms such as C haetoceros , M elosira , S keletonema , and T halassiosira dominated. S crippsiella , G ymnodinium , and A lexandrium were common dinoflagellate taxa. Diatom spores germinated in samples from all seasons but were abundant in the autumn and winter samples. Low numbers of dinoflagellate cells germinated in the winter samples. The nanophytoplankton taxa, G ymnodinium corii and C hrysochromulina sp., which have not been recorded in the previous phytoplankton surveys, were abundant, suggesting either their new appearance in the water column or perhaps that they were overlooked in routine phytoplankton monitoring due to their small sizes. Vegetative cells of harmful or potentially harmful taxa were germinated, and some of them such as A mphidinium , G ambierdiscus , O streopsis , and C oolia have not previously been reported in the study area. Based on the results of the incubation of sediments from the two bays near the international ports, it is suggested that international shipping increases the risk of the introduction of new phytoplankton species and thus promotes the incidence of harmful algal blooms.

Trace Element, Antioxidant Activity, and Lipid Peroxidation Levels in Brain Cortex of Gerbils After Cerebral Ischemic Injury - Kwang-Ming Fang; Fu-Chou Cheng; Yeou-Lih Huang; Shu-Ying Chung; Zhong-Yang Jian; Ming-Cheng Lin (Biological Trace Element Research, 2013)

Transgenic lines of melon (Cucumis melo L. var. makuwa cv. ‘Silver Light’) expressing antifungal protein and chitinase genes exhibit enhanced resistance to fungal pathogens - Ismail Bezirganoglu; Shaw-Yhi Hwang; Tony J. Fang; Jei-Fu Shaw (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

A SYBR Green-based real-time RT-PCR assay for simple and rapid detection and differentiation of highly pathogenic and classical type 2 porcine reproductive and respiratory syndrome virus circulating in China - Zheng Chai; Wenjun Ma; Fang Fu; Yuekun Lang; Wei Wang; Guangzhi Tong; Qinfang Liu; Xuehui Cai; Xi Li (Archives of Virology, 2013)

An in vivo molecular imaging probe 18F-Annexin B1 for apoptosis detection by PET/CT: preparation and preliminary evaluation - Ming-Wei Wang; Fang Wang; Yu-Jia Zheng; Ying-Jian Zhang; Yong-Ping Zhang; Qing Zhao; Clifton Kwang-Fu Shen; Yue Wang; Shu-Han Sun (Apoptosis, 2013)

Exon 47 skipping of fibrillin-1 leads preferentially to cardiovascular defects in patients with thoracic aortic aneurysms and dissections - Wen-Jing Wang; Peili Han; Jun Zheng; Fang-Yuan Hu; Yun Zhu; Jin-Sheng Xie; Jian Guo; Zhe Zhang; Jie Dong; Gu-Yan Zheng; Huiqing Cao; Tian-Shu Liu; et al. (Journal of Molecular Medicine, 2013)

River islands, refugia and genetic structuring in the endemic brown frog R ana kukunoris ( A nura, R anidae) of the Q inghai‐ T ibetan P lateau - Weiwei Zhou; Fang Yan; Jinzhong Fu; Shifang Wu; Robert W. Murphy; Jing Che; Yaping Zhang (Molecular Ecology, 2013)
Frequently, P leistocene climatic cycling has been found to be the diver of genetic structuring in populations, even in areas that did not have continental ice sheets, such as on the Q inghai‐ T ibetan P lateau ( QTP ). Typically, species distributed on the plateau have been hypothesized to re‐treat to south‐eastern refugia, especially during the L ast G lacial M aximum ( LGM ). We evaluated sequence variation in the mitochondrial DNA gene Cytb and the nuclear DNA gene RAG ‐1 in R ana kukunoris , a species endemic to the QTP . Two major lineages, N and S, were identified, and lineage N was further subdivided into N 1 and N 2. The geographical distribution and genealogical divergences supported the hypothesis of multiple refugia. However, major lineages and sublineages diverged prior to the LGM . Demographical expansion was detected only in lineage S and sublineage N 2. Sublineage N 1 might have survived several glacial cycles in situ and did not expand after the LGM because of the absence of suitable habitat; it survived in river islands. Genetic analysis and environment modelling suggested that the north‐eastern edge of QTP contained a major refugium for R . kukunoris . From here, lineage S dispersed southwards after the LGM . Two microrefugia in northern Q ilian M ountains greatly contributed to current level of intraspecific genetic diversity. These results were found to have important implications for the habitat conservation in N orthwest C hina.

Grain and shoot zinc accumulation in winter wheat affected by nitrogen management - Yan-Fang Xue; Shan-Chao Yue; Yue-Qiang Zhang; Zhen-Ling Cui; Xin-Ping Chen; Fu-Chun Yang; Ismail Cakmak; Steve P. McGrath; Fu-Suo Zhang; Chun-Qin Zou (Plant and Soil, 2012)

Comparative analysis of human reproductive proteomes identifies candidate proteins of sperm maturation - Liu Fu-Jun; Shen Xiao-Fang (Molecular Biology Reports, 2012)

The variation of tree beta diversity across a global network of forest plots - Miquel De Cáceres; Pierre Legendre; Renato Valencia; Min Cao; Li‐Wan Chang; George Chuyong; Richard Condit; Zhanqing Hao; Chang‐Fu Hsieh; Stephen Hubbell; David Kenfack; Keping Ma; et al. (Global Ecology and Biogeography, 2012)
Aims With the aim of understanding why some of the world's forests exhibit higher tree beta diversity values than others, we asked: (1) what is the contribution of environmentally related variation versus pure spatial and local stochastic variation to tree beta diversity assessed at the forest plot scale; (2) at what resolution are these beta‐diversity components more apparent; and (3) what determines the variation in tree beta diversity observed across regions/continents? Location World‐wide. Methods We compiled an unprecedented data set of 10 large‐scale stem‐mapping forest plots differing in latitude, tree species richness and topographic variability. We assessed the tree beta diversity found within each forest plot separately. The non‐directional variation in tree species composition among cells of the plot was our measure of beta diversity. We compared the beta diversity of each plot with the value expected under a null model. We also apportioned the beta diversity into four components: pure topographic, spatially structured topographic, pure spatial and unexplained. We used linear mixed models to interpret the variation of beta diversity values across the plots. Results Total tree beta diversity within a forest plot decreased with increasing cell size, and increased with tree species richness and the amount of topographic variability of the plot. The topography‐related component of beta diversity was correlated with the amount of topographic variability but was unrelated to its species richness. The unexplained variation was correlated with the beta diversity expected under the null model and with species richness. Main conclusions Because different components of beta diversity have different determinants, comparisons of tree beta diversity across regions should quantify not only overall variation in species composition but also its components. Global‐scale patterns in tree beta diversity are largely coupled with changes in gamma richness due to the relationship between the latter and the variation generated by local stochastic assembly processes.

An Effective Approach to Long-Term Optimal Operation of Large-Scale Reservoir Systems: Case Study of the Three Gorges System - Fang-Fang Li; Jia-Hua Wei; Xu-Dong Fu; Xin-Yu Wan (Water Resources Management, 2012)

A novel dirigent protein gene with highly stem-specific expression from sugarcane, response to drought, salt and oxidative stresses - Guo Jin-long; Xu Li-ping; Fang Jing-ping; Su Ya-chun; Fu Hua-ying; Que You-xiong; Xu Jing-sheng (Plant Cell Reports, 2012)

Characteristics and sources of non-methane hydrocarbons and halocarbons in wintertime urban atmosphere of Shanghai, China - Ping Song; Fu-Hai Geng; Xue-Fang Sang; Chuen-Yu Chan; Lo-Yin Chan; Qiong Yu (Environmental Monitoring and Assessment, 2012)

Molecular biomarkers of colorectal cancer: prognostic and predictive tools for clinical practice - Wei-qin Jiang; Fang-fang Fu; Yang-xia Li; Wei-bin Wang; Hao-hao Wang; Hai-ping Jiang; Li-song Teng (Journal of Zhejiang University-SCIENCE B, 2012)

Performance of Agasicles hygrophila (Coleoptera: Chrysomelidae), a biological control agent of invasive alligator weed, at low non-freezing temperatures - Jian-Ying Guo; Jian-Wei Fu; Xiao-Qing Xian; Ming-Yong Ma; Fang-Hao Wan (Biological Invasions, 2012)

Apoptosis induced by 1,3,6,7-tetrahydroxyxanthone in Hepatocellular carcinoma and proteomic analysis - Wei-ming Fu; Jin-fang Zhang; Hua Wang; Hong-sheng Tan; Wei-mao Wang; Shih-Chi Chen; Xiao Zhu; Tak-ming Chan; Ching-man Tse; Kwong-sak Leung; Gang Lu; Hong-xi Xu; et al. (Apoptosis, 2012)

Sphingosine 1-phosphate acts as an activator for the porcine Gpr3 of constitutively active G protein-coupled receptors - Bao-le Zhang; Ye Li; Jian-hua Ding; Fu-lu Dong; Yan-jun Hou; Bao-chun Jiang; Fang-xiong Shi; Yin-xue Xu (Journal of Zhejiang University-SCIENCE B, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Human influence on the population decline and loss of genetic diversity in a small and isolated population of Sichuan snub-nosed monkeys (Rhinopithecus roxellana) - Zong Fei Chang; Mao Fang Luo; Zhi Jin Liu; Jing Yuan Yang; Zuo Fu Xiang; Ming Li; Linda Vigilant (Genetica, 2012)

Improved LASSO priors for shrinkage quantitative trait loci mapping - Ming Fang; Dan Jiang; Dandan Li; Runqing Yang; Weixuan Fu; Lijun Pu; Huijiang Gao; Guihua Wang; Liyun Yu (Theoretical and Applied Genetics, 2012)

Spontaneous retroperitoneal hemorrhage after hemodialysis involving anticoagulant agents - Wen-xing Fan; Zheng-xu Deng; Fang Liu; Rong-bo Liu; Ling He; Bogati Amrit; Li Zang; Jing-wen Li; Xian-rong Liu; Song-min Huang; Ping Fu (Journal of Zhejiang University-SCIENCE B, 2012)

Ischemia hypothermia improved contractility under normothermia reperfusion in the model of cultured cardiomyocyte - Heng Li; Xiangshao Fang; Zhengfei Yang; Yue Fu; Yu Wang; Jinlang Wu; Tao Yu; Zitong Huang (In Vitro Cellular & Developmental Biology - Animal, 2012)

Polymorphisms of KiSS-1 and GPR54 genes and their relationships with litter size in sheep - Mingxing Chu; Chaoting Xiao; Tao Feng; Yan Fu; Guiling Cao; Li Fang; Ran Di; Qianqian Tang; Dongwei Huang; Yuehui Ma; Kui Li; Ning Li (Molecular Biology Reports, 2012)

Molecular cloning and functional analysis of one ZEITLUPE homolog GmZTL3 in soybean - Zheng-Gang Xue; Xiao-Mei Zhang; Chen-Fang Lei; Xin-Jian Chen; Yong-Fu Fu (Molecular Biology Reports, 2012)

Effect of dirhamnolipid on the removal of phenol catalyzed by laccase in aqueous solution - Zhi-Feng Liu; Guang-Ming Zeng; Hua Zhong; Xing-Zhong Yuan; Hai-Yan Fu; Mei-Fang Zhou; Xiao-Ling Ma; Hui Li; Jian-Bing Li (World Journal of Microbiology and Biotechnology, 2012)

The interaction between ubiquitin C-terminal hydrolase 37 and glucose-regulated protein 78 in hepatocellular carcinoma - Ying Fang; Jingui Mu; Yushui Ma; Duan Ma; Da Fu; Xizhong Shen (Molecular and Cellular Biochemistry, 2012)

The Activation of NMDA Receptor–ERK Pathway in the Central Amygdala is Required for the Expression of Morphine-Conditioned Place Preference in the Rat - Fang Li; Xiao-Sheng Wang; Ru-Ping Dai; Jian-Yi Zhang; Xin-Fu Zhou; Wei Hao; Chang-Qi Li (Neurotoxicity Research, 2011)

Introduction to the FY-3A Total Ozone Unit: instrument, performance and results - Weihe Wang; Xingying Zhang; Yongmei Wang; Yingjian Wang; Zhongmou Zhang; Liping Fu; Fang Jiang; Guoyang Liu (International Journal of Remote Sensing, 2011)

Soil phosphorus fractions and tree phosphorus resorption in pine forests along an urban-to-rural gradient in Nanchang, China - Xiao-Fei Hu; Fu-Sheng Chen; Gregory Nagle; Yun-Ting Fang; Ming-Quan Yu (Plant and Soil, 2011)

Resveratrol attenuates apoptosis of pulmonary microvascular endothelial cells induced by high shear stress and proinflammatory factors - Liang Xia; Fang Ding; Jun-Hui Zhu; Guo-Sheng Fu (Human Cell, 2011)

Downregulation of Cinnamyl Alcohol Dehydrogenase (CAD) Leads to Improved Saccharification Efficiency in Switchgrass - Chunxiang Fu; Xirong Xiao; Yajun Xi; Yaxin Ge; Fang Chen; Joseph Bouton; Richard A. Dixon; Zeng-Yu Wang (BioEnergy Research, 2011)

Molecular epidemiology of norovirus gastroenteritis in children in Jiangmen, China, 2005–2007 - Ying-chun Dai; Gui-fang Hu; Xu-fu Zhang; Can-lei Song; Wen-long Xiang; Xian-bo Wu; Le-yi Wang; Xi Jiang; Jun Nie (Archives of Virology, 2011)

Overexpression of a 10-deacetylbaccatin III-10 β-O-acetyltransferase gene leads to increased taxol yield in cells of Taxus chinensis - Peng Zhang; Shu-Tao Li; Ting-Ting Liu; Chun-Hua Fu; Peng-Peng Zhou; Chun-Fang Zhao; Long-Jiang Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Molecular cloning, expression, and regulation of goose leptin receptor gene in adipocytes - Fang Wang; Lizhi Lu; Hao Yuan; Yong Tian; Jinjun Li; Junda Shen; Zhengrong Tao; Yan Fu (Molecular and Cellular Biochemistry, 2011)

Characterization of a salt-tolerant xylanase from Thermoanaerobacterium saccharolyticum NTOU1 - Kuo-Sheng Hung; Shiu-Mei Liu; Tsuei-Yun Fang; Wen-Shyong Tzou; Fu-Pang Lin; Kuang-Hui Sun; Shye-Jye Tang (Biotechnology Letters, 2011)

2010 oil spill: trajectory projections based on ensemble drifter analyses - Yu-Lin Chang; Leo Oey; Fang-Hua Xu; Hung-Fu Lu; Ayumi Fujisaki (Ocean Dynamics, 2011)

A large indel mutation of the bovine ADD1/SREBP1c gene and its effects on growth traits in some native cattle breeds from China - Yong-Zhen Huang; En-Ping Zhang; Jing Wang; Yong-Tao Huai; Liang Ma; Fu-Ying Chen; Xian-Yong Lan; Chu-Zhao Lei; Xing-Tang Fang; Ju-Qiang Wang; Hong Chen (Molecular Biology Reports, 2011)

Special Distribution of Polybrominated Diphenyl Ethers in Brain Tissues of Free-range Domestic Hens and Ducks from a Village near an Electronic Waste Recycling Site in South China - Zhong-Zhi Yang; Yong-Fang Li; Shan Fu; Xing-Ru Zhao (Bulletin of Environmental Contamination and Toxicology, 2011)

Human insulin gene expressing with Bombyx mori multiple nucleopolyhedrovirus (BmMNPV) expression system - Wan-fu Yue; Fang Zhou; Jia-biao Hu; Enoch Y. Park; Joe Hull; Yun-gen Miao (World Journal of Microbiology and Biotechnology, 2011)

Genotype and host range analysis of infectious spleen and kidney necrosis virus (ISKNV) - Xiaozhe Fu; Ningqiu Li; Lihui Liu; Qiang Lin; Fang Wang; Yingtiao Lai; Haiming Jiang; Houjun Pan; Cunbin Shi; Shuqin Wu (Virus Genes, 2011)

Dietary patterns and breast cancer risk among Chinese women - Cai-Xia Zhang; Suzanne C. Ho; Jian-Hua Fu; Shou-Zhen Cheng; Yu-Ming Chen; Fang-Yu Lin (Cancer Causes & Control, 2011)

Effect of high glucose levels on the calcification of vascular smooth muscle cells by inducing osteoblastic differentiation and intracellular calcium deposition via BMP-2/Cbfα-1 pathway - Fang Liu; Hui Zhong; Jing-yuan Liang; Ping Fu; Zhi-juan Luo; Li Zhou; Rong Gou; Jun Huang (Journal of Zhejiang University-SCIENCE B, 2010)

Construction and Preliminary Analysis of a Deep-Sea Sediment Metagenomic Fosmid Library from Qiongdongnan Basin, South China Sea - Yongfei Hu; Chengzhang Fu; Yeshi Yin; Gong Cheng; Fang Lei; Xi Yang; Jing Li; Elizabeth Jane Ashforth; Lixin Zhang; Baoli Zhu (Marine Biotechnology, 2010)

Up-regulation of growth factor independence 1 in endotoxin tolerant macrophages with low secretion of TNF-α and IL-6 - Min-Fang Zhu; Jing Zhang; Jie-Ming Qu; Hui-Jun Zhang; Shuang-Cheng Zhou; Sheng-Fu Dong; Hong-Ni Jiang; Hanssa Summah (Inflammation Research, 2010)

Lowland rainforests in southern Taiwan and Lanyu, at the northern border of Paleotropics and under the influence of monsoon wind - Wei-Chun Chao; Guo-Zhang M. Song; Kuo-Jung Chao; Chi-Cheng Liao; Su-Wei Fan; Shan-Huah Wu; Tsung-Hsin Hsieh; I-Fang Sun; Yau-Lun Kuo; Chang-Fu Hsieh (Plant Ecology, 2010)

Total estrogenic activity and nonylphenol concentration in the Donggang River, Taiwan - Meei-Fang Shue; Fu-An Chen; Ting-Chien Chen (Environmental Monitoring and Assessment, 2010)

Identification of an intergenic region that is not essential for replication of goatpox virus - Wenge Ma; Fang Wang; Li Yu; Ying Xue; Yan Wang; Jie Wei; Jiong Huang; Zihua Fu (Archives of Virology, 2010)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

Investigations on boron levels in drinking water sources in China - Ren-ji Xu; Xiao-ru Xing; Qun-fang Zhou; Gui-bin Jiang; Fu-sheng Wei (Environmental Monitoring and Assessment, 2010)

Fluorescent Property of the Gd3+-Doped Terbium Complexes and Crystal Structure of [Tb(TPTZ)(H2O)6]Cl3·3H2O - Yan-Fang Zhao; Yong-Liang Zhao; Feng Bai; Xiao-yan Wei; Yong-sheng Zhou; Mei-na Shan; Huan-huan Li; Rui-jun Ma; Xiao-tao Fu; Yan Du (Journal of Fluorescence, 2010)

Association between transforming growth factor β1 polymorphisms and left ventricle hypertrophy in essential hypertensive subjects - Hai-Ying Xu; Xu-Wei Hou; Li-Fang Wang; Ning-Fu Wang; Jian Xu (Molecular and Cellular Biochemistry, 2010)

Meat and egg consumption and risk of breast cancer among Chinese women - Cai-Xia Zhang; Suzanne C. Ho; Yu-Ming Chen; Fang-Yu Lin; Jian-Hua Fu; Shou-Zhen Cheng (Cancer Causes & Control, 2009)

Developmental Control of Lignification in Stems of Lowland Switchgrass Variety Alamo and the Effects on Saccharification Efficiency - Hui Shen; Chunxiang Fu; Xirong Xiao; Tui Ray; Yuhong Tang; Zengyu Wang; Fang Chen (BioEnergy Research, 2009)

Studying the Interaction of Pirarubicin with DNA and Determining Pirarubicin in Human Urine Samples: Combining Excitation -Emission Fluorescence Matrices with Second-order Calibration Methods - Hong-Yan Zou; Hai-Long Wu; Yan Zhang; Shu-Fang Li; Jin-Fang Nie; Hai-Yan Fu; Ru-Qin Yu (Journal of Fluorescence, 2009)

An investigation of vitamin B12 deficiency in elderly inpatients in neurology department - Yu-Hui Wang; Fang Yan; Wen-Bo Zhang; Gang Ye; Yun-Yun Zheng; Xu-Hua Zhang; Fu-Yuan Shao (Neuroscience Bulletin, 2009)

Infection and replication of avian influenza H5N1 virus in an infected human - Jing-Jiao Zhou; Dan-Yun Fang; Jie Fu; Jiang Tian; Jun-Mei Zhou; Hui-Jun Yan; Yu Liang; Li-Fang Jiang (Virus Genes, 2009)

Caspase-3 binds diverse P4 residues in peptides as revealed by crystallography and structural modeling - Bin Fang; Guoxing Fu; Johnson Agniswamy; Robert W. Harrison; Irene T. Weber (Apoptosis, 2009)

Genetic analysis of H3 subtype influenza viruses isolated from domestic ducks in northern China during 2004–2005 - Juan Pu; Qin-Fang Liu; Ying-Ju Xia; Yu-Lei Fan; Earl G. Brown; Fu-Lin Tian; Jin-Hua Liu (Virus Genes, 2009)

Studies on the Toxicological Effects of PFOA and PFOS on Rats Using Histological Observation and Chemical Analysis - Lin Cui; Qun-fang Zhou; Chun-yang Liao; Jian-jie Fu; Gui-bin Jiang (Archives of Environmental Contamination and Toxicology, 2009)

Consumption of Grape Seed Extract Prevents Amyloid-β Deposition and Attenuates Inflammation in Brain of an Alzheimer’s Disease Mouse - Yan-Jiang Wang; Philip Thomas; Jin-Hua Zhong; Fang-Fang Bi; Shantha Kosaraju; Anthony Pollard; Michael Fenech; Xin-Fu Zhou (Neurotoxicity Research, 2009)

Structural basis for executioner caspase recognition of P5 position in substrates - Guoxing Fu; Alexander A. Chumanevich; Johnson Agniswamy; Bin Fang; Robert W. Harrison; Irene T. Weber (Apoptosis, 2008)

Root phosphate exudation and pH shift in the rhizosphere are not responsible for aluminum resistance in rice - Rong Fu Chen; Ren Fang Shen (Acta Physiologiae Plantarum, 2008)

Desert disturbance assessments of regional oil exploitation by Aster and ETM+ images in Taklimakan Desert China - Wei Ouyang; Fang-Hua Hao; Yongshuo Fu; Jiaxun Zhang (Environmental Monitoring and Assessment, 2008)

The sweet potato sporamin promoter confers high-level phytase expression and improves organic phosphorus acquisition and tuber yield of transgenic potato - Ya-Fang Hong; Chang-Yeu Liu; Kuo-Joan Cheng; Ai-Ling Hour; Min-Tsair Chan; Tung-Hai Tseng; Kai-Yi Chen; Jei-Fu Shaw; Su-May Yu (Plant Molecular Biology, 2008)

On indexing in the Web of Science and predicting journal impact factor - Xiu-fang Wu; Qiang Fu; Ronald Rousseau (Journal of Zhejiang University-SCIENCE B, 2008)

White-spot disease of Chinese soft-shelled turtles (Trionyx sinens) caused by Paecilomyces lilacinus - Xiao-liang Li; Chu-long Zhang; Wei-huan Fang; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2008)

Population genetics of Ageratina adenophora using inter-simple sequence repeat (ISSR) molecular markers in China - Fu-Rong Gui; Fang-Hao Wan; Jian-Ying Guo (Plant Biosystems, 2008)

Secretion of malate and citrate from roots is related to high Al-resistance in Lespedeza bicolor - Xiao Ying Dong; Ren Fang Shen; Rong Fu Chen; Zhao Liang Zhu; Jian Feng Ma (Plant and Soil, 2008)

The concentrations, distribution and sources of PAHs in agricultural soils and vegetables from Shunde, Guangdong, China - Yong Tao Li; Fang Bai Li; Jun Jian Chen; Guo Yi Yang; Hong Fu Wan; Tian Bin Zhang; Xiao Duo Zeng; Jian Ming Liu (Environmental Monitoring and Assessment, 2008)

Inhibition by oxytocin of methamphetamine-induced hyperactivity related to dopamine turnover in the mesolimbic region in mice - Jia Qi; Jing-Yu Yang; Ming Song; Yan Li; Fang Wang; Chun-Fu Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Reduced expression of GSTM2 and increased oxidative stress in spontaneously hypertensive rat - Si-Gui Zhou; Ping Wang; Rong-Biao Pi; Jie Gao; Jia-Jia Fu; Jian Fang; Jia Qin; Hui-Jie Zhang; Rui-Fang Li; Shao-Rui Chen; Fu-Tian Tang; Pei-Qing Liu (Molecular and Cellular Biochemistry, 2008)

A novel thioredoxin reductase inhibitor inhibits cell growth and induces apoptosis in HL-60 and K562 cells - Zuo-fu Peng; Lin-xiang Lan; Fang Zhao; Jing Li; Qiang Tan; Han-wei Yin; Hui-hui Zeng (Journal of Zhejiang University-SCIENCE B, 2008)

Construction of a flocculating yeast for fuel ethanol production - Fu-Zhuan Wang; Wei Shen; Zhi-Ming Rao; Hui-Ying Fang; Xiao-Bei Zhan; Jian Zhuge (Biotechnology Letters, 2007)

Identification of the distinct promoters for the two transcripts of apoptosis related protein 3 and their transcriptional regulation by NFAT and NFκB - Guodong Yang; Fang Yu; Haiyan Fu; Fan Lu; Bo Huang; Liyuan Bai; Zhongliang Zhao; Libo Yao; Zifan Lu (Molecular and Cellular Biochemistry, 2007)

Evaluation of dermal absorption and protective effectiveness of respirators for xylene in spray painters - Fu-Kuei Chang; Mei-Lien Chen; Shu-Fang Cheng; Tung-Sheng Shih; I-Fang Mao (International Archives of Occupational and Environmental Health, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Edaravone neuroprotection effected by suppressing the gene expression of the Fas signal pathway following transient focal ischemia in rats - Bo Xiao; Fang -Fang Bi; Yue -Qiang Hu; Fa -Fa Tian; Zhi -Guo Wu; Hadi M. Mujlli; Ling Ding; Xin -Fu Zhou (Neurotoxicity Research, 2007)

Molecular characterization of the surface glycoprotein genes of an H5N1 influenza virus isolated from a human in Guangdong, China - J.-J. Zhou; J. Fu; D.-Y. Fang; H.-J. Yan; J. Tian; J.-M. Zhou; J.-P. Tao; Y. Liang; L.-F. Jiang (Archives of Virology, 2007)

Identification of the distinct promoters for the two transcripts of apoptosis related protein 3 and their transcriptional regulation by NFAT and NFκB - Guodong Yang; Fang Yu; Haiyan Fu; Fan Lu; Bo Huang; Liyuan Bai; Zhongliang Zhao; Libo Yao; Zifan Lu (Molecular and Cellular Biochemistry, 2007)

Protein kinase C-ζ regulation of GLUT4 translocation through actin remodeling in CHO cells - Xiao-Jun Liu; Chang Yang; Nishith Gupta; Jin Zuo; Yong-Sheng Chang; Fu-De Fang (Journal of Molecular Medicine, 2007)

Expression of a grape calcium-dependent protein kinase ACPK1 in Arabidopsis thaliana promotes plant growth and confers abscisic acid-hypersensitivity in germination, postgermination growth, and stomatal movement - Xiang-Chun Yu; Sai-Yong Zhu; Gui-Feng Gao; Xiao-Jing Wang; Rui Zhao; Ke-Qin Zou; Xiao-Fang Wang; Xiao-Yan Zhang; Fu-Qing Wu; Chang-Cao Peng; Da-Peng Zhang (Plant Molecular Biology, 2007)

Expression of CYP2E1 in human nasopharynx and its metabolic effect in vitro - De-Fu Hou; Shui-Liang Wang; Zhi-Min He; Fang Yang; Zhu-Chu Chen (Molecular and Cellular Biochemistry, 2007)

Isolation of a human gallbladder cancer cell clone with high invasive phenotype in vitro and metastatic potential in orthotopic model and inhibition of its invasiveness by heparanase antisense oligodeoxynucleotides - Xin-Zhong Chang; Zhan-Min Wang; Jin-Ming Yu; Fu-Guo Tian; Wei Jin; Yi Zhang; Jie Yu; Lian-Fang Li; Xiao-Feng Liu; Zhi-Wei Li; Zhi-Min Shao (Clinical & Experimental Metastasis, 2007)

Genetic Diversity of Traditional Chinese Mustard Crops Brassica juncea as Revealed by Phenotypic differences and RAPD Markers - Jie Fu; Ming-Fang Zhang; Xiao-Hua Qi (Genetic Resources and Crop Evolution, 2006)

Buckwheat accumulates aluminum in leaves but not in seeds - Ren Fang Shen; Rong Fu Chen; Jian Feng Ma (Plant and Soil, 2006)

Heterologous Expression and Purification of Recombinant Allophycocyanin in Marine Streptomyces sp. Isolate M097 - Yan-Hua Hou; Song Qin; You-Xun Li; Fu-Chao Li; Huan-Zhang Xia; Fang-Qing Zhao (World Journal of Microbiology and Biotechnology, 2006)

A fine physical map of the rice chromosome 5 - Chia-Hsiung Cheng; Mei-Chu Chung; Shu-Mei Liu; Shi-Kuang Chen; Fang-Yi Kao; Shu-Jen Lin; Shin-Hsin Hsiao; I-Chieh Tseng; Yue-Ie C. Hsing; Hong-Pang Wu; Ching-San Chen; Jei-Fu Shaw; et al. (Molecular Genetics and Genomics, 2005)

Small heat-shock protein 22 mutated in autosomal dominant Charcot-Marie-Tooth disease type 2L - Bei-sha Tang; Guo-hua Zhao; Wei Luo; Kun Xia; Fang Cai; Qian Pan; Ru-xu Zhang; Fu-feng Zhang; Xiao-min Liu; Biao Chen; Cheng Zhang; Lu Shen; et al. (Human Genetics, 2005)

The serotonergic system may be involved in the sleep-inducing action of oleamide in rats - Jing-Yu Yang; Chun-Fu Wu; Fang Wang; Hong-Rui Song; Wen-Jun Pan; Yu-Ling Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Use of oligonucleotide fingerprinting and faecal DNA in identifying the distribution of the Chinese tiger (Panthera tigris amoyensis Hilzheimer) - Qiu-Hong Wan; Sheng-Guo Fang; Guo-Fu Chen; Zhang-Ming Wang; Ping Ding; Mu-Yuan Zhu; Kong-Shou Chen; Jiu-Hua Yu; Yue-Ping Zhao (Biodiversity and Conservation, 2003)

G-box binding coincides with increased Solanum melongena cysteine proteinase expression in senescent fruits and circadian-regulated leaves - Zeng-Fu Xu; Mee-Len Chye; Hong-Ye Li; Fang-Xiu Xu; Kwok-Ming Yao (Plant Molecular Biology, 2003)

Relations of soil properties to topography and vegetation in a subtropical rain forest in southern Taiwan - Zueng-Sang Chen; Chang-Fu Hsieh; Feei-Yu Jiang; Tsung-Hsin Hsieh; I-Fang Sun (Plant Ecology, 1997)